Development and clinical validation of a PCR assay for human parvovirus B19 detection with applications in challenging diagnostic scenarios - Kashmi Sharma; Rohan Shrivastava; Somesh Mishra; Poonam Parihar; Debasis Biswas; Narendra Kumar Chaudhary; Poorva Gohiya; Mahendra Jain; Ram K. Nema; Ashwin A. Raut; Vandana Gupta; Megha Katare Pandey (Molecular Biology Reports, 2026)

Engineering the Perfect Medicated Nail Lacquer: Quality by Design–Driven Optimization Strategy for Boosting Antifungal Nail Penetration - Poonam Chandra; Reshu Agrawal; Sunil K. Jain (Journal of Pharmaceutical Innovation, 2026)

Biochemical and molecular profiling of stress-responsive traits and genes in climate-resilient PGPRs - Deepanjali Gupta; Kiran P. Raverkar; Navneet Pareek; Poonam Gautam; Ajay Veer Singh; Kanchan Karki; Shivanshu Garg; Geetanjali Bhandari (Physiological and Molecular Plant Pathology, 2026)

Air movement and temperature regime in large stacked apple bins during the initial phases of cold storage - Tuany Gabriela Hoffmann; Poonam Bidgar; Jincheng Yu; Daniel Alexandre Neuwald; Reiner Jedermann; Manfred Linke; Pramod Mahajan (Biosystems Engineering, 2026)

Isolation, characterization and evaluation of growth kinetics and multilineage differentiation of ovine ovarian mesenchymal stem cells - Poonam Singh; S. Nandi; J. Ghosh; S. Mondal; A. Arangasamy; P.S.P. Gupta (Theriogenology, 2026)

In vitro micropropagation and regeneration optimization of Convolvulus prostratus Forssk.: An important medicinal plant - Dinesh Vasava; Pranav Joshi; Deepak Jadav; Poonam Bhagriya (South African Journal of Botany, 2026)

Enhancing postharvest quality and vase life of Gladiolus hybridus Hort. Using herbal extracts of mentha, tea and eucalyptus - Ananya Sood; Harman; Anita Choudhary; Aman Kumar; Vandana Jaiswal; Poonam Kumari (South African Journal of Botany, 2026)

Targeted Nano-delivery of Recombinant Therapeutic Cargos for Ovarian Cancer: Advances in Molecular Pharmacodynamics and Pharmacokinetics - Om Chandrakar; Trilochan Satapathy; Poonam Sahu; Kamlesh Sahu (Journal of Pharmaceutical Innovation, 2026)

QbD Enabled Chebulinic Acid Solid Dispersions Encapsulated in Modified Xanthan Gum Coated Sodium Alginate Beads for Enhanced Gastric Ulcer Therapy - Bigul Yogeshwar Bhardwaj; Aditi Sharma; Rohit Sharma; Rohit Goyal; Kaisar Raza; Rakesh Pahwa; Kamal Dua; Sachin Kumar Singh; Ram Prakash Dwivedi; Jen Chang Yang; Thakur Gurjeet Singh; Poonam Negi (Journal of Pharmaceutical Innovation, 2026)

Microneedle-assisted molecular delivery in plants - Mingzhuo Li; Aditi Dey Poonam; Qingshang Wei (Trends in Plant Science, 2026)

Analytical profiling and HPTLC-based quantification of scopoletin in vitro cultured and field-grown plants of Convolvulus prostratus Forssk.: Toward phytochemical standardization - Dinesh Vasava; Pranav Joshi; Dipak Jadav; Poonam Bhagriya (South African Journal of Botany, 2026)

Plant secondary metabolites: Integrating phytochemical characterization, in silico approaches, and biotechnological innovations for future applications - Priyanka; Pooja Sharma; Mahiti Gupta; Poonam Bansal; Raj Singh; Anil Kumar Sharma; Sonal Datta (Rhizosphere, 2026)

Multi-criteria decision analysis for mass timber sourcing for construction in the United States - Vaibhav Kumar; Marco Lo Ricco; Prakash Nepal; Poonam Khatri; Richard D. Bergman; Neelam C. Poudyal (Journal of Cleaner Production, 2026)

Influence of gibberellic acid on aluminium-induced suppression of seed germination and early root growth in certain rice (Oryza sativa L.) landraces from Sikkim Himalaya - Poonam Chetry; Vijay Kumar; Shanti S. Sharma (The Nucleus, 2026)

GDP-L-Galactose Phosphorylase (GGP), L-Galactose Dehydrogenase (L-GalDH), and L-Galactono-1,4-Lactone Dehydrogenase (GLDH) are Key Genes for Screening Guava Genotypes for Higher Ascorbic Acid Content - Chukkamettu Anusha; Arumugam Nagaraja; Madhubala Thakre; Poonam Maurya; Shubham Jagga; Eldho Varghese; Nayan Deepak Gangappa; Manish Srivastav; Mohammad Tasleem; Amitha Mithra Sevanthi (Plant Molecular Biology Reporter, 2026)

Machine Learning Based Location Estimation for Analysing GPS Accuracy - Pankaj P. Tasgaonkar; Rahul Dev Garg; Pradeep Kumar Garg; Poonam Bhosale (Journal of the Indian Society of Remote Sensing, 2026)

LC-MS/MS-based discovery of new cytochalasin from fungus Rosellinia sanctae-cruciana - Nisha Sharma; Poonam Choudhary; Priya Kumari; Mohd Murtaza; Vidushi Abrol; Chetan Kumar; Rohit Singh; Sundeep Jaglan; Manoj Kushwaha (Natural Product Research, 2026)

FSH mediated endocrine disruption potential of Dibutyl phthalate in cultured ovine ovarian granulosa cells: Cytotoxicity, oxidative stress, steroidogenesis, cell senescence, and expression of related key developmental genes - Poonam Singh; Bogapathi Sampath Kumar; Sumanta Nandi; Paluru Subramniyam Parameswara Gupta; Sukanta Mondal (Reproductive Toxicology, 2026)

Optimizing water retention and nutrient release in soil with diammonium phosphate-loaded guar gum/diatomite composite hydrogel: Implications for agriculture - Poonam BARALA; Parul SANGWAN; Jyoti YADAV; Vinita HOODA (Pedosphere, 2026)

Electrostatic spray drying of whey protein-carbohydrate systems: Influence of pH, water activity, and storage temperature on Maillard reactions - Doll Chutani; Poonam Rani; Thom Huppertz; Eoin Murphy (International Dairy Journal, 2026)

Engineering Alternative Proteins for Future Foods: Advances in Cultivated Meat, Precision Fermentation, and Plant Protein Structuring - Vanshika Verma; Vinay Kumar Pandey; Ruchi Sharma; Poonam Verma (Food Bioscience, 2026)

SEM based morphological characterization of larval, pupal and adult stages of dengue vector Aedes albopictus (Diptera: Culicidae) - Poonam Kumari; Dixit Sharma; Pankaj Thakur; Sunil Kumar (Zoomorphology, 2026)

Unraveling the Impact of Microplastics and Particulate Matter on Lung Cancer: A Climate Perspective on Air Pollution and Public Health - Abija James; Avinash Sharma; Henok Gulilat; Dinesh Kumar; Poonam Negi; Rupak Nagraik (Water, Air, & Soil Pollution, 2026)

Dynamic regulation of porcine luteal physiology by fibroblast growth factors: expression patterns and FGF2 modulation in-vitro - Rishi Nanda; V. S. Chouhan; Poonam Yadav; H. A. Samad; Sanjib Borah; Simson Soren; Devojyoti Dutta; V. P. Maurya; Gyanendra Singh (Veterinary Research Communications, 2026)

Advances in mutant characterization for detecting causal mutations in crop plants - Poonam G. Bhad; Shreekant Baradkar; Suvendu Mondal; Anand M. Badigannavar (Theoretical and Applied Genetics, 2026)

Regulation of Carotenogenic Pathways During Ripening and Storage in Horticultural Crops: A Review - Poonam Choudhary; Manisha Bhandari; Narsaiah Kairam; Sandeep Mann (Applied Fruit Science, 2026)

Morphological and biochemical characterization of Chironji (Buchanania cochinchinensis (Lour.) M. R. Almeida) populations from central India for biodiversity conservation - Ankur Dahayat; Naseer Mohammad; Raj Singh Yadav; Poonam Verma (Agroforestry Systems, 2026)

Development and characterization of a reserpine-induced mouse model of depression: An integrated in-vivo and in-silico approach - Karuna Gautam; Sukala Prasad; Poonam Singh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unraveling the role of non-structural proteins in the life cycle of chikungunya virus - Komal Chhikara; Dipesh Kumar Verma; Poonam Kanta; Kapil Goyal; Arnab Ghosh; Mini P. Singh (VirusDisease, 2026)

Copper oxide and zinc oxide nanoparticle-mediated elicitation of biomass and phytochemicals in Eclipta alba (L.) Hassk. tissue cultures: a sustainable biotechnological approach - Nisha Swami; Suchita Taxak; Poonam Yadav; Rakshita Malik; Anita Rani Sehrawat (In Vitro Cellular & Developmental Biology - Plant, 2026)

Quantifying the development of visual expertise in medical image interpretation using fractal eye-gaze metrics - Ghasem Azemi; Poonam Kumari; Carlo Russo; Antonio Di Ieva (Medical & Biological Engineering & Computing, 2026)

Saroglitazar, a novel PPAR-α/γ agonist, modulates thyroid hormone homeostasis through hepatic UGT expression in wistar rats - Praveen Kumar Jain; Laxit K. Bhatt; Ashvin K. Patel; Satyam Patel; Kalpesh Z. Patani; Rajesh J. Patel; Pankaj Dwivedi; Shekhar B. Kadam; Ramchandra K. Ranvir; Hiren M. Patel; Abhijit Chatterjee; Laxmikant Gupta; et al. (Chemico-Biological Interactions, 2026)

Bacillus amyloliquefaciens-responsive rice basic helix–loop–helix gene acts as putative regulator of phenylpropanoid pathway, carbohydrate metabolism, and ion homeostasis under nutrient-deficient conditions - Nikita Bisht; Harshita Joshi; Anshu Anshu; Shanshank Kumar Mishra; Poonam C. Singh; Puneet Singh Chauhan (Planta, 2026)

Assessment of organic and inorganic contaminants in handmade paper industry effluents from Rajasthan, India: a field-based physicochemical, ICP-MS, and GC–MS investigation - Om Prakash; Rahul Mishra; Devyani Srivastava; Anju Patel; Poonam C. Singh (Environmental Monitoring and Assessment, 2026)

Improved micropropagation protocol for pomegranate ‘Bhagva’: media optimization, trait correlation, and genetic stability - Fenil Patel; Poonam Patel; Jagruti Mahla; Chaitanya Joshi; Madhvi Joshi (In Vitro Cellular & Developmental Biology - Plant, 2026)

“Alpha ketoglutarate mediated regulation of maturation and oxidative balance” in OPU derived Bos indicus oocytes - Rele Gauri Shrikant; V.S. Chouhan; Chinmay Warghat; Poonam Yadav; Shweta Sharma; H.A. Samad; Brijesh Kumar; V.P. Maurya; Gyanendra Singh (Reproductive Biology, 2026)

Morphological identification and molecular characterization of Asian tiger mosquito Aedes albopictus (Diptera: Culicidae) - Poonam Kumari; Alka Rana; Kushal Thakur; Kumari Ruchika; Dixit Sharma; Sunil Kumar (Ecological Genetics and Genomics, 2026)

A sequential downstream strategy for polychromatic proteins from Spirulina platensis: integrating thermo-mechano-chemical disruption with high-yield fractionation - Neha Goel; Poonam Choudhary (Bioresource Technology Reports, 2026)

Pimprinethine: A bioactive indole–oxazole alkaloid with therapeutic potential from Streptomyces netropsis IICTRSP-174 of Leh-Ladakh origin - Somarowthu Tejaswi; R.S. Prakasham; Cheemalamarri Chandra sekhar; Bandi Siva; B. Uma Rajeswari; N. Narendra Kumar; Ravinder Reddy Patlolla; Balaji Rathod; K. SaiTeja; V. Sravanthi; Mihir Ranjan Padhan; Poonam Kumari; et al. (Bioresource Technology Reports, 2026)

Development of Proniosomal Dry Powder for Dual Pulmonary Delivery of Salbutamol Sulfate and Carvacrol: A Design of Experiment Approach - Deepa Neopane; Poonam Kushwaha; Badruddeen (Pharmaceutical Research, 2026)

Design, Development, and Characterization of a Tannic Acid-loaded Transfersomal Gel for Psoriatic Skin - Mohammad Shaif; Poonam Kushwaha; Shazia Usmani; Supriya Pandey (Pharmaceutical Research, 2026)

Osmo and Microbial seed Priming Enhances Biochemical, soil Biological and Symbiotic Traits of Soybean under Diverse Environments - Simranpreet Singh Bola; Harpreet Kaur Virk; Anil Khokhar; Navjyot Kaur; Poonam Sharma (Journal of Soil Science and Plant Nutrition, 2026)

First Comprehensive Whole Genome Analysis of Plant Growth-Promoting Endophytic Bacterium Micrococcus luteus ASd6 Isolated from Medicinal Plant Andrographis paniculata - Poonam Kumari; Shivam Chauhan; Akanksha Singh (Journal of Plant Growth Regulation, 2026)

Hulless Barley (Hordeum vulgare L.) Variety DWRB 223 - Jogendra Singh; Omvir Singh; R. P. S. Verma; Chuni Lal; Lokendra Kumar; S. K. Bishnoi; Rekha Malik; Dinesh Kumar; OP Gupta; Charan Singh; Poonam Jasrotia; Ravindra Kumar; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Genotypic characterization on the basis of chilling requirement in apple (Malus × domestica Borkh.) using simple sequence repeat (SSR) markers - Madhuri Tiwari; Rajnish Sharma; Megha Sharma; Poonam; Anamika Thakur; Parul Sharma; Pramod Verma; Anupama Singh (Genetic Resources and Crop Evolution, 2026)

Beyond new pills: integrative strategies to overcome multidrug-resistant bacteria - Poonam Sahu; Trilochan Satapathy (Archives of Microbiology, 2026)

Comprehensive Morphological and Molecular Characterization of Conopomorpha sinensis Bradley (Lepidoptera: Gracillariidae) on Litchi (Litchi chinensis) from India - Masrat Siraj; Sandeep Singh; Vikas Jindal; Rajwinder Kaur Sandhu; P. R. Shashank; Aayush Kaushal; Guranshpaul Singh; Sumanjit Kaur; Poonam Srivastava; Anamika Kar; Jaipal Singh Choudhary; M. K. Dhakar; et al. (Applied Fruit Science, 2026)

The Gut-Liver Axis in Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD): Mechanisms, Microbiome Interactions and Therapeutic Targets - Poonam Sahu; Trilochan Satapathy (Probiotics and Antimicrobial Proteins, 2026)

Aluminium alleviates fluoride toxicity in Cyamopsis tetragonoloba by enhancing growth performance and reducing fluoride uptake - Poonam Poonam; Nilima Kumari; Vinay Sharma (Vegetos, 2026)

Horticulture-Based Integrated Farming Enhances Productivity, Profitability, and Soil Biological Activity in Ustochrepts of the Upper Gangetic Plains, India - Poonam Kashyap; A. K. Prusty; A. L. Meena; Natesan Ravisankar; Rakshit Bhagat; P. C. Jat; Jairam Choudhary; Debashis Dutta; M. Shamim; Kamlesh Kumar; A. S. Panwar; M. A. Ansari; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Morphological variations and distribution of various sensilla and scales on Aedes aegypti (Diptera: Culicidae) using scanning electron microscope - Poonam Kumari; Alka Rana; Dixit Sharma; Himanshu Thakur; Pankaj Thakur; Sunil Kumar (International Journal of Tropical Insect Science, 2026)

Hydrothermal Liquefaction of Deep Eutectic Solvent Treated Alkaline Lignin for Bio-Based Chemicals Production Using Magnetic Biochar Catalyst - Snehil Rana; Km Diksha; Poonam Gera; Anjireddy Bhavanam (BioEnergy Research, 2026)

Historic Building Information Modelling Framework Using Terrestrial LiDAR for Heritage Documentation and Digital Twin Creation - Anurupa Goswami; Madhavan Sridhar; Hina Pande; Poonam S. Tiwari; Shefali Agrawal (Journal of the Indian Society of Remote Sensing, 2026)

Symbiont dominance and microbiome dysbiosis in wheat-aphid revealed through 16 S rRNA gene amplicon sequencing analysis - Poonam Jasrotia; Priyanka Chandra; Arjun Singh; Prem Lal Kashyap; Susheel Kumar Sharma (World Journal of Microbiology and Biotechnology, 2026)

Smart In Situ-Forming Ocular Therapeutics for Dry Eye Disease: Bridging Biomaterials, Nanotechnology, and Clinical Translation - Adiba Rahman; Poonam Kushwaha; Bipasha Ray; Sapna Yadav (AAPS PharmSciTech, 2026)

Synergistic Amelioration of Imidacloprid-Induced fertility impairment by Vitex agnus-castus and Nigella sativa in Female Rats: Mechanistic Evidence of Hormonal and Reproductive Restoration - Trilochan Satapathy; Darshana Rathi; Poonam Sahu (Cell Biochemistry and Biophysics, 2026)

Development and Evaluation of Sea Buckthorn Oil-Loaded SNEDDS for Hormonal and Lipid Regulation in PCOS - Sourabh Patil S P; Kanika Thakur K T; Rohit Sharma R S; Ankit Awasthi A A; Lalit Sharma L S; Bigul Yogeshwar Bhardwaj B Y B; Thakur Gurjeet Singh T G S; Poonam Negi P N (Journal of Pharmaceutical Innovation, 2026)

Mupirocin Oleogel for Enhanced Burn Wound Healing Applications: a Preclinical Study - Sunil Aher; Poonam Patil; Shreya Shevate; Shubham Munde; Popat Mohite; Ketan Ranch; Sudarshan Singh (Journal of Pharmaceutical Innovation, 2026)

Environmental footprint of chloride eutectic mixtures: A comprehensive life cycle assessment for concentrated solar power systems - Swanand R. Patange; Poonam R. Sutar; Ganapati D. Yadav (Clean Technologies and Environmental Policy, 2026)

Role of human papillomavirus (HPV) variants and host genetic susceptibility in cervical carcinogenesis - Ankita Singh; Priya Sahani; Shivangi Singh; Anupama Ojha; Poonam Gupta; Chakra Pani Awasthi; Narendra Birbiya; Sarad Kumar Mishra (Archives of Microbiology, 2026)

Spatial Diversity and Abundance of Bactrocera spp. Fruit Flies in the Northwestern Himalaya of Uttarakhand Using Methyl Eugenol Traps - Ashutosh Gairola; Poonam Srivastava; Dipti Joshi; Manoj Joshi; Jitesh Singh Bisht; Puneet Kumar Mishra (Applied Fruit Science, 2026)

Rivers of Himalaya: Response to climate and tectonic variables - Poonam Chahal; Rupa Ghosh; Debarati Nag; Anil Kumar; Yogesh Ray; Pradeep Srivastava (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Biological macromolecules in bioremediation: Exploring OMICs approaches for environmental cleanup - Priti Duhan; Kumkum Verma; Charu Lata; Bhupesh Gupta; Poonam Bansal (Ecological Genetics and Genomics, 2026)

Genetic evaluation of lactation curve characteristics in Murrah buffaloes - Rakesh Nehra; Yogesh C. Bangar; Kamaldeep Dhundwal; Sunil Kumar; Poonam Sevda; Pulkit Chugh (Tropical Animal Health and Production, 2026)

Genome-wide association mapping of rice bran oil content and γ-oryzanol reveals candidate genes for lipid biosynthesis and transport - Samrath Baghel; Parmeshwar Kumar Sahu; Ravi Raj Singh Patel; Poonam Gajanan Bhad; Sayaji Mehetre; Bikram Kishore Das; Girish Chandel; Latif Ahmad Peer; Deepak Sharma; Suvendu Mondal (Planta, 2026)

Design and characterization of phloretin-loaded PEG–lipid hybrid micelles for enhanced breast cancer therapy - Imran Ahmad; Poonam Kushwaha; Shazia Usmani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Visnagin attenuates thioacetamide-induced kidney damage through suppression of renal injury marker, oxidative stress, inflammation, apoptosis, and TGF-β-mediated renal fibrosis - Akshay Amruta Navghare; Sonu Rajput; Poonam Yadav; Sumeet Kumar Singh; Yogender Goswami; Jasvinder Singh Bhatti; Umashanker Navik (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Seed Priming Strategies with Rhizobacteria Under Thermal Stress Modulate the Emergence, Growth, Yield and Economic Potential of Soybean - Simranpreet Singh Bola; Harpreet Kaur Virk; Anil Khokhar; Navjyot Kaur; Poonam Sharma (Journal of Soil Science and Plant Nutrition, 2026)

Inactivation of Avian Influenza Virus in Raw Milk Kefir - Anna C. S. Porto-Fett; Sonsiray Alvarez-Narvaez; Poonam G. Vinayamohan; Telvin Harrell; Abdulkarim Shwani; David L. Suarez; John B. Luchansky (Food and Environmental Virology, 2026)
Both highly pathogenic avian influenza virus (HPAIV) and its viral RNA have been detected in raw milk during the ongoing outbreak in dairy cows. While pasteurization effectively inactivates the virus in milk, comparatively little has been published on AIV inactivation in fermented dairy products made from raw milk. We evaluated the viability of two isolates of low pathogenic avian influenza virus (LPAIV) during fermentation of kefir to assess the potential for viral persistence. Raw (unpasteurized) milk (ca. 3.0% fat) was inoculated with ca. 7.5 log 10 CFU per mL of active commercial kefir starter culture. Next, raw milk (125 mL) was inoculated with 1.0 mL of either strain A/rgGyrfalconHAxPR8/2014 H5N1 or A/turkey/Wisconsin/1968 H5N9 to achieve an average initial level of ca. 5.0 log 10 50% egg infectious doses (EID 50 ) per mL. The inoculated raw milk (ca. pH 6.55 ± 0.05) was fermented at 25 °C for ca. 36 h to an average endpoint pH of pH 4.44 ± 0.05. Results confirmed that fermentation of raw milk to produce kefir delivered an appreciable reduction of both LPAIV strains, that being a ca. 4.1 or 3.1 log 10 EID 50 per mL decrease of strains H5N1 or H5N9, respectively, from their initial levels in raw milk. In the absence of a starter culture, due to fermentation by the indigenous flora the pH of the raw milk after incubation at 25 °C for ca. 36 h also significantly decreased on average to ca. pH 5.3:, and levels of strains H5N1 and H5N9 were reduced by 4.1 and 3.5 log 10 EID 50 per mL, respectively. Our findings established that fermentation of raw milk (with or without added kefir starter culture) to ≤ pH 5.3 over ca. 36 h at 25 °C appreciably decreases titers (≥ 3.1 log 10 EID 50 per mL) of AIV strains H5N1 and H5N9 and, therefore, lowers risk associated with its consumption.

Echinomycin, a peptide antibiotic from a new bacterial source and its potential to tackle drug resistance in methicillin-resistant Staphylococcus aureus - Mohd Murtaza; Nitika Bhasin; Priya Kumari; Avleen Kour; Poonam Choudhary; Manoj Kushwaha; Sandeep Sharma; Sundeep Jaglan (Archives of Microbiology, 2026)

Eco-Responsive Potential of Male Bamboo Seedlings Bio Primed with Pseudomonas aeruginosa PB_AQ27 Isolate in Waste Dumpsite Soil - Poonam Bhanse; Lal Singh; Asifa Qureshi (Indian Journal of Microbiology, 2026)

New insights into the Neogene sedimentary Formations of south-western India: Implications for provenance, palaeovegetation and depositional environment - K.V. Sarath; K. Sandeep; Alka Absur; Namitha Ajay; Poonam Verma; Yogesh P. Singh; A.K. Rafaz; V. Nandakumar; G. Indu; E. Shaji (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Capsaicin supplementation modulates the nutrigenomic signature essential for energy metabolism in adipose tissue and liver of bisphenol-A exposed mice - Dhirendra Pratap Singh; Joshi Poonam; Riva Mehta; Vandana Bijalwan; Shweta Gupta; Mahendra Bishnoi; Santasabuj Das (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Optimizing GEDI Footprint Selection for Forest Canopy Height Estimation in the Western Himalaya Using Multi-sensor Data - Akshay Paygude; Hina Pande; Poonam Seth Tiwari; Praveen Kumar Varma; Manoj Kumar (Journal of the Indian Society of Remote Sensing, 2026)

Converting industrial waste cenosphere into cost-effective ceramic membranes for hydrogen separation - Poonam R. Sutar; Ujjal Mondal; Ganapati D. Yadav (Clean Technologies and Environmental Policy, 2026)

Eco-friendly Approaches for Mango Hopper Suppression: Mitigating Insecticide Resistance Across India’s Agro-ecological Zones - Poonam Srivastava; A. Y. Munj; P. V. Rami Reddy; Anamika Kar; Sachin Chavan; Sandeep Singh; J. K. Bana; R. V. Kadu; A. Nithish; K. Manasa; Prakash Patil (Applied Fruit Science, 2026)

Effects of organized guarding on mortality from human–elephant conflict in northeast India - Nitin Sekar; Tanay Bhatt; Arpit Deomurari; Sanchaya Sharma; Poonam Kumari; Athisii Kayina; E. Somanathan (Conservation Biology, 2026)
Human–elephant conflict (HEC) frequently results in human and elephant mortality, posing major social justice and conservation concerns across Asia and Africa. Although a variety of interventions have been introduced to mitigate HEC, rigorous evaluations of how they affect mortality are practically nonexistent. Using a 20‐year dataset from Sonitpur district in Assam, India, we examined whether organized guarding and short‐distance drives—which are used to manage HEC in several countries globally—led to a reduction in human and elephant mortality from conflict as intended. We controlled for changes in land use and economic development, spillover effects, and nonrandom selection of villages for intervention. Results on whether organized guarding provided protection against human death due to HEC were inconclusive. Contrary to expectations, the intervention was associated with an approximate 2.0–2.9 times increase in elephant mortality. Disaggregation based on cause of mortality suggested that elephants may be more likely to be killed accidentally in villages where organized guarding occurs. Data on crop damage by elephants were not available, and it is possible that antidepredation squads present a trade‐off that fosters greater crop protection at the expense of occasional elephant mortality. Our results highlight the indispensability of rigorous evaluations for finding solutions to human–wildlife conflict.

Design, synthesis and pharmacological evaluation of coumarin tethered 1,3,4-oxadiazole conjugates as dual binding site acetylcholinesterase ligands targeting Alzheimer’s disease - Geetakshi Arora; Ajay Kumar; Pragati Silakari; Poonam Piplani (Molecular Diversity, 2026)

Unravelling rhizosphere competent plant growth promoting bacteria for mainstreaming finger millet to climate smart agriculture - Poonam Kumari; R. S. Netam; Prafull Kumar (Folia Microbiologica, 2026)

Modeling per- and polyfluoroalkyl substance precursor transformation in groundwater at a well-characterized site - Emily B. Stockwell; David T. Adamson; Jeff D. Gamlin; Poonam R. Kulkarni; Aman Singh; Ronald W. Falta; Charles J. Newell (Journal of Contaminant Hydrology, 2026)

Upcycled jojoba protein as a plant-based hydrocolloid: Insights into emulsification and gelation for sustainable food systems - Nevetha Ravindran; Poonam Singha; Sushil Kumar Singh (Bioresource Technology, 2026)

Predicting performance traits in Murrah buffaloes using machine learning: a comparative approach - Rakesh Nehra; Yogesh C. Bangar; C. S. Patil; Kamaldeep Dhundwal; Poonam Sevda (Tropical Animal Health and Production, 2026)

Chlorogenic Acid Fails to Confer Neuroprotection in a Chronic Mouse Model of Parkinson’s Disease - Akshaya Rajan; Surya Prakash; Devendra Singh; Poonam Thakur (Molecular Neurobiology, 2026)

Mechanical and Microstructural Properties of Cohesive Soil Stabilized with Fly Ash and Lime Sludge Based Geopolymer - Jitendra Singh Yadav; Poonam Shekhawat; Praveen Kumar (Geotechnical and Geological Engineering, 2026)

Strategies to decipher silent biosynthetic gene clusters in actinomycetes - Mohd Murtaza; Puja Gupta; Poonam Choudhary; Mehnaza Manzoor; Sandeep Sharma; Sundeep Jaglan (Archives of Microbiology, 2026)

Advances in microplastic mitigation: current progress and future directions - Vivek Kumar Gaur; Yashika Raheja; Prachi Gaur; Nitish Kumar; Poonam Sharma; Ajay Kumar; Janmejai Kumar Srivastava (Archives of Microbiology, 2026)

Brightly Luminescent Red-Emitting Europium (III) Complexes Prepared with Fluro Quinoline and Ancillary Ligands - Poonam Kumari; Vaishnavi Lather; Pratibha Ahlawat; Bhawna Rathee; Harkesh Sehrawat; V. B. Taxak; Rajesh Kumar (Journal of Fluorescence, 2025)

Mitochondrial Derived Peptides (MDPs) as Emerging Gero Protectors: Molecular Signaling, Systemic Effects, and Translational Perspectives - Poonam Sahu; Abinash Satapathy; Abhisek Satapathy; Trilochan Satapathy (International Journal of Peptide Research and Therapeutics, 2025)

Generation and characterization of early stage oral cancer cell line of buccal mucosa of Indian origin - Akhila George; Sudhir Nair; Kumar Prabhash; Sayujata Thakur; Poonam Gera; Arjun Singh; Pankaj Chaturvedi; Swapnil Rane; Trupti Pradhan; Subrata Sen; Madan Barkume; Dhanlaxmi Shetty; et al. (Human Cell, 2025)
Being topmost cancer in India, oral cancer management warrants discovery of novel biomarkers, treatment strategies, and targets to help with early diagnosis, treatment, and recovery. To have a continuous supply of cells, the study was aimed at generation and characterization of established cell line from buccal mucosa (BM) tumors from patients of Indian origin which can be developed as a pre-clinical tool for biomedical application. Surgically resected tumor tissue from histo-pathologically confirmed oral cancer were processed for explant culture. TBM-02 cell line was passaged and characterized for morphology and function. Further, the cell line was silenced for inflammasome pathway gene NLRP3 to evaluate its linkage with oral cancer tumorigenesis. TBM-02, successfully established from BM, was maintained up to 100 passages, exhibited epithelioid morphology, high EpCam expression and triploid ploidy with chromosomal aberrations. Novelty and human origin of TBM-02 was authenticated by Short Tandem Repeats profiling and comparison with DSMZ database. TBM-02 revealed tumorigenic potential in vitro and in vivo which was abrogated on silencing NLRP3. Increased expression of NLRP3, hallmark of chronic inflammation in TBM-02, was validated at protein and gene level and in xenograft. TBM-02 demonstrated migratory potential and was found to be a sensitive tool to study drug response. RNA sequencing demonstrated upregulation of oral cancer-associated genes and pathways. Thus, in current study, we have reported development of novel cell line from early-stage buccal mucosa cancer patient which has a strong potential to be developed and to be used as pre-clinical model for improving oral cancer management and therapeutics. Graphical Abstract

Harnessing therapeutic potential of bromelain and its nanoformulations: sojourn of pineapple from food to nanomedicine - Rajge Rahul Ravindra; Jaskiran Kaur; Sukriti Vishwas; M.V.N.L. Chaitanya; Narendra Kumar Pandey; Md Sadique Hussain; Poonam Negi; Gaurav Gupta; Popat Kumbhar; John Disouza; Sachin Kumar Singh (DARU Journal of Pharmaceutical Sciences, 2025)

Artificial Intelligence in Ocular Drug Delivery: Precision Drug Delivery's New Horizon - Vaibhavi Srivastava; Pragya Yadav; Abhishek Yadav; Poonam Parashar (AAPS PharmSciTech, 2025)

Emerging paradigms in diabetic neuropathy: Epigenetics, phytotherapy, machine-learning-based diagnostics and clinical trials of herbal interventions - Poonam Vashishta; Mahima Chauhan; Rajesh Asija (Next Research, 2025)

A literature review on enablers for the adoption of integrated sustainable green lean six sigma agile manufacturing system (ISGLSAMS) - Dharmendra Hariyani; Poonam Hariyani; Sanjeev Mishra (Next Research, 2025)

Diversity analysis and risk assessment of microplastics in terrestrial soil across different landuses of northern India - Ekta Gupta; Shweta Yadav; Priyansha Gupta; Virendra Kumar Mishra; Anju Patel; Mahua Saha; Poonam C. Singh; Pankaj Kumar Srivastava (Gondwana Research, 2025)

Hypercholesterolemia management beyond conventional therapy using Sugarcane Policosanol (a lipid-lowering agent): A systematic review - Parinitha A; Navjot Kaur; Poonam Aggarwal; Sukhpreet Kaur; Sandra Maria Barbalho (Food and Humanity, 2025)

Extraction of gum from fenugreek seeds: Structural composition and rheological characterization - Navjot Kaur; Hamid; Rafeeya Shams; Kshirod Kumar Dash; Poonam Choudhary; Sandeep Mann; Pintu Choudhary (Food and Humanity, 2025)

Genomic insights into plant-microbe interactions - Pushpa Gehlot; Jyoti Yadav; Poonam Meena; Priya Soni; Tripta Jain (Ecological Genetics and Genomics, 2025)

Empagliflozin in diabetic cardiomyopathy: elucidating mechanisms, therapeutic potentials, and future directions - Aiswarya Jaiswal; Poonam Yadav; Pushkar Singh Rawat; Maninder Kaur; Srivalliputturu Sarath Babu; Amit Khurana; Jasvinder Singh Bhatti; Umashanker Navik (Molecular Biology Reports, 2025)

Artemisinin’s molecular symphony: illuminating pathways for cancer therapy - Sandeep Kumar Jhade; Karthik Kalidoss; Poonam Kumari Pathak; Rahul Shrivastava (Molecular Biology Reports, 2025)

Downregulation of Glycogen Synthase Kinase-3 Beta by Urtica dioica L. Contributes to Neuroprotection Against Aluminum Chloride-Mediated Neurotoxicity in Zebrafish Larvae - Rajneesh Kumar; Poonam Dhiman; Shiv Kumar Saini; Damanpreet Singh (Molecular Neurobiology, 2025)

Click Chemistry: an overview and recent updates in the medicinal attributes of click-derived heterocycles - Poonam Bishnoi; Bhavna Saroha; Suresh Kumar; Gourav Kumar; Arpana Bhardwaj; Meena Kumari; Naveen Kumar (Molecular Diversity, 2025)

Efficacy of Seed Priming Technology in Ameliorating Metals and Metalloids Toxicity in Crops: Prospective and Issues - Debojyoti Moulick; Subhas Chandra Santra; Arnab Majumdar; Anupam Das; Bhaben Chowardhara; Bedabrata Saha; Dibakar Ghosh; Jayjit Majumdar; Munish Kumar Upadhyay; Poonam Yadav; Sukamal Sarkar; Sourav Garai; et al. (Reviews of Environmental Contamination and Toxicology, 2025)

Understanding and Management of Fruit Drop in Litchi Cultivation - V. R. Gharge; Narayan Lal; Poonam; Jyoti Singh; Arunima Tripathi; Kalyani Nagraj; Johnson Lakra (Applied Fruit Science, 2025)

Evaluation of a Native Isolate of Metarhizium anisopliae (Metschn.) Sorokin Against the Mango Leaf Hopper Complex (Idioscopus spp.) Infesting Mango (Mangifera indica L.) for Organic Fruit Production - T. K. Radha; P. N. Ganga Vishalakshy; P. V. Rami Reddy; A. Nithish; Sachin Chavan; Poonam Shrivastava; Suganya Kanna; Anamika Kar; A. Y. Munj; M. C. Keerthi; Prakash Patil (Applied Fruit Science, 2025)

A review update on Ganoderma species: etiology and management approaches - Pratibha Thakur; Sonali Khanal; Ashwani Tapwal; Neha Sharma; Poonam Chauhan; Tamanna Singh Thakur; Dinesh Kumar; Rachna Verma (Antonie van Leeuwenhoek, 2025)

Potential of potassium silicate application on barley, Hordeum vulgare for management of corn-leaf aphid, Rhopalosiphum maidis (Fitch) L - Sunny Maanju; Surender Singh Yadav; Poonam Jasrotia; Manoj Kumar Jat; Preeti Sharma; Gyanendra Singh (Crop Protection, 2025)

Bisphenol-A at an environmentally plausible dose caused gut microbiota-led impaired cognitive performances in adult mice - Dhirendra Pratap Singh; Vandana Bijalwan; Joshi Poonam; Roshan Lal; Rajendra Palkhade; Ankit Viramgami; Heena Vidhani; Ashish Kumar; Mahendra Bishnoi; Santasabuj Das (Journal of Hazardous Materials, 2025)

Glandular prickles in Rosa hybrida accumulate specific sesquiterpenes implicated in defense against aphid pests - Aarzoo Dhiman; Anand Mishra; Rajveer Singh; Rimpy Diman; Mohit Kumar Swarnkar; Poonam Kumari; Vivek Dogra (Biocatalysis and Agricultural Biotechnology, 2025)

Tiny Plastics, Massive Consequences: The Environmental and Health Crisis of Micro (Nano) Plastics - Prachi Gaur; Yashika Raheja; Raj Kumar Regar; Amarnath Singh; Komal Kumari; Ankita Kumari; Poonam Sharma; Vivek Kumar Gaur; Janmejai Kumar Srivastava (Water, Air, & Soil Pollution, 2025)

Genetic evaluation of early reproductive traits in Beetal goats - Poonam Sevda; Yogesh C. Bangar; Sunil Kumar; Rakesh Nehra; Manoj Kumar (Tropical Animal Health and Production, 2025)

Modelling lactation curve in Murrah buffaloes using non-linear models - Rakesh Nehra; Yogesh C. Bangar; Kamaldeep Dhundwal; Narender Singh; Poonam Sevda; Poonam Ratwan (Tropical Animal Health and Production, 2025)

Identification of a natural RcLOG1 allele linked to prickle development in Rose (Rosa spp.) - Priya Kumari; Himanshi Gangwar; Vijay Gahlaut; Poonam Kumari; Vandana Jaiswal (Planta, 2025)

Advancing pulmonary therapy: the role of dry powder inhalation technology in lung disease management - Imran Ahmad; Poonam Kushwaha; Abdul Hafeez (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Intricate Relationship of Trk Receptors in Brain Diseases and Disorders - Sarthak Dahiya; Poonam Sharma; Bhupesh Sharma; Priyanka Saroj; Harsha Kharkwal; Nitin Sharma (Molecular Neurobiology, 2025)

Impact of weather parameters and integrated disease management practices on banded leaf and sheath blight (caused by Rhizoctonia solani f. sp. sasakii) and grain yield of maize - Parvesh Kumar; Rakesh Mehra; Poonam Kumari; Prashant Chauhan; Rakesh Kumar; Harbinder Singh; Vishal Gandhi; Mahaveer Singh Bochalya; Ashish Jain; Sumit (European Journal of Plant Pathology, 2025)

Ramification of mycogenic copper oxide nanoparticles on wastewater remediation from selected sites of Yamuna River - Somani Chandrika Rath; Pankaj Sah; Poonam Sharma; Amit C. Kharkwal; Arti Goel (Environmental Geochemistry and Health, 2025)

Bovine β-defensin 129 (BBD129) polymorphisms associated with differential posttranslational O-glycosylation and phosphorylation modifications perturb the sperm functions and their fertilizing potential - Subhash Solanki; Abhishek Kumar; Poonam Kashyap; Rakesh Kumar; Tirtha Kumar Datta (Animal Reproduction Science, 2025)

Towards sustainable aquaponics: a bibliometric analysis of trends, scientific developments, and thematic evolution - Ahmad Faisal; Poonam Biswal; Debasruti Bhattacharya; Suraj Kumar; Mamoni Banerjee; Gourav Dhar Bhowmick; Dillip Kumar Swain (Aquaculture International, 2025)

Characteristics of aqueous film forming foam (AFFF) sites impacted with per- and polyfluoroalkyl substances (PFAS): A 37-site study - Poonam R. Kulkarni; Nicolette E. Andrzejczyk; Arun Gavaskar; Abigail Cartwright; David T. Adamson; John Cook; Charles J. Newell (Water Research, 2025)

Modulatory effects of Glycyrrhiza glabra L. on endocrinological shift in ovariectomy-induced menopausal mice: Network pharmacology guided in-vivo study - Poonam Rawat; Shekhar Singh; Priyanka Kumari Keshri; Hagera Dilnashin; Bhanu Kumar; Ankita Misra; Surya Pratap Singh; Sharad Srivastava (Phytochemistry Letters, 2025)

Integrated in vitro and in vivo antilithiatic efficacy of a synergistic herbal formulation, URO-5 and exploration of in silico guided mechanism of action - Ankita Misra; Mridul kant Chaudhary; Poonam Rawat; Hafizurrahman Khan; Vikas Srivastava; Dhirendra Singh; Saroj Kanta Barik; Sharad Srivastava (Phytochemistry Letters, 2025)

Development of superhydrophobic jute for food grain storage applications - Poonam Chauhan; Aditya Kumar (Food Chemistry, 2025)

Developmental and neurobehavioral toxicity of di-(2-ethylhexyl) phthalate (DEHP) in zebrafish larvae - Garima Jindal; Anuradha Mangla; Poonam Goswami; Mehjbeen Javed; Mohd. Anas Saifi; Iqra Mazahir; Padmshree Mudgal; Basir Ahmad; Sheikh Raisuddin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Evaluating life cycle greenhouse gas emissions from alternative forest residue utilization: Energy and product pathways - Poonam Khatri; Richard Bergman; Prakash Nepal; David Nicholls; Andrew Gray (Biomass and Bioenergy, 2025)

Effect of hydrolysed Trifolium repens L. extract on menopause induced obesity and depressive symptoms: an in-vitro and in-silico approach - Poonam Rawat; Bhanu Kumar; Ankita Misra; Satyendra Pratap Singh; Surya Pratap Singh; Sharad Srivastava (Natural Product Research, 2025)

Photophysical and Optical Properties of β-keto Carboxylate Tb(III) Complexes with Heterocyclic Sensitizers - Shagun Goyat; Vaishnavi Lather; Aarti Khatkar; Pratibha Ahlawat; Poonam Kumari; Bhawna Rathee; Rajesh Kumar (Journal of Fluorescence, 2025)

Combined challenges posed by climate change and pollution to river ecosystems: exploring connecting links, hydro-biological impacts and future research approaches - Ashutosh Tripathi-II; Sarojni Rai; Devendra Kumar Soni; Ashutosh Tripathi-I; Poonam Pandey (Environmental Sustainability, 2025)

Near-infrared spectroscopy coupled with machine learning for soil properties prediction - Kamini G. Panchbhai; Poonam B. Gautam; Madhusudan G. Lanjewar; Lalchand B Patle (International Journal of Remote Sensing, 2025)

Enhanced clonal propagation for elite potato varieties: Implications for growth performance and plant transformation studies - Poonam Patel; Dhara Raval; Chaitanya Joshi; Madhvi Joshi; Amrutlal Patel; Fenil Patel (South African Journal of Botany, 2025)

Molecular engineering and synergistic redox-active hexaazatrinaphthalene and pyrene-based conjugated microporous polymers for superior faradaic supercapacitor energy storage - Mohamed Gamal Mohamed; Bhargabi Halder; Poonam Nagendra Singh; Ahmed A.K. Mohammed; Perumal Elumalai; Shiao-Wei Kuo (Chemical Engineering Journal, 2025)

Influence of additive and maternal genetics on kid survival in Beetal goat - Poonam Sevda; Yogesh C. Bangar; Sunil Kumar; Man Singh; Rakesh Nehra; S. P. Dahiya (Tropical Animal Health and Production, 2025)

Optimising Processing Technologies for Coloured-Skinned Potato Wedges: Analysis of Bioactive Compounds, Structural Integrity, and Sensory Properties - Rajni Saini; Sukhpreet Kaur; Poonam Aggarwal; Satpal Sharma; Atul Dhiman (Potato Research, 2025)

Development and characterization of multi-millet extruded food snack - Tej Bhan Singh; Ravinder Kaushik; Raju Sasikumar; Vivek Kambhampati; Poonam Singha; Sushil Kumar Singh (Cereal Research Communications, 2025)

Sustainable and cost-effective production of bacterial cellulose by using rice straw hydrolysate: a response surface approach - Poonam Sharma; Ritu Sharma; Anita Yadav; Neeraj K. Aggarwal (Brazilian Journal of Microbiology, 2025)

What drives anthropogenic fine particulate chloride emissions in India? – A quantitative assessment of hotspots - Pallavi Sahoo; Ashirbad Mishra; Poonam Mangaraj; Khaiwal Ravindra; Gufran Beig; Bhishma Tyagi; Saroj Kumar Sahu (Science of The Total Environment, 2025)

Machine learning-guided Orbitrap-HRAMS-based metabolomic fingerprinting for geographical origin, variety and tissue specific authentication, and adulteration detection of turmeric and ashwagandha - CH. Ratnasekhar; Abhishek Kumar Rai; Poonam Rakwal; Samreen Khan; Anoop Kumar Verma; Pradipto Mukhopadhyay; Priya Rathor; Lal Hinghrani; Nicholas Birse; Ritu Trivedi; Prabodh Kumar Trivedi (Food Chemistry, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Immunopharmacology of senescence: targeting the senescence-associated secretory phenotype (SASP)—a mechanism-based review - Poonam Sahu; Trilochan Satapathy (Inflammopharmacology, 2025)

Exploring the potential of Moringa oleifera seed extract-loaded microemulsion hydrogel in the DNCB-induced atopic dermatitis model - Prakrati Garg; Aaliya Ali; Sewa Singh; Kanika Thakur; Kaisar Raza; Bigul Yogeshver Bhardwaj; Saurabh Kulshrestha; Poonam Negi (Inflammopharmacology, 2025)

Exploring the Therapeutic Potential of Lipid Nanocarriers in Psoriasis Management: Advances and Applications - Atif Husain; Poonam Kushwaha; Archita Kapoor; Priyanka Singh (AAPS PharmSciTech, 2025)

Exploration of Predictive Potential of AI-enabled Portable System in Anticancer Drug Delivery: A Comparative Study with Modified Gompertz like Biphasic Response Model - Subeel Shah; Kapil Saraswat; Charu Misra; Poonam Negi; Kaisar Raza (AAPS PharmSciTech, 2025)

Optimizing starch-free arabinogalactan-rich taro nanomucilage: Green experimental design, structural elucidation, amino acid profiling, and biological properties - Mansuri M. Tosif; Aarti Bains; Prince Chawla; Surinder Paul; Poonam Kumari; Sanju Bala Dhull; Nemat Ali; Gulden Goksen (Food Chemistry, 2025)

Targeting inflammatory macrophages with tailored bioactive β-glucan conjugated polymeric nanoparticles for the treatment of pancreatitis - Archana Karole; Yirivinti Hayagreeva Dinakar; Poonam Sagar; Shabi Parvez; Ravi Kumar; Shyam Lal Mudavath (Chemical Engineering Journal, 2025)

Identification of IGFBP2 gene polymorphism and association of genotypes with performance traits in Large White Yorkshire pigs - Rohit Solanki; S. S. Dhaka; Poonam Ratwan; Mohit Singh; Manoj Kumar (Tropical Animal Health and Production, 2025)

Molecular docking and molecular dynamics simulation studies of thiazole-coumarin and thiazole-triazole conjugates against Mpro and ACE2 receptor for SARS COV-2 - Deepak Mishra; Ram Singh; Nupur S. Munjal; Naresh Kumar; Prashant Kumar; Poonam; Sandeep Sharma (In Silico Pharmacology, 2025)

Machine learning-assisted Fourier transform infrared spectroscopy to predict adulteration in coriander powder - Rishabh Goyal; Poonam Singha; Sushil Kumar Singh (Food Chemistry, 2025)

Sustainable poultry feed formulations from fruit and vegetable residues for advancing animal health - Ankita Siwach; Sonu Saini; Arup Giri; Poonam Khatri; Ramesh Chander Kuhad; Anil Kumar (Bioresource Technology Reports, 2025)

Promising pancreatic lipase inhibitory activity of a novel tetrapeptide isolated from endophytic Fusarium incarnatum - Mahiti Gupta; Sanjai Saxena; Poonam Bansal; Dinesh Goyal (World Journal of Microbiology and Biotechnology, 2025)

Pharmacological, computational, and mechanistic insights into triptolide’s role in targeting drug-resistant cancers - Md Sadique Hussain; Somdutt Mujwar; M. Arockia Babu; Kavita Goyal; Dinesh Kumar Chellappan; Poonam Negi; Thakur Gurjeet Singh; Haider Ali; Sachin Kumar Singh; Kamal Dua; Gaurav Gupta; Ashok Kumar Balaraman (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Innovating alopecia treatment: nanostructured lipid carriers as advanced delivery platforms - Poonam Kushwaha; Shazia Usmani; Mohd. Sufiyan; Priyanka Singh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Risk resilience of growing settlements in landslide prone hilly areas: case study on Kalimpong-I block, Darjeeling District, West Bengal - Chalantika Laha Salui; Shovan Lal Chattoraj; Ganga Prasad Prasain; Poonam Sharma (Natural Hazards, 2025)

Harnessing the Potential of Sulphur Oxidizing Bacillus with Agrochemicals for Improving Soil Health and Nutrient Acquisition in Brassica Napus L - Vishnu; Poonam Sharma; Jupinder Kaur; Sohan Singh Walia (Journal of Soil Science and Plant Nutrition, 2025)

Advancing bioremediation: biosurfactants as catalysts for sustainable remediation - Yashika Raheja; Poonam Sharma; Prachi Gaur; Vivek Kumar Gaur; Janmejai Kumar Srivastava (Biodegradation, 2025)

Soil Attributes Modulate the Fungal Population and Diversity of Phytopathogens and Biocontrol Agents - Isha Verma; Sumit K. Soni; Rahul Kumar; Bhavya Priyadarshini Mishra; Udit Yadav; Anshu anshu; Touseef Fatima; Sanjeeva Nayaka; Mariya Naseem; Suchi Srivastava; Poonam C. Singh (Agricultural Research, 2025)

Establishment and characterization of patient-derived tongue squamous cell carcinoma cell lines - Priyanka Joshi; Sanjay Bane; Pankaj Chaturvedi; Poonam Gera; Sanjeev K. Waghmare (Human Cell, 2025)
Oral squamous cell carcinoma (OSCC) is a common carcinoma in Indian population, wherein one-third of global OSCC cases are from India. The five-year survival rate is poor due to late diagnosis. Oral tongue squamous cell carcinoma (OTSCC) is the second-most common OSCC. An in vitro cell line model is a valuable tool to get a deeper understanding of the molecular mechanisms involved in therapy resistance and disease progression. We report establishment of three OTSCC cell lines from advanced stage treatment naïve Indian patient samples, such as ACOTSC120, ACOSTC132, and ACOTSC140. All three OTSCC cell lines showed epithelial morphology, which was confirmed by Keratin-14 staining. The cell lines showed in vitro spheroid-forming and in vivo tumorigenic potential. The STR of the cell lines ensured their human origin and novelty when compared to DSMZ cell line database. The karyotype of the cell lines showed aneuploidy and further confirmed their human origin. These cell lines showed the presence of cancer stem cell (CSCs) population, i.e., the ALDH br /CD44 + population. These cell lines thus provide a model to help understand the biology of disease and its progression.

Mechanisms behind the post harvest sprouting of onions (allium cepa) and future implications of prevention strategies - Mahesh Kumar Samota; Shilpa S. Selvan; Poonam Choudhary; Amit Nath; Arvind Ahlawat; Varinda (Journal of Stored Products Research, 2025)

Effect of heat wave on physiological responses, body surface temperature, heat load, and panting behaviour in buffalo heifers - Brijesh Yadav; Poonam Yadav; Arun Kumar Madan; Mukul Anand; Sarvajeet Yadav (Theoretical and Applied Climatology, 2025)

Erasing Methylation Marks on DNA by Plant-Specific DEMETER Family DNA Glycosylases - Praveen Rai; Poonam Kumari; Vineet Gaur (Journal of Plant Growth Regulation, 2025)

Influence of drip irrigation and straw mulching on economic feasibility and soil fertility of rice-potato system in subtropical India - Poonam Biswal; Ahmad Faisal; Suchismita Tripathy; Dillip Kumar Swain; Madan Kumar Jha; Geetha Mohan (Irrigation Science, 2025)

A critical review on Moringa oleifera : current status, physicochemical attributes, and food industrial applications - Poonam Jaglan; Deepika Kaushik; Mukul Kumar; Jyoti Singh; Fatih Oz; Shubham Shubham; Vikas Bansal; Charalampos Proestos; Vishal Kumar; Ritu Rani (Natural Product Research, 2025)

TCE-mediated neuroprotection against rotenone-induced dopaminergic neuronal death in PD mice: insights into the Nrf-2/PINK1/Parkin-mitophagy pathway - Hagera Dilnashin; Shekhar Singh; Poonam Rawat; Aaina Singh Rathore; Richa Singh; Priyanka Kumari Keshri; Nitesh Kumar Gupta; Singh Ankit Satyaprakash; Surya Pratap Singh (Metabolic Brain Disease, 2025)

Decoration of Fe3O4-vitamin C nanoparticles on alginate-chitosan nanocomplex: Characterization, safety, bioacessibility boost and Iron Nanofortification in A2 goat milk gels - Shweta Rathee; Ankur Ojha; Poonam Sagar; Ashutosh Upadhyay; Irfan A. Rather; Shruti Shukla (Food Chemistry, 2025)

Recovery of high-value components from Bauhinia variegata leaves using ultrasound-microwave-assisted extraction technique - Gagan Dip; Poonam Aggarwal; Aakriti Kapoor; Sumit Grover; Sukhpreet Kaur (Biomass and Bioenergy, 2025)

Genetic characterization of Tulip (Tulipa hybrida L.) genotypes under mid hills of Himachal Pradesh - Nepu Rana; Puja Sharma; Sita Ram Dhiman; Bharati Kashyap; Rajesh Kumar Dogra; Anju Sharma; Poonam Sharma (Genetic Resources and Crop Evolution, 2025)

Potential drivers of plant diversity and composition in high-altitude alpine regions of Himalaya - Neha Thapliyal; Puja Bhojak; K. Chandra Sekar; Kapil Bisht; Poonam Mehta; Dhani Arya; Sunil Joshi (Community Ecology, 2025)

In Vitro Eradication of Endophytic Bacteria to Enhance Micropropagation of L49 Guava (Psidium guajava L.) - Poonam Patel; Fenil Patel; Chaitanya Joshi; Madhvi Joshi (Applied Fruit Science, 2025)

Synthesis and Photophysical Characteristics of Samarium-based Complexes for Optoelectronic and Latent Fingerprint Applications - Shagun Goyat; Vaishnavi Lather; Aarti Khatkar; Bhawna Rathee; VB Taxak; SP Khatkar; Pratibha Ahlawat; Poonam Kumari; Vipin Kumar; Rajesh Kumar (Journal of Fluorescence, 2025)

Psiguanol, a novel α-pyrone derivative from Psidium guajava leaves and vasorelaxant activity in rat aorta cells through intracellular cGMP-dependent opening of calcium-activated potassium channels - Shraddha Srivastava; Divya Mishra; Rohit Bisht; Kumari Savita; Kishan Singh; Poonam Rani; Debabrata Chanda; Kapil Dev (Natural Product Research, 2025)

Effects of acoustic waves on the growth, development and phytochemical contents of In Vitro raised Swertia chirayita - Swalpanaa Singh; Poonam Sharma; Hemant Sood; Vikrant Abbot (Next Research, 2025)

Post harvest hot water immersion treatment as sustainable approach for artificial curing of immature dates to reduce wastage - Prabhjot Kaur; Sukhpreet Kaur; Poonam Aggarwal; Anil Kumar (Food Chemistry, 2025)

Investigating the antibiotic resistance genes and mobile genetic elements in water systems impacted with anthropogenic pollutants - Poonam Sharma; Namrata Pal; Manoj Kumawat; Samradhi Singh; Deepanker Das; Anita Tilwari; Anil Prakash; Rajnarayan R. Tiwari; Manoj Kumar (Environmental Research, 2025)

Sustainable valorization of jojoba oilcake: Pressing method-dependent protein stability and functionality for food applications - Nevetha Ravindran; Sushil Kumar Singh; Poonam Singha (Biomass and Bioenergy, 2025)

Sustainable microbial solutions for managing fungal threats in wheat: progress and future directions - Prem Lal Kashyap; Sudheer Kumar; Annie Khanna; Poonam Jasrotia; Gyanendra Singh (World Journal of Microbiology and Biotechnology, 2025)

Foliar application of chlormequat chloride improves lodging resistance and grain yield in bread wheat - Hanif Khan; Om Parkash; H. M. Mamrutha; Rakesh Kumar Bairwa; Chandra Nath Mishra; Raj Kumar; Poonam Jasrotia; Sunil Kumar; Gopalareddy Krishnappa; O. P. Ahlawat; Gyanendra Singh (Plant Physiology Reports, 2025)

Mild Blast Exposure Dysregulates Metabolic Pathways and Correlation Networking as Evident from LC–MS-Based Plasma Profiling - Ruchi Baghel; Kiran Maan; Seema Dhariwal; Megha Kumari; Apoorva Sharma; Kailash Manda; Richa Trivedi; Poonam Rana (Molecular Neurobiology, 2025)

Photo-Physical, Optical and Antimicrobial Properties of Eu(III) Complexes with TPB by Using Different Auxiliary Ligands - Vaishnavi Lather; Aarti khatkhar; Shagun Goyat; Manoj Kumar; Pratibha Ahlawat; Poonam Kumari; Bhawna Rathee; Rajesh Kumar (Journal of Fluorescence, 2025)

Development of Multifunctional C-dots from Processing Waste of Pomelo Fruits for Determination of pH and Methyl Parathion - Priya Darshini M J; A. Sangeeta; Poonam Mishra (Journal of Fluorescence, 2025)

Unlocking the potential of food waste chemistry for biodegradable plastics production: Recent advancements, perspectives, and life-cycle assessment - Vivek Kumar Gaur; Prachi Gaur; Andrei Telegin; Ravindra Singh Thakur; Poonam Sharma; Pallavi Gupta; Kusum Dhakar; Yashika Raheja; Janmejai Kumar Srivastava; Sunita Varjani; Jonathan W.C. Wong; How Yong Ng; et al. (Trends in Food Science & Technology, 2025)

Methyl donor ameliorates CCl4-induced liver fibrosis by inhibiting inflammation, and fibrosis through the downregulation of EGFR and DNMT-1 expression - Manish Bishnolia; Poonam Yadav; Sumeet Kumar Singh; Nirmal Manhar; Sonu Rajput; Amit Khurana; Jasvinder Singh Bhatti; Umashanker Navik (Food and Chemical Toxicology, 2025)

Enhancing melatonin photostability and controlled release using pH-responsive mesoporous silica nanoparticles for agricultural applications - Parul Sangwan; Poonam Barala; Vinita Hooda (Biocatalysis and Agricultural Biotechnology, 2025)

Volume Estimation of Glaciers in Alaknanda Sub-basin - Shivang Alok; Poonam Mishra; D. Ram Rajak; Sushil K. Singh; Naveen Tripathi (Journal of the Indian Society of Remote Sensing, 2025)

Environmental desiccation stress induces viable but non culturable state in Neisseria meningitidis - Poonam Kanojiya; Tiyasa Haldar; Sunil D. Saroj (Archives of Microbiology, 2025)

Optimization of protocol for analysis of dicarboxylic acids in ambient aerosol samples using GC–MS: method comparison and application - Pratibha Vishwakarma; Poonam Nigam; Tarun Gupta (Environmental Monitoring and Assessment, 2025)

An integrated high-rate algal pond ̶ immobilized algal biomat reactor (HRAP ̶ IAB) for rapid phycoremediation and biomass production – A loop and non-retrofit approach - Judah Jacob; Allwin Vinoth Jayakumar; Varshavardhini Moorthy; Poonam Marcella Andrew Louis; Samson Lijoseraj Charles; Jayandan Sellapillai Arunachalam; Muthu Thangavel; Ramasamy Vijayaraghavan; Senthil Chinnasamy; Polur Hanumantha Rao (Journal of Water Process Engineering, 2025)

Clearing the path: Unraveling bisphenol a removal and degradation mechanisms for a cleaner future - Sourav Kundu; Basanta Kumar Das; Abhilash Wodeyar; Poonam Majumder; Susmita Jana; Ayan Biswas; Sagarika Das; Rinku Besra (Journal of Environmental Management, 2025)

Recent advancements in xanthan gum-based gastroretentive floating formulations: Chemical modification, production and applications - Bigul Yogeshver Bhardwaj; Samar Vihal; Rakesh Pahwa; Shweta Agarwal; Bhuvanesh Gupta; Jen Chang Yang; Raveen Chauhan; Dinesh Kumar Chellappan; Gaurav Gupta; Sachin Kumar Singh; Kamal Dua; Poonam Negi (Carbohydrate Polymers, 2025)

Retraction notice to “Microbial strategies for bio-transforming food waste into resources” [Bioresour. Technol. 299 (2020) 122580] - Poonam Sharma; Vivek Kumar Gaur; Sang-Hyoun Kim; Ashok Pandey (Bioresource Technology, 2025)

Extraction and characterization of phytochemicals from Bauhinia variegata flowers using ultrasound and microwave techniques - Gagan Dip; Poonam Aggarwal; Sukhpreet Kaur; Sumit Grover (Biomass and Bioenergy, 2025)

Leveraging nanostructured lipid carriers to enhance targeted delivery and efficacy in breast cancer therapy: a comprehensive review - Nazish Naseem; Poonam Kushwaha; Faheem Haider (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Heat Shock Proteins expression in malaria and dengue vector - Poonam Singh; Shweta Pasi; Veena Pande; Ramesh C. Dhiman (International Journal of Biometeorology, 2025)

Early signals of climate change impacts on alpine plant diversity in Indian Himalaya - K. Chandra Sekar; Neha Thapliyal; Puja Bhojak; Kapil Bisht; Aseesh Pandey; Poonam Mehta; Vikram Singh Negi; Rajendra Singh Rawat (Biodiversity and Conservation, 2025)

Provenance and tectonic settings of sandstones of Jhuran Formation (Kimmeridgian to Tithonian); Mundhan dome, Kachchh, Western India - Poonam R. Mangtani; A. V. Joshi (Journal of Sedimentary Environments, 2024)

Quantification and spatial analysis of gridded (0.1° × 0.1°) emission of indirect GHGs/Air pollutants from anthropogenic sources in India - Saroj Kumar Sahu; Poonam Mangaraj; Pallavi Sahoo; Ashirbad Mishra; Gufran Beig (Environmental Pollution, 2024)

Understanding the Significance of Weather and Soil Microclimate for Improvement of Potato Yield Using SUBSTOR and Statistical Models - Poonam Biswal; Dillip Kumar Swain; Madan Kumar Jha (Potato Research, 2024)

Evolution of Indian Frozen French Fry Industry: Industrial Constraints, Challenges and Future Prospects - Sukhpreet Kaur; Poonam Aggarwal; Navjot Kaur (Potato Research, 2024)

Correction: Exome sequencing identified mutations in the WNT1 and COL1A2 genes in osteogenesis imperfecta cases - Poonam Mehta; Rahul Vishvkarma; Sushil Gupta; Naibedya Chattopadhyay; Singh Rajender (Molecular Biology Reports, 2024)

GALNT14 in association with GDF-15 promotes stemness and drug resistance through β-catenin signalling pathway in breast cancer - Ashita Gadwal; Purvi Purohit; Manoj Khokhar; Jeewan Ram Vishnoi; Puneet Pareek; Ramkaran Choudhary; Poonam Elhence; Mithu Banerjee; Praveen Sharma (Molecular Biology Reports, 2024)

Exome sequencing identified mutations in the WNT1 and COL1A2 genes in osteogenesis imperfecta cases - Poonam Mehta; Rahul Vishvkarma; Sushil Gupta; Naibedya Chattopadhyay; Singh Rajender (Molecular Biology Reports, 2024)

Existing status and future advancements of adulteration detection techniques in herbal products - Munir Ibrahim; Asmita Detroja; Bhavisha P. Sheth; Poonam Bhadja; Gaurav Sanghvi; Ashok Kumar Bishoyi (Molecular Biology Reports, 2024)

Interactions between AT1R and GRKs: the determinants for activation of signaling pathways involved in blood pressure regulation - Poonam; Shashi Chaudhary (Molecular Biology Reports, 2024)

Dengue and chikungunya virus dynamics, identification, and monitoring in wastewater - Tiyasa Haldar; Poonam Katarmal; Bishnudeo Roy; Santosh Koratkar (Environmental Monitoring and Assessment, 2024)

Selective inhibition of T-type calcium channel preserves ischemic pre-conditioning mediated neuroprotection during cerebral ischemia reperfusion injury in diabetic mice - Poonam Sharma; Bhupesh Sharma; Harsha Kharkwal; Shivani Ghildiyal; Vaishali M. Patil (Metabolic Brain Disease, 2024)

Influence of additive and maternal effects on growth traits in Deccani sheep through Bayesian inference - Yogesh B. Kandalkar; Yogesh C. Bangar; Poonam; Rakesh Nehra; Ravindranath G. Nimase (Small Ruminant Research, 2024)

Reporting of gridded ammonia emission and assessment of hotspots across India: A comprehensive study of 24 anthropogenic sources - Pallavi Sahoo; Saroj Kumar Sahu; Poonam Mangaraj; Ashirbad Mishra; Gufran Beig; Sachin S. Gunthe (Journal of Hazardous Materials, 2024)

“Efficient novel fungal-enriched biochar formulation for hexavalent chromium bioremediation” - Priya Dubey; Aditi Roy; Sandhya Mishra; Mariya Naseem; Alvina Farooqui; Anju Patel; Poonam C. Singh; Pankaj Kumar Srivastava (Journal of Environmental Management, 2024)

Promotion of lactose isomerization to fructose and lactulose in one batch by immobilized enzymes on bacterial cellulose membranes - Vasilis Panagopoulos; Ioannis K. Karabagias; Agapi Dima; Konstantina Boura; Maria Kanellaki; Loulouda Bosnea; Poonam Singh Nee Nigam; Athanasios Koutinas (Food Chemistry, 2024)

Exploring Ganoderma lucidum: morphology, cultivation and market potential - Pratibha Thakur; Sonali Khanal; Ashwani Tapwal; Dinesh Kumar; Rachna Verma; Poonam Chauhan; Neha Sharma (World Journal of Microbiology and Biotechnology, 2024)

Bayesian approach for assessment of co-variances and genetic parameters of production and reproduction traits in Sahiwal cattle - Poonam Ratwan; Manoj Kumar; A. K. Chakravarty (Tropical Animal Health and Production, 2024)

Study of Luminescence Phenomena of Tb (III) Containing Fluroquinoline for Application in Optoelectronic Devices - Poonam Kumari; Vaishnavi Lather; Arjun Malik; Pratibha Ahlawat; Rajesh Kumar (Journal of Fluorescence, 2024)

The designing of magnetic nanomaterials synthesis and applications in dye degradation: a review - Surbhi Dhadda; Nidhi Jangir; Poonam Sihag; Surendra K. Bagaria; Dinesh K. Jangid (Environmental Science and Pollution Research, 2024)

Phage therapy: an alternative treatment modality for MDR bacterial infections - Namrata Pal; Poonam Sharma; Manoj Kumawat; Samradhi Singh; Vinod Verma; Rajnarayan R. Tiwari; Devojit Kumar Sarma; Ravinder Nagpal; Manoj Kumar (Infectious Diseases, 2024)

Involvement of Sirt1-FoxO3a-Bnip3 axis and autophagy mediated mitochondrial turnover in according protection to hyperglycemic NRK-52E cells by Berberine - Sugandh Saxena; Sumit Kumar Anand; Ankita Sharma; Poonam Kakkar (Toxicology in Vitro, 2024)

Predicting the patterns of plant species distribution under changing climate in major biogeographic zones of mainland India - Poonam Tripathi; Mukunda Dev Behera; Parth Sarathi Roy (Biodiversity and Conservation, 2024)

Quality, Textural, Bioactive, Molecular and Chromatographic Characterization of Citrus Pseudolimon from Different Geographical Locations in India - Ramandeep Kaur; Vikas Kumar; Poonam Aggarwal; Gurvinder Singh; Satish Kumar (Applied Fruit Science, 2024)

Nanotechnology-driven Microemulsion Based Intranasal Delivery to Neurotechnology-driven Neuralink: Strategies to Improve Management of Neurodegenerative Disorders - Pragya; Shradha Bisht; Poonam Parashar (AAPS PharmSciTech, 2024)

Activating agent-driven hierarchical nano-porous structure in mustard oil–derived carbon soot for supercapacitive application - Ritu Jangra; Poonam Mahendia Bhoria; Manoj Karakoti; Sandeep Pandey; Nanda Gopal Sahoo; Anurag Srivastava; Suman Mahendia (Environmental Science and Pollution Research, 2024)

OsMED14_2, a tail module subunit of Mediator complex, controls rice development and involves jasmonic acid - Ankita Prusty; Poonam Mehra; Shivam Sharma; Naveen Malik; Pinky Agarwal; Swarup Kumar Parida; Sanjay Kapoor; Akhilesh Kumar Tyagi (Plant Science, 2024)

Harnessing microbial potentials by advancing bioremediation of PAHs through molecular insights and genetics - Poonam Sharma; Prachi Gaur; Shreya Dwivedi; Komal Kumari; Janmejai Kumar Srivastava; Kusum Dhakar; Vivek Kumar Gaur; Sunita Varjani; Jo-Shu Chang; Huu Hao Ngo; How Yong Ng; Cheng-Di Dong; et al. (International Biodeterioration & Biodegradation, 2024)

Self-assembled PEGylated micelles for precise and targeted drug delivery: Current challenges and future directions - Surekharani Sinha; Arpan Kumar Tripathi; Ashish Pandey; Poonam Naik; Aakansha Pandey; Vinay Sagar Verma (Biocatalysis and Agricultural Biotechnology, 2024)

Sustainable Soil Management for Climate Resilience: Long-Term Management Effects on Soil Carbon Sequestration and Nitrogen Dynamics in a Semi-Arid Tropical Inceptisol of India - Debashis Dutta; Amrit Lal Meena; Chandra Bhanu; PC Ghasal; Jairam Choudhary; Sunil Kumar; RP Mishra; MA Ansari; Raghavendra KJ; AK Prusty; P. C. Jat; Poonam Kashyap; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Structural and Luminescent Properties of Dy(III) Doped Ca0.5Bi3P2O10 Nanophosphors for Solid-State Lighting & Latent Fingerprinting Applications - Diksha Solanki; Poonam Devi; Hina Dalal; Neeraj Sehrawat; Mukesh Kumar; Surendra Kumar; Rajesh Kumar Malik (Journal of Fluorescence, 2024)

A comprehensive review on the recent trends in extractions, pretreatments and modifications of plant-based proteins - Nevetha Ravindran; Sushil Kumar Singh; Poonam Singha (Food Research International, 2024)

Integrating advanced techniques and machine learning for landfill leachate treatment: Addressing limitations and environmental concerns - Vivek Kumar Gaur; Krishna Gautam; Reena Vishvakarma; Poonam Sharma; Upasana Pandey; Janmejai Kumar Srivastava; Sunita Varjani; Jo-Shu Chang; Huu Hao Ngo; Jonathan W.C. Wong (Environmental Pollution, 2024)

Enterocin LD3 from Enterococcus hirae LD3 Inhibits the Growth of Salmonella enterica subsp. enterica serovar Typhimurium ATCC 13311 in Fruit Juice - Poonam Sheoran; Manoj Kumar Yadav; Indu Kumari; Santosh Kumar Tiwari (Probiotics and Antimicrobial Proteins, 2024)

Downregulation of ATF-4 Attenuates the Endoplasmic Reticulum Stress–Mediated Neuroinflammation and Cognitive Impairment in Experimentally Induced Alzheimer’s Disease Model - Poonam Goswami; Juheb Akhter; Anuradha Mangla; Suramya Suramya; Garima Jindal; Shahzad Ahmad; Sheikh Raisuddin (Molecular Neurobiology, 2024)

Upgradation and valorization of hydrothermally liquified wastewater algae to recover multiple products - Farah Naaz; Sumit Dhali; Saptarshi Dey; Arghya Bhattacharya; Poonam Choudhary; Kamal Kishore Pant; Anushree Malik (Algal Research, 2024)

Wastewater surveillance of severe acute respiratory syndrome coronavirus-2 in open drains of two Indian megacities captures evolutionary lineage transitions: a zonation approach - Saee Zambre; Poonam Katarmal; Shubhankar Pawar; Snehal Dawkhar; Parvati Iyer; Vinay Rajput; Pradnya Kadam; Unnati Bhalerao; Manisha Tupekar; Priyanki Shah; Krishanpal Karmodiya; Mahesh Dharne; et al. (Environmental Science and Pollution Research, 2024)

Gallic acid derived diarylpropanones exhibit synergistic antibacterial activities - Sneha Singh; Sana Khan; Alka Kurmi; Ranjana Das; Barsha Thapa; Poonam Rani; Feroz Khan; Dharmendra Saikia; Debabrata Chanda; Arvind Singh Negi (Medicinal Chemistry Research, 2024)

Recent Trends in Biologically Synthesized Metal Nanoparticles and their Biomedical Applications: a Review - Laxmi Devi; Poonam Kushwaha; Tarique Mahmood Ansari; Ashish Kumar; Amit Rao (Biological Trace Element Research, 2024)

Preparation and Judd-Ofelt Analysis of Warm Red Luminescent Eu3+ Complexes for Semiconductor Lasing Devices - Manoj Kumar; Pratibha Ahlawat; Poonam Kumari; Vaishnavi Lather; Aarti Khatkar; Harkesh Sehrawat; Rajesh Kumar (Journal of Fluorescence, 2024)

Panicle compactness along with abiotic factors influence the abundance of earhead feeding insect pests of sorghum [Sorghum bicolor (L.) Moench] - Rahul Saini; Dalip Kumar; Jyotsana Chauhan; Poonam Jasrotia (International Journal of Tropical Insect Science, 2024)

Scaffold-Mediated Drug Delivery for Enhanced Wound Healing: A Review - Mohd Sufiyan; Poonam Kushwaha; Mohammad Ahmad; Purba Mandal; Km Khushbo Vishwakarma (AAPS PharmSciTech, 2024)

Advancements in sustainable food packaging: A comprehensive review on utilization of nanomaterials, machine learning and deep learning - Pratik Madhukar Gorde; Dibya Ranjan Dash; Sushil Kumar Singh; Poonam Singha (Sustainable Chemistry and Pharmacy, 2024)

Bio-based composite active film/coating from deccan hemp seed protein, taro starch and leaf extract: Characterizations and application in grapes - Dibya Ranjan Dash; Sushil Kumar Singh; Poonam Singha (Sustainable Chemistry and Pharmacy, 2024)

Insecticidal paint: An alternate integrated vector management strategy for mosquito control - Bharat Singh; Dinesh Kumar; Gaurav Kumar; Poonam Saroha; Kumar Vikram; Sanjeev Kumar Gupta; Himmat Singh (Process Safety and Environmental Protection, 2024)

Targeting OsNIP3;1 via CRISPR/Cas9: A strategy for minimizing arsenic accumulation and boosting rice resilience - Puja Singh; Amit Kumar; Twinkle Singh; Sonik Anto; Yuvraj Indoliya; Poonam Tiwari; Soumit Kumar Behera; Debasis Chakrabarty (Journal of Hazardous Materials, 2024)

Air pollution and serious bleeding events in high-risk older adults - Rindala Fayyad; Kevin Josey; Poonam Gandhi; Melanie Rua; Aayush Visaria; Benjamin Bates; Soko Setoguchi; Rachel C. Nethery (Environmental Research, 2024)

Development of Microalgae-Bacteria Consortium for the Treatment of Domestic Waste Water - Shiwani Guleria Sharma; Poonam Singla; Gurwinder Singh Kocher (Water, Air, & Soil Pollution, 2024)

Lipase domain effector AGLIP1 in Rhizoctonia solani triggers necrotic killing in plants - Parvesh Kumar; Poonam Kumari (Plant Cell Reports, 2024)

Exploring the potential of Moringa oleifera Lam in skin disorders and cosmetics: nutritional analysis, phytochemistry, geographical distribution, ethnomedicinal uses, dermatological studies and cosmetic formulations - Prakrati Garg; Swati Pundir; Aaliya Ali; Sebika Panja; Dinesh Kumar Chellappan; Kamal Dua; Saurabh Kulshrestha; Poonam Negi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Facies analysis and depositional environment of siliciclastic sediments of Mundhan dome, Northwestern Kachchh, Western India - Poonam R. Mangtani; A. V. Joshi (Journal of Sedimentary Environments, 2024)

Harnessing the combined effect of antivirulence agent trans-chalcone with bactericidal curcumin against sortase A enzyme to tackle Gram-positive bacterial infections - Poonam Kumari; Sanjay K. Banerjee; Upadhyayula Surayanarayana Murty; Velayutham Ravichandiran; Utpal Mohan (Folia Microbiologica, 2024)

Sedimentological evidence of climate-tectonic interaction in the upper Satluj catchment of NW Himalaya - Moulishree Joshi; Poonam Jalal (Journal of Mountain Science, 2024)

First report of Alternaria tenuissima causing leaf black spot on Aloe barbadensis in India - Kajal Singh; Poonam Kumari; Rahul Kumar Gupta; Anil Kumar Gupta; Akanksha Singh (Journal of Plant Pathology, 2024)

U–Pb zircon geochronology of the Proterozoic siliciclastic stratal succession of the Kumaun Lesser Himalaya: Implications for regional stratigraphic correlation - Poonam Jalal; Sumit K Ghosh; Mohit Puniya; Gajender Kumar (Journal of Earth System Science, 2024)

Analysis of energy balance and its role in melting over Gangotri and Saraswati glaciated region from 2001–2022 - Shivang Alok; Poonam Mishra; D Ram Rajak; Sushil K Singh (Journal of Earth System Science, 2024)

Comparative Interpretation of Structural, Functional, Phytochemical and Pasting Profile of Coloured Variety Potato Flakes Prepared Using Different Drying Techniques - Rajni Saini; Sukhpreet Kaur; Poonam Aggarwal; Atul Dhiman; Sumit Grover (Potato Research, 2024)

Green Synthesis of Highly Fluorescent NCQDs: A Comprehensive Study on Synthesis, Characterization, Photophysical Properties, pH Sensing, Heavy Metal Detection, and Solvatochromic Behavior through Hydrothermal Method - Poonam Negi; Bhupendra Singh Rawat; Naveen Chandra Joshi; Kanak Pal Singh Parmar; Shuchi Upadhyay; Narinder Kumar; Vinod Singh (Journal of Fluorescence, 2024)

Development of emission inventory for air quality assessment and mitigation strategies over most populous Indian megacity, Mumbai - Poonam Mangaraj; Saroj Kumar Sahu; Gufran Beig (Urban Climate, 2024)

Exploring the influence of ground-dwelling ant bioturbation activity on physico-chemical, biological properties and heavy metal pollution in coal mine spoil - Shbbir R. Khan; Poonam C. Singh; Martin Schmettow; Satish K. Singh; Neelkamal Rastogi (Pedobiologia, 2024)

Quantification and assessment of hazardous mercury emission from industrial process and other unattended sectors in India: A step towards mitigation - Saroj Kumar Sahu; Madhusmita Mishra; Ashirbad Mishra; Poonam Mangaraj; Gufran Beig (Journal of Hazardous Materials, 2024)

Crystal Phase Refinement and Optical Features of Highly Efficient Green Light Radiating Ca9Y(VO4)7: Er3+ Nanophosphors for Emerging Solid-state Lighting Applications - Poonam Devi; Priyanka Sehrawat; Hina Dalal; Monika Sheoran; Neelam Kumari; Rajesh Kumar Malik (Journal of Fluorescence, 2024)

Investigating the potential of dimensional sandstone waste used as a 50% replacement to sand in mortar for masonry - Poonam I. Modi; Rajul K. Gajjar; Anil Kumar Sharma (Innovative Infrastructure Solutions, 2024)

Recent advances on the impact of novel non-thermal technologies on structure and functionality of plant proteins: A comprehensive review - Dibya Ranjan Dash; Sushil Kumar Singh; Poonam Singha (Critical Reviews in Food Science and Nutrition, 2024)

Spectroscopic food adulteration detection using machine learning: Current challenges and future prospects - Rishabh Goyal; Poonam Singha; Sushil Kumar Singh (Trends in Food Science & Technology, 2024)

Autoclave-Assisted Steam Blanching of Sugarcane Bites: Effect on Enzymatic Activity, Color Values, Phytochemical Profile, and Organoleptic Quality - Parinitha A; Navjot Kaur; Poonam Aggarwal; Sukhpreet Kaur (Sugar Tech, 2024)

Proteomic profiling of Arabidopsis G-protein β subunit AGB1 mutant under salt stress - Poonam Yadav; Nisha Khatri; Ravi Gupta; Yashwanti Mudgil (Physiology and Molecular Biology of Plants, 2024)

Satellite or ground-based measurements for air pollutants (PM2.5, PM10, SO2, NO2, O3) data and their health hazards: which is most accurate and why? - Zainab Mushtaq; Pargin Bangotra; Alok Sagar Gautam; Manish Sharma; Suman; Sneha Gautam; Karan Singh; Yogesh Kumar; Poonam Jain (Environmental Monitoring and Assessment, 2024)

Rapid Decline of SARS-CoV-2 Viral Load in Single vs. Double-Dose (Short-Interval <6 Weeks) ChAdOx nCoV-19 Vaccinated Health-Care Workers - Arnab Ghosh; Poonam Kanta; Manisha Ramola; Ritin Mohindra; Kapil Goyal; Roop Kishore; Vikas Suri; P. V. M. Lakshmi; Chanderkanta Chauhan; Manisha Sharma; Partha Rakshit; Kalaiarasan Ponnusamy; et al. (Current Microbiology, 2024)

Circulating miRNA-21 Levels in Breast Cancer Patients Before and After Chemotherapy and Its Association with Clinical Improvement - Sanchi Sukhija; Purvi Purohit; Puneet Pareek; Pawan Kumar Garg; Jeewan Ram Vishnoi; Poonam Abhay Elhence; Shobhan Babu Varthya; Praveen Sharma; Sneha Ambwani; Jaykaran Charan (Indian Journal of Clinical Biochemistry, 2024)

Potential health risks assessment associated with arsenic-contaminated groundwater in the eastern district of Uttar Pradesh, India: a case study - Devendra Kumar Soni; Pradeep Kumar Mishra; Poonam Pandey (Environmental Sustainability, 2024)

Paleoecological and paleobiogeographic implications of a seagrass-indicating foralgal skeletal assemblage: Retracing the Burdigalian Quilon Limestone (Kerala Basin, SW India) - Suman Sarkar; Yogesh Pal Singh; Poonam Verma (Marine Micropaleontology, 2024)

Sustainable water management in rice cultivation reduces arsenic contamination, increases productivity, microbial molecular response, and profitability - Arnab Majumdar; Munish Kumar Upadhyay; Biswajit Giri; Poonam Yadav; Debojyoti Moulick; Sukamal Sarkar; Barun Kumar Thakur; Kashinath Sahu; Ashish Kumar Srivastava; Martin Buck; Mark Tibbett; Manoj Kumar Jaiswal; et al. (Journal of Hazardous Materials, 2024)

Biodiversity and Bioactive Potential of Actinomycetes from Unexplored High Altitude Regions of Kargil, India - Mohd Murtaza; Vidushi Abrol; Ekta Nehra; Poonam Choudhary; Shashank K. Singh; Sundeep Jaglan (Indian Journal of Microbiology, 2024)

Cow urine mediated biogenically generated FeNP to boost antimycotic activity against leaf spot pathogen - Sushma Sharma; Nahla A. Bouqellah; Tanvir Kaur; Poonam Kumari; Sunita Chandel; Magda M. Mehanni; Abd El-Latif Hesham (European Journal of Plant Pathology, 2024)

Antibiotic disposal challenges in India: investigating causes and effects - Samradhi Singh; Poonam Sharma; Namrata Pal; Devojit Kumar Sarma; Manoj Kumar (Environmental Monitoring and Assessment, 2024)

Utilizing soil metabolomics to investigate the untapped metabolic potential of soil microbial communities and their role in driving soil ecosystem processes: A review - Sudeshna Bhattacharjya; Avijit Ghosh; Asha Sahu; Richa Agnihotri; Namrata Pal; Poonam Sharma; M.C. Manna; M.P. Sharma; A.B. Singh (Applied Soil Ecology, 2024)

Altered DTI scalars in the hippocampus are associated with morphological and structural changes after traumatic brain injury - Palkin Arora; Richa Trivedi; Megha Kumari; Kavita Singh; Rajat Sandhir; Maria M. D’Souza; Poonam Rana (Brain Structure and Function, 2024)

Nutritional characterization of an underutilized legume Entada rheedii Spreng. seeds and validation of its folklore uses - Poonam Rawat; Bhanu Kumar; Ankita Misra; Satyendra Pratap Singh; Sharad Srivastava (Natural Product Research, 2024)

Co-existence of halo-tolerant Pseudomonas fluorescens and Enterococcus hirae with multifunctional growth promoting traits to ameliorate salinity stress in Vigna radiata - Kailash Chand Kumawat; Poonam Sharma; Asmita Sirari; Barkha Sharma; Gayatri Kumawat; R.M. Nair; Bindumadhava H; Kunal (Chemosphere, 2024)

Bridge-building practices for holistic vision of agrarian-rural societies in India and Spain - Poonam Pandey; Sebastian Iturriaga Gazol; Mario Pansera (Journal of Rural Studies, 2024)

Endophytic biofungicide Bacillus subtilis (NBRI-W9) reshapes the metabolic homeostasis disrupted by the chemical fungicide, propiconazole in tomato plants to provide sustainable immunity against non-target bacterial pathogens - Udit Yadav; Vandana Anand; Sanjeev Kumar; Suchi Srivastava; Shashank K. Mishra; Puneet Singh Chauhan; Poonam C. Singh (Environmental Pollution, 2024)

Rice-based integrated farming system improves the soil quality, bacterial community structure and system productivity under sub-humid tropical condition - Prafulla Kumar Nayak; A. K. Nayak; B. B. Panda; A. Senapati; P. Panneerselvam; A. Kumar; R. Tripathi; A. Poonam; M. Shahid; S. D. Mohapatra; Megha Kaviraj; Upendra Kumar (Environmental Geochemistry and Health, 2024)

Corrigendum to ‘California's harvested wood products: A time-dependent assessment of life cycle greenhouse gas emissions’ [Sci. Total Environ. 886 (2023) 163918] - Poonam Khatri; Prakash Nepal; Kamalakanta Sahoo; Richard Bergman; David Nicholls; Andrew Gray (Science of The Total Environment, 2024)

Adaptive evolution of Sphingopyxis sp. MC4 conferred degradation potential for persistent β- and δ-Hexachlorocyclohexane (HCH) isomers - Monika Sharma; Durgesh Narain Singh; Gunjan Uttam; Poonam Sharma; Shivam A. Meena; Akhilesh K. Verma; Ram Krishan Negi (Journal of Hazardous Materials, 2024)

In-situ hydrogen production and battery electrode materials from metal effluent and biomass - Pankaj Kumar; Sivamohan N. Reddy; Abhishek Dharmesh; Poonam Rani; Ashwini Kumar Sharma (Chemical Engineering Journal, 2024)

Hybrid electrolyte with biomass-derived carbon host for high-performance aqueous Zn–S battery - Dinesh Patel; Abhishek Dharmesh; Yash Sharma; Poonam Rani; Ashwini Kumar Sharma (Chemical Engineering Journal, 2024)

Crystal Chemistry and Photoluminescent Aspects of Bright Orange Light Emitting Sm3+- Activated Ba2BiV3O11 Nanomaterials for Advanced Illuminating Applications - Poonam Devi; Priyanka Sehrawat; Monika Sheoran; Hina Dalal; Neeraj Sehrawat; Rajesh Kumar Malik (Journal of Fluorescence, 2024)

Development of Bambusa tulda-reinforced different biopolymer matrix green composites and MCDM-based sustainable material selection for automobile applications - Abir Saha; Nikhil Dilip Kulkarni; Poonam Kumari (Environment, Development and Sustainability, 2023)

A systematic review on MICP technique for developing sustainability in concrete - Santosh Ashok Kadapure; Umesh B. Deshannavar; Basavaraj G. Katageri; Poonam S. Kadapure (European Journal of Environmental and Civil Engineering, 2023)

Nitrate contamination in groundwater and preferred treatment technology in rural India - Ravindra Sewak; Poonam Sewak; Pooja Sarvotham Singh (Water Security, 2023)

Application of green technologies for the extraction of phytocompounds from C. pseudolimon residues; an approach for biological characterization - Ramandeep Kaur; Vikas Kumar; Poonam Aggarwal; Gurvinder Singh (Sustainable Chemistry and Pharmacy, 2023)

Life cycle greenhouse gas emissions from five contrasting rice production systems in the tropics - Pradeep K. DASH; Pratap BHATTACHARYYA; Soumya R. PADHY; Amaresh K. NAYAK; Annie POONAM; Sangita MOHANTY (Pedosphere, 2023)

Exploring bioactive compounds and antioxidant properties of twenty-six Indian medicinal plant extracts: A correlative analysis for potential therapeutic insights - Sachin Kumar; Nutan Chauhan; Bhawna Tyagi; Poonam Yadav; Ashis Kumar Samanta; Amrish Kumar Tyagi (Food and Humanity, 2023)

AI based system for creating freezing protocols for cell cryopreservation - Poonam Panwar (Cryobiology, 2023)

Storage Stability Evaluation of Liquid Jaggery Incorporated Pumpkin Toffee Under Different Packaging Conditions - Gagandeep Kaur; Sukhpreet Kaur; Poonam Aggarwal; Navjot Kaur (Sugar Tech, 2023)

Evaluating Progress of Indian Potato Processing Industry: an Updated Review - Sukhpreet Kaur; Poonam Aggarwal; Neha Babbar (Potato Research, 2023)

Spent coffee ground: transformation from environmental burden into valuable bioactive metabolites - Tanim Arpit Singh; Namrata Pal; Poonam Sharma; Ajit Kumar Passari (Reviews in Environmental Science and Bio/Technology, 2023)
Spent coffee ground (SCG) is a primary by-product obtained during soluble coffee processing and could be used for high-value products due to its protein content. The SCG is a rich source of cellulose, hemicellulose, lignin, lipids and proteins. The bioactive peptide obtained after protein hydrolysis has great potential as an antioxidant, antimicrobial, and anti-mutagenic agent and a better understanding is a prerequisite for proper utilization of the natural and renewable source of protein to attain a sustainable approach. Moreover, by utilizing SCG-derived peptides we can reduce the contamination of these residues at an agronomical scale. In this review, we discussed the spent coffee ground protein-based peptides and also high-lightened the properties of these valuable bioactive peptides in addition to other industrially important metabolites. Conclusively, the SCG peptides can be an interesting substitute to plant protein with functional properties in food industries, and at the same time utilization of SCG would reduce the bio-waste burden. Graphical abstract

Recent application of protein hydrolysates in food texture modification - Niveditha Asaithambi; Poonam Singha; Sushil Kumar Singh (Critical Reviews in Food Science and Nutrition, 2023)

New Highly Luminescent Red Emitting Complexes: Synthesis, Characterization, Judd-Ofelt Intensity Parameters and Pharmacological Investigations - Manoj Kumar; Vaishnavi Lather; Poonam Nandal; Pratibha Ahlawat; Poonam kumari; Aarti Khatkar; S. P. Khatkar; V. B. Taxak; Rajesh Kumar (Journal of Fluorescence, 2023)

Impact of emerging non-thermal processing treatments on major food macromolecules: Starch, protein, and lipid - Hadis Rostamabadi; Małgorzata Nowacka; Rosana Colussi; Sabrina Feksa Frasson; Ilkem Demirkesen; Behic Mert; Poonam Singha; Sushil Kumar Singh; Seid Reza Falsafi (Trends in Food Science & Technology, 2023)

Conventional and emerging innovative processing technologies for quality processing of potato and potato-based products: A review - Rajni Saini; Sukhpreet Kaur; Poonam Aggarwal; Atul Dhiman; Priyanka Suthar (Food Control, 2023)

Exploring genetic diversity and ascertaining genetic loci associated with important fruit quality traits in apple (Malus × domestica Borkh.) - Poonam; Rajnish Sharma; Parul Sharma; Naveen C. Sharma; Kuldeep Kumar; Krishna Nand Singh; Vinay Bhardwaj; Narender Negi; Neena Chauhan (Physiology and Molecular Biology of Plants, 2023)

Multidimensional outlook on the pathophysiology of cervical cancer invasion and metastasis - Neena George; Poonam Bhandari; Padival Shruptha; Pradyumna Jayaram; Sima Chaudhari; Kapaettu Satyamoorthy (Molecular and Cellular Biochemistry, 2023)
Cervical cancer being one of the primary causes of high mortality rates among women is an area of concern, especially with ineffective treatment strategies. Extensive studies are carried out to understand various aspects of cervical cancer initiation, development and progression; however, invasive cervical squamous cell carcinoma has poor outcomes. Moreover, the advanced stages of cervical cancer may involve lymphatic circulation with a high risk of tumor recurrence at distant metastatic sites. Dysregulation of the cervical microbiome by human papillomavirus (HPV) together with immune response modulation and the occurrence of novel mutations that trigger genomic instability causes malignant transformation at the cervix. In this review, we focus on the major risk factors as well as the functionally altered signaling pathways promoting the transformation of cervical intraepithelial neoplasia into invasive squamous cell carcinoma. We further elucidate genetic and epigenetic variations to highlight the complexity of causal factors of cervical cancer as well as the metastatic potential due to the changes in immune response, epigenetic regulation, DNA repair capacity, and cell cycle progression. Our bioinformatics analysis on metastatic and non-metastatic cervical cancer datasets identified various significantly and differentially expressed genes as well as the downregulation of potential tumor suppressor microRNA miR-28-5p. Thus, a comprehensive understanding of the genomic landscape in invasive and metastatic cervical cancer will help in stratifying the patient groups and designing potential therapeutic strategies.

Phytoliths analysis in root, culm, leaf and synflorescence of Rostraria cristata (Poaceae) - Poonam Chowdhary; Priya Badgal; Mudassir Ahmad Bhat; Sheikh Abdul Shakoor; Bilal Ahmad Mir; Amarjit Singh Soodan (Journal of Plant Research, 2023)

Investigation of bamboo-based vertical axis wind turbine blade under static loading - Mridusmita Bora; Akash Vasudeo Sharma; Poonam Kumari; Niranjan Sahoo (Ocean Engineering, 2023)

High rainfall afforded resilience to tropical rainforests during Early Eocene Climatic Optimum - Gaurav Srivastava; Harshita Bhatia; Poonam Verma; Yogesh Pal Singh; Torsten Utescher; Rakesh C. Mehrotra (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Integrating microalgae into textile wastewater treatment processes: Advancements and opportunities - Vandana Mishra; Nikhil Mudgal; Deepak Rawat; Pankaj Poria; Paromita Mukherjee; Udita Sharma; Poonam Kumria; Balaram Pani; Mrinalini Singh; Archana Yadav; Furqan Farooqi; Radhey Shyam Sharma (Journal of Water Process Engineering, 2023)

Current and emerging applications in detection and removal of bitter compounds in citrus fruit juice: A critical review - Arun Kumar Gupta; Subhamoy Dhua; Pratiksha; Vijay Kumar; Bindu Naik; Lembe Samukelo Magwaza; Khayelihle Ncama; Umezuruike Linus Opara; David Julian McClements; Poonam Mishra (Food Bioscience, 2023)

Turning up the volume: How root branching adaptive responses aid water foraging - Poonam Mehra; Rebecca Fairburn; Nicola Leftley; Jason Banda; Malcolm J. Bennett (Current Opinion in Plant Biology, 2023)

Utilization of pulp and paper industrial wastewater for production of polyhydroxybutyrate by Bacillus sonorensis NAM5 - Mahak Mittal; Anish Bhuwal; Poonam Sharma; Neeraj K. Aggarwal (Systems Microbiology and Biomanufacturing, 2023)

Satellite Epidemic of Covid-19 Associated Mucormycosis in India: A Multi-Site Observational Study - Aanchal Satija; Tanu Anand; Aparna Mukherjee; Poonam Sharma Velamuri; Kh. Jitenkumar Singh; Madhuchhanda Das; Kripa Josten; Archana Y. Keche; Nitin M. Nagarkar; Prashant Gupta; D. Himanshu; Sejal N. Mistry; et al. (Mycopathologia, 2023)

Variability and association studies among carnation mutants (Dianthus caryophyllus L.) in Northwestern Himalayas - Poonam Sharma; Puja Sharma; Sita Ram Dhiman; Rajesh Kumar Dogra; Anju Sharma; Nepu Rana (Genetic Resources and Crop Evolution, 2023)

New Insights into the Applications of 3D-Printed Biomaterial in Wound Healing and Prosthesis - Aayushi Pandey; Pragya; Jovita Kanoujia; Poonam Parashar (AAPS PharmSciTech, 2023)

Buffalo sperm membrane glycan-binding proteins reveal precise and preferential binding signatures with specific glycans targets on oviduct epithelium and zona pellucida-an implication in fertilization - Poonam Kashyap; Subhash Solanki; Tirtha Kumar Datta; Rakesh Kumar (Theriogenology, 2023)

In-situ formed aryl acid-triggered intramolecular dehydrative cyclization whilst supported Pd-catalyzed carbonylative synthesis of 2-aryl benzimidazoles - Ajay Kumar Sharma; Poonam Sharma; Pushkar Mehara; Pralay Das (Chemical Engineering Journal, 2023)

Advances in therapeutic applications of silver nanoparticles - Ashutosh Kaushal; Isha Khurana; Poonam Yadav; Prince Allawadhi; Anil Kumar Banothu; Dinesh Neeradi; Sunitha Thalugula; Percy Jasmine Barani; Ramavath Redya Naik; Umashanker Navik; Kala Kumar Bharani; Amit Khurana (Chemico-Biological Interactions, 2023)

Development of an Agrobacterium-delivered codon-optimized CRISPR/Cas9 system for chickpea genome editing - Santosh Kumar Gupta; Niraj Kumar Vishwakarma; Paheli Malakar; Poonam Vanspati; Nilesh Kumar Sharma; Debasis Chattopadhyay (Protoplasma, 2023)

Integrated Application of Trichoderma and Carbendazim Affects the Carbendazim Extractability and Microbial Functions in the Maize Rhizosphere - Soni Chauhan; Touseef Fatima; Amita Dubey; Puneet Singh Chauhan; Om Prakash; Poonam C. Singh (Journal of Soil Science and Plant Nutrition, 2023)

Exploration of Optical and Radiative Properties of Fluorinated β-keto Carboxylate Tb3+ Complexes Emanating Cool Green Light - Savita Khatri; Deepanita Khatri; Vaishnavi Lather; Yudhvir Singh; Poonam Kumari; S. P. Khatkar; V. B. Taxak; Rajesh Kumar (Journal of Fluorescence, 2023)

Retraction Note: A facile approach for fabricating CD44-targeted delivery of hyaluronic acid-functionalized PCL nanoparticles in urethane-induced lung cancer: Bcl-2, MMP-9, caspase-9, and BAX as potential markers - Poonam Parashar; Chandra Bhushan Tripathi; Malti Arya; Jovita Kanoujia; Mahendra Singh; Abhishek Yadav; Shubhini A. Saraf (Drug Delivery and Translational Research, 2023)

The development of a solid lipid nanoparticle (SLN)-based lacticin 3147 hydrogel for the treatment of wound infections - Aoibhín Ryan; Pratikkumar Patel; Poonam Ratrey; Paula M. O’Connor; Julie O’Sullivan; R. Paul Ross; Colin Hill; Sarah P. Hudson (Drug Delivery and Translational Research, 2023)
Chronic wounds affect millions of people globally. This number is set to rise with the increasing incidence of antimicrobial-resistant bacterial infections, such as methicillin-resistant Staphylococcus aureus (MRSA), which impair the healing of chronic wounds. Lacticin 3147 is a two-peptide chain bacteriocin produced by Lactococcus lactis that is active against S. aureus including MRSA strains. Previously, poor physicochemical properties of the peptides were overcome by the encapsulation of lacticin 3147 into solid lipid nanoparticles. Here, a lacticin 3147 solid lipid nanoparticle gel is proposed as a topical treatment for S. aureus and MRSA wound infections. Initially, lacticin 3147’s antimicrobial activity against S. aureus was determined before encapsulation into solid lipid nanoparticles. An optimised gel formulation with the desired physicochemical properties for topical application was developed, and the lacticin-loaded solid lipid nanoparticles and free lacticin 3147 aqueous solution were incorporated into separate gels. The release of lacticin 3147 from both the solid lipid nanoparticle and free lacticin gels was measured where the solid lipid nanoparticle gel exhibited increased activity for a longer period (11 days) compared to the free lacticin gel (9 days). Both gels displayed potent activity ex vivo against S. aureus- infected pig skin with significant bacterial eradication (> 75%) after 1 h. Thus, a long-acting potent lacticin 3147 solid lipid nanoparticle gel with the required physicochemical properties for topical delivery of lacticin 3147 to the skin for the potential treatment of S. aureus -infected chronic wounds was developed. Graphical abstract

Carbendazim Modulates the Metabolically Active Bacterial Populations in Soil and Rhizosphere - Soni Chauhan; Udit Yadav; Nasreen Bano; Sanjeev Kumar; Touseef Fatima; Anshu; Amita Dubey; Poonam C. Singh (Current Microbiology, 2023)

Development and evaluation of hydrogel formulation comprising essential oil of Mentha longifolia L. for oral candidiasis - Prakriti Nidhi; Kamal Dev; Poonam Negi; Anuradha Sourirajan (Advances in Traditional Medicine, 2023)

Phytolith profiles of Lolium perenne L. from the Kashmir Himalayas - Poonam Chowdhary; Mudassir Ahmad Bhat; Priya Badgal; Sheikh Abdul Shakoor; Bilal Ahmad Mir; Amarjit Singh Soodan (Brazilian Journal of Botany, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

California's harvested wood products: A time-dependent assessment of life cycle greenhouse gas emissions - Poonam Khatri; Prakash Nepal; Kamalakanta Sahoo; Richard Bergman; David Nicholls; Andrew Gray (Science of The Total Environment, 2023)

Starch modification through its combination with other molecules: Gums, mucilages, polyphenols and salts - Hadis Rostamabadi; Dagmara Bajer; Ilkem Demirkesen; Yogesh Kumar; Chunyan Su; Yong Wang; Małgorzata Nowacka; Poonam Singha; Seid Reza Falsafi (Carbohydrate Polymers, 2023)

Development and evaluation of Resveratrol-loaded liposomes in hydrogel-based wound dressing for diabetic foot ulcer - Supriya Pandey; Arshiya Shamim; Mohammad Shaif; Poonam Kushwaha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

How effective are ionization state-based QSPKR models at predicting pharmacokinetic parameters in humans? - Anish Gomatam; Blessy Joseph; Poonam Advani; Mushtaque Shaikh; Krishna Iyer; Evans Coutinho (Molecular Diversity, 2023)

A SNP-based linkage mapping revealed a mutant-origin major quantitative trait locus for seed size in A05 chromosome of groundnut (Arachis hypogaea L.) - Poonam G. Bhad; Suvendu Mondal; Anand M. Badigannavar (Euphytica, 2023)

Effect of respiratory tract co-colonizers on initial attachment of Neisseria meningitidis - Poonam Kanojiya; Sunil D. Saroj (Archives of Microbiology, 2023)

Sulphonated poly(ethersulfone)/carbon nano-onions-based nanocomposite membranes with high ion-conducting channels for salt removal via electrodialysis - Poonam Kumari; Prashant Upadhyay; Kumud Malika Tripathi; Ragini Gupta; Vaibhav Kulshrestha; Kamlendra Awasthi (Environmental Science and Pollution Research, 2023)

Natural resources as cancer-treating material - Poonam Kaswan (South African Journal of Botany, 2023)

Light-dependent biohydrogen production: Progress and perspectives - G. Suresh; Poonam Kumari; S. Venkata Mohan (Bioresource Technology, 2023)

Role of aerosol liquid water content on the production of dicarboxylic acids in the dust-laden air masses over the Arabian Sea: Implications for heterogeneous chemistry - Poonam Bikkina; Srinivas Bikkina; Kimitaka Kawamura (Atmospheric Research, 2023)

Ethanol from cellulose and cellobiose of woody-substrates in a single stage of 3-combined-bioprocesses employing a non-GM yeast cell-factory - Iris Plioni; Archontoula Kalogeropoulou; Dimitra Dimitrellou; Panagiotis Kandylis; Poonam Singh Nigam; Maria Kanellaki; Athanasios A. Koutinas (Biocatalysis and Agricultural Biotechnology, 2023)

Marker trait association for biological nitrogen fixation traits in an interspecific cross of chickpea (Cicer arietinum × Cicer reticulatum) - Sharon Nagpal; Asmita Sirari; Poonam Sharma; Satinder Singh; Kamalpreet Singh Mandahal; Harpreet Singh; Sarvjeet Singh (Physiology and Molecular Biology of Plants, 2023)

Chronology and paleoclimatic implications of the upper Ganga catchment floods since Marine Isotopic Stage-2 - Neha Chauhan; Yaspal Sundriyal; Sameeksha Kaushik; Poonam Chahal; D.K. Panda; D. Banerjee; Ambili Narayanan; A.D. Shukla (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Carbohydrate nanotubes production and its techno-economic validation - Athanasia Panitsa; Theano Petsi; Eleana Kordouli; Poonam Singh Nigam; Maria Kanellaki; Athanasios A. Koutinas (Bioresource Technology Reports, 2023)

Assessment of multidrug-resistant profile, multi-locus sequence typing and efflux pump activity in Salmonella Typhimurium isolated from hospital sewage - Manoj Kumawat; Bilkees Nabi; Poonam Sharma; Namrata Pal; Devojit Kumar Sarma; Swasti Shubham; Rajnarayan R Tiwari; Samradhi singh; Manoj Kumar (World Journal of Microbiology and Biotechnology, 2023)

Process simulation-based life cycle assessment of the six-step Cu-Cl Cycle of green hydrogen generation and comparative analysis with other Cu-Cl cycles - Poonam Sutar; Ramdas Kadam; Ganapati D. Yadav (The International Journal of Life Cycle Assessment, 2023)

Influence of AtROS1 demethylase on transcription factors involved in tobacco plant defense - Poonam Bharti; Sudesh K. Yadav; Vipin Hallan (Journal of Plant Biochemistry and Biotechnology, 2023)

A MEMS-enabled portable gas chromatography injection system for trace analysis - Nipun Thamatam; Jeonghyeon Ahn; Mustahsin Chowdhury; Arjun Sharma; Poonam Gupta; Linsey C. Marr; Leyla Nazhandali; Masoud Agah (Analytica Chimica Acta, 2023)

Mapping biodiversity conservation priorities for threatened plants of Indian Himalayan Region - Poonam Mehta; Kapil Bisht; K. Chandra Sekar; Ashutosh Tewari (Biodiversity and Conservation, 2023)

Chemical composition , in vitro and in silico evaluation of essential oil from Eucalyptus tereticornis leaves for lung cancer - Anju; Amit Kumar; Poonam Yadav; Umashanker Navik; Vikas Jaitak (Natural Product Research, 2023)

Biomass-derived carbon nano-onions for the effective elimination of organic pollutants and oils from water - Poonam Kumari; Kumud Malika Tripathi; Kamlendra Awasthi; Ragini Gupta (Environmental Science and Pollution Research, 2023)

A review on control and abatement of soil pollution by heavy metals: Emphasis on artificial intelligence in recovery of contaminated soil - Krishna Gautam; Poonam Sharma; Shreya Dwivedi; Amarnath Singh; Vivek Kumar Gaur; Sunita Varjani; Janmejai Kumar Srivastava; Ashok Pandey; Jo-Shu Chang; Huu Hao Ngo (Environmental Research, 2023)

Bacterial cellulose: Nano-biomaterial for biodegradable face masks – A greener approach towards environment - Poonam Sharma; Mahak Mittal; Anita Yadav; Neeraj K. Aggarwal (Environmental Nanotechnology, Monitoring & Management, 2023)

Establishment of GLORIA sites in Indian Himalayan Region: diversity and distribution of lichens - Kapil Bisht; Shashi Upadhyay; K. Chandra Sekar; Poonam Mehta; Renu Rawal; Yogesh Joshi; Vishal Kumar (Vegetos, 2023)

First report of endophytic Bipolaris axonopicola from untapped Bastar forests, India, producing human lipase and histone deacetylase inhibitors - Soniya Goyal; Poonam Bansal; Paavan Singhal; Raman Kumar; Ajay Gupta; Gurmeen Rakhra; Mahiti Gupta; Abdulrab Ahmed M. Alkhanjaf; Ibrahim Ahmed Shaikh; Ahmad Umar; Mohd. Sayeed Akhtar; Sotirios Baskoutas (South African Journal of Botany, 2023)

Damage Detection and Virtual Reconstruction of Built Heritage: An Approach Using High-Resolution Range and Intensity Data - Poonam S. Tiwari; Hina Pande; Siddharth Gupta; Chandan Grover; Esha Semwal; Shefali Agarwal (Journal of the Indian Society of Remote Sensing, 2023)

Antimicrobial activity of nanocellulose composite hydrogel isolated from an agricultural waste - Poonam Nehra; Rishi Pal Chauhan (Archives of Microbiology, 2023)

Differential binding of CREB and REST/NRSF to NMDAR1 promoter is associated with the sex-selective cognitive deficit following postnatal PBDE-209 exposure in mice - Priya Gupta; Rajaneesh K. Gupta; Behrose S. Gandhi; Poonam Singh (Environmental Science and Pollution Research, 2023)

Facile synthesis of ZnO/ZnS hollow nanorods via Kirkendall effect with enhanced photocatalytic degradation of methylene blue - Poonam Kumari; Surojit Pande; Pragati Fageria (Environmental Science and Pollution Research, 2023)

The role of transportation in developing the tourism sector at high altitude destination, Kinnaur - Ravinder Jangra; S. P. Kaushik; Etender Singh; Parveen Kumar; Poonam Jangra (Environment, Development and Sustainability, 2023)

A review of industrial food processing using solar dryers with heat storage systems - Jasinta Poonam Ekka; Dhananjay Kumar (Journal of Stored Products Research, 2023)

Mitigation of arsenic toxicity in rice by the co-inoculation of arsenate reducer yeast with multifunctional arsenite oxidizing bacteria - Jasvinder Kaur; Vandana Anand; Sonal Srivastava; Vidisha Bist; Mariya Naseem; Pallavi Singh; Vartika Gupta; Poonam C. Singh; Sangeeta Saxena; Saraswati Bisht; Pankaj Kumar Srivastava; Suchi Srivastava (Environmental Pollution, 2023)

First report of tomato chlorosis virus (ToCV) and detection of other viruses in field-grown tomatoes in North-Western region of India - Poonam Chaudhary; Amritpreet Kaur; Balwinder Singh; Surender Kumar; Vipin Hallan; Avinash Kaur Nagpal (VirusDisease, 2023)

Design and Optimization of Nanophytosomes Containing Mucuna prureins Hydroalcoholic Extract for Enhancement of Antidepressant Activity - Poonam Karekar; Suresh Killedar; Sudhanshu Kulkarni; Amir Shaikh; Poournima Patil (Journal of Pharmaceutical Innovation, 2023)

Combustion Synthesis and Study of Double Charge Transfer in Highly Efficient Cool White-emitting Dy3+ Activated Vanadate-based Nanophosphor for Advanced Solid-state Lighting - Hina Dalal; Mukesh Kumar; Suman Devi; Priyanka Sehrawat; Monika Sheoran; Poonam Devi; Neeraj Sehrawat; Rajesh Kumar Malik (Journal of Fluorescence, 2023)

Hydrothermal Treatment of Pretreated Castor Residue for the Production of Bio-oil - Ravneet Kaur; Poonam Gera; Mithilesh Kumar Jha; Thallada Bhaskar (BioEnergy Research, 2023)

Green synthesis of nanoparticles using botanicals and their application in management of fungal phytopathogens: a review - Poonam Chauhan; Ashwani Tapwal (Archives of Microbiology, 2023)

Assessment of hazardous radionuclide emission due to fly ash from fossil fuel combustion in industrial activities in India and its impact on public - Madhusmita Mishra; Saroj Kumar Sahu; Poonam Mangaraj; Gufran Beig (Journal of Environmental Management, 2023)

In vitro and in vivo therapeutic antileishmanial potential of ellagic acid against Leishmania donovani in murine model - Poonam Keshav; Deepak Kumar Goyal; Sukhbir Kaur (Medical Microbiology and Immunology, 2023)

Nanophytosomes Loading Andrographis paniculata Hydroalcoholic Extract: Promising Drug Delivery for Hepatoprotective Efficacy - Poonam Karekar; Suresh Killedar; Harinath More (Journal of Pharmaceutical Innovation, 2023)

Targeted nano-delivery of chemotherapy via intranasal route suppresses in vivo glioblastoma growth and prolongs survival in the intracranial mouse model - Puja Sandbhor; Jayant Goda; Bhabani Mohanty; Poonam Gera; Sandhya Yadav; Godanjali Chekuri; Pradip Chaudhari; Shilpee Dutt; Rinti Banerjee (Drug Delivery and Translational Research, 2023)

Strength characteristics of hazardous wastes flyash and eggshell powder-based geopolymer-stabilized soft soil cured at ambient temperature - Poonam Shekhawat; Gunwant Sharma; Rao Martand Singh (Arabian Journal of Geosciences, 2023)

Identification, Purification, Characterization and Biopreservation Potential of Antimicrobial Peptide of Pediococcus acidilactici NCDC 252 - Shweta Dhanda; Praveen Kumar; Poonam Bansal; Jasbir Singh; Suman Dhanda (International Journal of Peptide Research and Therapeutics, 2023)

Plant mediated magnetic nano composite as promising scavenger's radionuclides for the efficient remediation in aqueous medium - Poonam Deshmukh; Santosh Kumar Sar; Manoj Kumar Jindal (Chemosphere, 2023)

A review on the effect of micro- and nano-plastics pollution on the emergence of antimicrobial resistance - Vivek Kumar Gaur; Ranjna Sirohi; Mohd Ishfaq Bhat; Krishna Gautam; Poonam Sharma; Janmejai Kumar Srivastava; Ashok Pandey (Chemosphere, 2023)

Role of ZrO2 and CeO2 support on the In2O3 catalyst activity for CO2 hydrogenation - Poonam Sharma; Phuoc Hoang Ho; Jieling Shao; Derek Creaser; Louise Olsson (Fuel, 2023)

Debris flow susceptibility assessment of Leh Valley, Ladakh, based on concepts of connectivity, propagation and evidence-based probability - Choudhurimayum Pankaj Sharma; Anil Kumar; Poonam Chahal; Uma Kant Shukla; Pradeep Srivastava; Manoj K. Jaiswal (Natural Hazards, 2023)

Self-nanoemulsifying drug delivery system (SNEDDS) mediated improved oral bioavailability of thymoquinone: optimization, characterization, pharmacokinetic, and hepatotoxicity studies - Charul Rathore; Chetna Hemrajani; Abhishek Kumar Sharma; Piyush Kumar Gupta; Niraj Kumar Jha; Alaa A. A. Aljabali; Gaurav Gupta; Sachin Kumar Singh; Jen-Chang Yang; Ram Prakash Dwivedi; Kamal Dua; Dinesh Kumar Chellappan; et al. (Drug Delivery and Translational Research, 2023)
Thymoquinone (TQ) is an antioxidant, anti-inflammatory, and hepatoprotective compound obtained from the black seed oil of Nigella sativa . However, high hydrophobicity, instability at higher pH levels, photosensitivity, and low oral bioavailability hinder its delivery to the target tissues. A self-nanoemulsifying drug delivery system (SNEDDS) was fabricated using the microemulsification technique to address these issues. Its physicochemical properties, thermodynamic stability studies, drug release kinetics, in vivo pharmacokinetics, and hepatoprotective activity were evaluated. The droplet size was in the nano-range (< 90 nm). Zeta potential was measured to be −11.35 mV, signifying the high stability of the oil droplets. In vivo pharmacokinetic evaluation showed a fourfold increase in the bioavailability of TQ-SNEDDS over pure TQ. Furthermore, in a PCM-induced animal model, TQ-SNEDDS demonstrated significant ( p < 0.05) hepatoprotective activity compared to pure TQ and silymarin. Reduction in liver biomarker enzymes and histopathological examinations of liver sections further supported the results. In this study, SNEDDS was demonstrated to be an improved oral delivery method for TQ, since it potentiates hepatotoxicity and enhances bioavailability. Graphical abstract

Study of MicroRNA (miR-221-3p, miR-133a-3p, and miR-9-5p) Expressions in Oral Submucous Fibrosis and Squamous Cell Carcinoma - Shweta Ukey; Ankit Jain; Shailendra Dwivedi; Chinmayee Choudhury; Jeewan Ram Vishnoi; Ankita Chugh; Purvi Purohit; Puneet Pareek; Poonam Elhence; Sanjeev Misra; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2023)

Geochemical characterization of the Middle Cambrian sandstones from Spiti Basin, India: implications for paleoenvironment, provenance, and tectonic setting - Shivani Pandey; Poonam Jalal; Suraj K. Parcha; Ramesh K. Sehgal (Arabian Journal of Geosciences, 2023)

Phytogenic synthesis of metallic nanoparticles: application for breast cancer nanomedicine - Poonam Banthia; Lokesh Gambhir; Dhiraj Daga; Asha Sharma; Neha Kapoor; R. D. Agarwal; Gaurav Sharma (Vegetos, 2022)

Minerals and trace elements status of blood serum of lactating goats in a semi-arid region of southwest of Haryana State, India - Mahavir Singh; Poonam Yadav; V. K. Garg; Anshu Sharma; Balvinder Singh (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Anogeissus Species in Rajasthan (India): A Comprehensive Review on an Unexplored Plant - Abhishek Dadhich; Lakshika Sharma; Mamta Dhiman; Poonam Dhawan; Abhijeet Singh; M. M. Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Year-round sustainable biomass production potential of Nannochloris sp. in outdoor raceway pond enabled through strategic photobiological screening - Kenny Paul; Mahadev Gaikwad; Poonam Choudhary; Natarajan Mohan; Puja Pai; Smita D. Patil; Yogesh Pawar; Akshay Chawande; Arun Banerjee; Vinod Nagle; Meenakshi Chelliah; Ajit Sapre; et al. (Photosynthesis Research, 2022)

Molecular diversity, haplotype distribution and genetic variation flow of Bipolaris sorokiniana fungus causing spot blotch disease in different wheat-growing zones - Prem Lal Kashyap; Sudheer Kumar; Anju Sharma; Ravi Shekhar Kumar; Sunita Mahapatra; Noyonika Kaul; Annie Khanna; Poonam Jasrotia; Gyanendra Pratap Singh (Journal of Applied Genetics, 2022)

An Overview of Scientific Research on Geoheritage in India - Poonam Chandel; Subhash Anand; Daljit Singh (Geoheritage, 2022)

Electronic nose and wireless sensor network for environmental monitoring application in pulp and paper industry: a review - Poonam Prasad; Piyush Raut; Sangita Goel; Rajesh P Barnwal; G. L. Bodhe (Environmental Monitoring and Assessment, 2022)

Alternate Approach in Storing and Shipment of SARS-CoV-2 RNA Samples with the Use of FTA Cards - Poonam Kanta; Komal Chhikara; Lalit Mohan; Arnab Ghosh; Kapil Goyal; Mini P. Singh (Current Microbiology, 2022)

Study of potent CDK7 inhibitor secondary metabolites from Tecomella undulata - Poonam Khandelwal; Harshita Tiwari; Venu Sharma; Deepak Mali; Pooja Vyas; Barkha Darra Wadhwani (Natural Product Research, 2022)

A Comprehensive Review of Development and Properties of Flyash-Based Geopolymer as a Sustainable Construction Material - Poonam Shekhawat; Gunwant Sharma; Rao Martand Singh (Geotechnical and Geological Engineering, 2022)

Novel 2-aminopyrimidine Schiff bases as possible GABA-AT inhibitors: molecular docking, MAOS, and pharmacological screening - Poonam Jaisal; Gul Naz Fatima; Sachin Kumar Vishwakarma; Vimlesh Kumar; Shailendra Pandey; Shailendra K. Saraf (Medicinal Chemistry Research, 2022)

Guar genes to genome and meta-analysis of SSR markers in sequencing studies - Shalini Pareek; Poonam Subhash Jaiswal; Divya Shrivastava (Genetic Resources and Crop Evolution, 2022)

Hydrogel composite containing azelaic acid and tea tree essential oil as a therapeutic strategy for Propionibacterium and testosterone-induced acne - Alpna Bisht; Chetna Hemrajani; Charul Rathore; Tania Dhiman; Rajan Rolta; Navneet Upadhyay; Prakriti Nidhi; Gaurav Gupta; Kamal Dua; Dinesh Kumar Chellappan; Kamal Dev; Anuradha Sourirajan; et al. (Drug Delivery and Translational Research, 2022)
Azelaic acid (AzA) is a USFDA bioactive prescribed against acne vulgaris . It possesses delivery challenges like poor aqueous solubility, low skin-penetrability, and dose-dependent side effects, which could be overcome by its synergistic combination with tea tree oil (TTO) as a microemulsion (ME)-based hydrogel composite. AzA-TTO ME was prepared to employ pseudo-ternary phase diagram construction. The best AzA-TTO ME was of uniform size (polydispersity index < 0.7), nano-range (~357.4 ± 2% nm), transmittance (> 90%), and negative zeta potential (−1.42 ± 0.25% mV) values. ME hydrogel composite with optimum rheological and textural attributes showed better permeation, retention, and skin-compliant characteristics, vis-a-vis marketed formulation (Aziderm™) when evaluated in Wistar rat skin. In vitro antibacterial efficacy in bacterial strains, i.e., Staphylococcus aureus , Propionibacterium acne , and Staphylococcus epidermidis , was evaluated employing agar well plate diffusion and broth dilution assay. ME hydrogel has shown an increase in zone of inhibition by two folds and a decrease in minimum inhibitory concentration (MIC) by eightfold against P. acnes vis-a-vis AzA. Finally, ME hydrogel composite exhibited a better reduction in the papule density (93.75 ± 1.64%) in comparison to Aziderm™ 72.69 ± 4.67%) on acne as developed in rats by inducing testosterone. Thus, the developed AzA-TTO ME hydrogel composite promises an efficacious and comparatively safer drug delivery system for the topical therapy of acne vulgaris . Graphical abstract

Sustainable carbon nano-onions as an adsorbent for the efficient removal of oxo-anions - Poonam Kumari; Kumud Malika Tripathi; Kamlendra Awasthi; Ragini Gupta (Environmental Science and Pollution Research, 2022)

Hydrophilic Polymers in Agriculture and the Use of Nanoadditives to Improve Their Capabilities - Poonam Barala; Vinita Hooda (Journal of Soil Science and Plant Nutrition, 2022)

Evaluation of TiO2 Nanoparticles Physicochemical Parameters Associated with their Antimicrobial Applications - Poonam Sharma; Rekha Kumari; Meena Yadav; Rup Lal (Indian Journal of Microbiology, 2022)

Unravelling the emerging threats of microplastics to agroecosystems - Shweta Yadav; Ekta Gupta; Anju Patel; Suchi Srivastava; Virendra Kumar Mishra; Poonam C. Singh; Pankaj Kumar Srivastava; Saroj Kanta Barik (Reviews in Environmental Science and Bio/Technology, 2022)

Emerging approaches to determine maturity of citrus fruit - Arun Kumar Gupta; Urbi Pathak; Thoithoi Tongbram; Manisha Medhi; Anupun Terdwongworakul; Lembe Samukelo Magwaza; Asanda Mditshwa; Tao Chen; Poonam Mishra (Critical Reviews in Food Science and Nutrition, 2022)

Untargeted lipidomic differences between clinical strains of methicillin-sensitive and methicillin-resistant Staphylococcus aureus - Philip Nikolic; Poonam Mudgil; David G. Harman; John Whitehall (Infectious Diseases, 2022)

Lipid-based emulsion drug delivery systems — a comprehensive review - Mori Dhaval; Poonam Vaghela; Kajal Patel; Keshvi Sojitra; Mohini Patel; Sushma Patel; Kiran Dudhat; Sunny Shah; Ravi Manek; Ramesh Parmar (Drug Delivery and Translational Research, 2022)

The source of carbon and nitrogen differentially affects the survival of Neisseria meningitidis in macrophages and epithelial cells - Poonam Kanojiya; Riya Joshi; Sunil D. Saroj (Archives of Microbiology, 2022)

Cruising Under and Post the COVID Pandemic: Toward Realization of the United Nations’ Sustainable Development Goals - Majid Eskafi; Poonam Taneja; Gudmundur F. Ulfarsson (Journal of Marine Science and Engineering, 2022)
Maritime sectors have always dealt with uncertainties and disruptions. The COVID pandemic confronted the cruise industry with profound, wide-ranging, and lasting challenges while disrupting normal operations. Although the cruise industry contributes to the implementation of the United Nations Sustainable Development Goals (UN SDGs), resumption and sustainable cruising requires the industry to adapt to the challenges presented. To this end, the paper suggests adaptive actions for the cruise sector to respond to the pandemic and links the actions to the UN SDGs to highlight their sustainable contributions. A system thinking approach is applied and a literature review is conducted to identify suitable adaptive actions. This paper shows the importance of UN SDGs 3, 4 and, in particular, 17 for sustainable cruising. The results of this paper provide support for informed decision-making to increase the cruise industry’s sustainability. This paper recommends that stakeholders: 1- identify drivers and barriers of sustainable cruising, 2- adapt to changes and embrace the UN SDGs, as they provide a platform for realizing sustainability, and 3- use educational programs to improve and transfer knowledge on sustainable cruising between academia and policymakers.

Change Detection and Feature Extraction Using High-Resolution Remote Sensing Images - Vinod K. Sharma; Dushyant Luthra; Eshita Mann; Poonam Chaudhary; V. M. Chowdary; C. S. Jha (Remote Sensing in Earth Systems Sciences, 2022)

BhopaL Epidemiologic Sleep Study: BLESS Study–Design and Sampling of the Study - Abhishek Goyal; Ankur Joshi; Abhijit Pakhare; Rajnish Joshi; Parneet Kaur Bhagtana; Chinta Siva Koti Rupa Sridevi; Mallu Abhinav Reddy; Poonam Chaudhary (Sleep and Vigilance, 2022)

Intraspecific Variation in Gloriosa Superba (L.) Population from Western Himalayas (India) and Evaluation of in vitro Antigout Potential - Ankita Misra; Pushpendra Kumar Shukla; Manish Kumar; Poonam Rawat; Sharad Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Regulatory role of organic acids and phytochelators in influencing the rhizospheric availability of phosphorus and iron and their uptake by plants - Raktim Mitra; Poonam Yadav; Kalidindi Usha; Bhupinder Singh (Plant Physiology Reports, 2022)

Acute onset urinary retention and neurogenic bladder: an unusual presenting feature of childhood acute myeloid leukemia - Prateek Kumar Panda; Indar Kumar Sharawat; Apurva Tomar; Shubhangee Arya; Rituparna Chetia; Poonam Sherwani (Acta Neurologica Belgica, 2022)

Desktop Research into Historic Automation Projects of Brownfield Container Terminals - Luis Burgos Gajardo; Poonam Taneja; Mark van Koningsveld (Journal of Marine Science and Engineering, 2022)
There is a global trend of automation of container terminals. However, there is a lack of literature to guide automation projects for brownfield terminals. Therefore, the experiences and lessons learnt from historical brownfield automation of container terminals are a valuable source of information to guide future projects. This paper describes the brownfield container terminal automation projects carried out in recent years. For each project, the drivers, challenges, benefits, and drawbacks of automation were gathered using a questionnaire directed to operators of brownfield converted container terminals. The characteristics as to the terminal sizes and implemented solutions were gathered via a desk study. It was found that the main drivers for automation are operational cost reductions and higher productivity. However, the desired levels are not always reached and depend on the terminal conditions and the solutions adopted. The continuity of operations was also identified as a major challenge. Terminals have dealt with it either by following a phased, greenfield-like, or big bang approach. Most terminals have opted for semi-automated solutions (automation of yard equipment only); this resulted in fewer labor problems, improved vessel productivity, less required space, and better agility in dealing with disruptions. Most terminals have chosen either automated RMG or the automated version of their manned equipment for yard operations, although exceptions were observed.

Current Approaches for Dissolution Similarity Assessment, Requirements, and Global Expectations - Andreas M. Abend; Limin Zhang; Emilija Fredro-Kumbaradzi; Thomas Hoffelder; Michael J. Cohen; Om Anand; Poonam Delvadia; Haritha Mandula; Zhen Zhang; Evangelos Kotzagiorgis; Susan Lum; Victor Gomes Pereira; et al. (The AAPS Journal, 2022)

Synergistic action of Trichoderma koningiopsis and T. asperellum mitigates salt stress in paddy - Anshu Anshu; Pallavi Agarwal; Kumkum Mishra; Udit Yadav; Isha Verma; Soni Chauhan; Pankaj Kumar Srivastava; Poonam C. Singh (Physiology and Molecular Biology of Plants, 2022)

Cultivar-Specific Oxidative Modification of Proteins, Proteolytic Activity and Alterations in Proteomes of Rice Seedlings to Simultaneous Water Deficit and Aluminum Toxicity - Poonam Pandey; Rama Shanker Dubey (Journal of Plant Growth Regulation, 2022)

Tectonaquinones A, B and C: three new naphthoquinone derivatives from the heartwood of Tectona grandis - Pooja Vyas; Barkha Darra Wadhwani; Poonam Khandelwal; Hiroshi Araya; Yoshinori Fujimoto (Natural Product Research, 2022)

New record of chromosome count and B- chromosome in Tinantia erecta (Jacq.) Fenzl collected from different localities of Mussoorie, Uttarakhand (India) - Arneet Grewal; Poonam Rani (The Nucleus, 2022)

FOXM1 mediates GDF-15 dependent stemness and intrinsic drug resistance in breast cancer - Anupama Modi; Purvi Purohit; Dipayan Roy; Jeewan Ram Vishnoi; Puneet Pareek; Poonam Elhence; Priyanka Singh; Shailja Sharma; Praveen Sharma; Sanjeev Misra (Molecular Biology Reports, 2022)

Ethnobotany, Phytochemistry and Pharmacology of Palash (Butea monosperma (Lam.) Taub.): a Systematic Review - Poonam Kumari; Kirti Raina; Sunil Thakur; Rohit Sharma; Natália Cruz-Martins; Pardeep Kumar; Kalyan Barman; Swati Sharma; Dileep Kumar; Pradeep Kumar Prajapati; Rohit Sharma; Ashun Chaudhary (Current Pharmacology Reports, 2022)

Respiratory viral infections other than SARS CoV-2 among the North Indian patients presenting with acute respiratory illness during the first COVID-19 wave - Monika Sapra; Sangeetha Kirubanandhan; Poonam Kanta; Arnab Ghosh; Kapil Goyal; Mini P. Singh; R. K. Ratho (VirusDisease, 2022)

Impact of High-Fiber Ingredient Mix on the Nutritional Indices of the Women Suffering from Metabolic Syndrome - Neerja Singla; Poonam Bakhetia; Rohini Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

‘Omics’ approaches in developing combined drought and heat tolerance in food crops - Anjali Bhardwaj; Poonam Devi; Shikha Chaudhary; Anju Rani; Uday Chand Jha; Shiv Kumar; H. Bindumadhava; P. V. Vara Prasad; Kamal Dev Sharma; Kadambot H. M. Siddique; Harsh Nayyar (Plant Cell Reports, 2022)

Applicability of Reddish-Orange Light Emitting Samarium (III) Complexes for Biomedical and Multifunctional Optoelectronic Devices - Pooja Hooda; V. B. Taxak; R. K. Malik; Savita Khatri; Poonam Kumari; S. P. Khatkar; Rajesh Kumar (Journal of Fluorescence, 2022)

Metabolic Cascade for Remediation of Plastic Waste: a Case Study on Microplastic Degradation - Vivek K. Gaur; Shivangi Gupta; Poonam Sharma; Pallavi Gupta; Sunita Varjani; Janmejai Kumar Srivastava; Jo-Shu Chang; Xuan-Thanh Bui (Current Pollution Reports, 2022)

Engineering Aspects of Incidence, Prevalence, and Management of Osteoarthritis: A Review - Dhirendra Kumar Verma; Poonam Kumari; Subramani Kanagaraj (Annals of Biomedical Engineering, 2022)

Bio-ecological studies of shoot gall psylla, Apsylla cistellata Buckton on mango under Tarai region of Northern India - Jyoti Raina; Poonam Srivastava (International Journal of Tropical Insect Science, 2022)

Systematic Evaluation of the Effect of Formulation Variables on In Vitro Performance of Mometasone Furoate Suspension-Metered Dose Inhalers - Sagar S. Bachhav; Poonam Sheth; Dennis Sandell; Mårten Svensson; Sharvari Bhagwat; Denise S. Conti; Oluwamurewa Oguntimein; Sneha Dhapare; Bhawana Saluja; Lawrence Winner; Jürgen B. Bulitta; Guenther Hochhaus (The AAPS Journal, 2022)

Metal(loid) nanosorbents in restoration of polluted soils: geochemical, ecotoxicological, and remediation perspectives - Arpna Kumari; Poonam Kumari; Vishnu D. Rajput; Svetlana N. Sushkova; Tatiana Minkina (Environmental Geochemistry and Health, 2022)

Mesenchymal stem cells are prospective novel off-the-shelf wound management tools - Poonam Malhotra; Manish Shukla; Poonam Meena; Anupama Kakkar; Nitin Khatri; Rakesh K Nagar; Mukesh Kumar; Sumit K Saraswat; Supriya Shrivastava; Rajan Datt; Siddharth Pandey (Drug Delivery and Translational Research, 2022)

Ecological performance of multifunctional pesticide tolerant strains of Mesorhizobium sp. in chickpea with recommended pendimethalin, ready-mix of pendimethalin and imazethpyr, carbendazim and chlorpyrifos application - Pallavi Mansotra; Poonam Sharma; Asmita Sirari; Navneet Aggarwal (Archives of Microbiology, 2022)

RPS13, a potential universal reference gene for normalisation of gene expression in multiple human normal and cancer tissue samples - Mudasir Rashid; Sanket Girish Shah; Abhiram Natu; Tripti Verma; Sukanya Rauniyar; Poonam B. Gera; Sanjay Gupta (Molecular Biology Reports, 2021)

Molecular identification of citrus greening bacterium associated with Kinnow Mandarin in Western Uttar Pradesh, India - Shweta; Jitender Singh; Poonam Kashyap; Pankaj Kumar; R. Kumar; A. S. Panwar; V. K. Baranwal (Indian Phytopathology, 2021)

Identification and in silico characterization of transcription termination/antitermination protein NusA of Mycobacterium fortuitum - Poonam Katoch; Shubham Mittal; Shivani Sood; Rahul Shrivastava (Biologia, 2021)

Antiparasitic potential of Indian honey bee glue against strains of Leishmania donovani sensitive and resistant to synthetic antileishmanial - Deepak Kumar Goyal; Poonam Keshav; Sukhbir Kaur (Biologia, 2021)

Phytochemical profile, antioxidant potential and DFT study of Araucaria columnaris (G. Forst.) Hook. Branch extracts - Poonam Kumari Patial; Damanjit Singh Cannoo (Natural Product Research, 2021)

Diversity of threatened medicinal plants of Indian Himalayan Region - Poonam Mehta; Kapil Bisht; K. Chandra Sekar (Plant Biosystems, 2021)

A global comparison of implementation and effectiveness of materiovigilance program: overview of regulations - Deeksha Joshi; Ishita Sharma; Saurabh Gupta; Thakur Gurjeet Singh; Sonia Dhiman; Abhimanyu Prashar; Monica Gulati; Bimlesh Kumar; Sukriti Vishwas; Dinesh Kumar Chellappan; Gaurav Gupta; Niraj Kumar Jha; et al. (Environmental Science and Pollution Research, 2021)

Correction to: Bioactivities of Penicillium citrinum isolated from a medicinal plant Swertia chirayita - Hemant Sharma; Arun Kumar Rai; Rajen Chettri; Poonam Singh Nigam (Archives of Microbiology, 2021)

Plant growth promoting Bacillus-based bio formulations improve wheat rhizosphere biological activity, nutrient uptake and growth of the plant - Priyanka Chandra; Rinki Khobra; Parul Sundha; Rakesh Kumar Sharma; Poonam Jasrotia; Amaresh Chandra; Devendra Pal Singh; Gyanendra Pratap Singh (Acta Physiologiae Plantarum, 2021)

Characterization, application and statistical optimization approach for enhanced production of pyocyanin pigment by Pseudomonas aeruginosa DN9 - Mayur Gahlout; Poonam B. Chauhan; Hiren Prajapati; Nirali Tandel; Seema Rana; Dhrutikumari Solanki; Nilamben Patel (Systems Microbiology and Biomanufacturing, 2021)

PHLPP1/Nrf2–Mdm2 axis induces renal apoptosis via influencing nucleo-cytoplasmic shuttling of FoxO1 during diabetic nephropathy - Alpana Mathur; Vivek Kumar Pandey; Mohammad Fareed Khan; Poonam Kakkar (Molecular and Cellular Biochemistry, 2021)

Distance Learning Experience During Covid-19 Period in Higher Education for Space Application - Poonam S. Tiwari; Harish Karnatak; Shefali Agarwal; Kamal Pandey; Janardan Vishwakarma; Ashok Ghildiyal; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2021)

Evaluation of the Role of Routine Laboratory Biomarkers in COVID-19 Patients: Perspective from a Tertiary Care Hospital in India - Barnali Das; Seema Y. Bhatia; Poonam M. Pal (Indian Journal of Clinical Biochemistry, 2021)

Bioactivites of Penicillium citrinum isolated from a medicinal plant Swertia chirayita - Hemant Sharma; Arun Kumar Rai; Rajen Chettri; Poonam Singh Nigam (Archives of Microbiology, 2021)
Endophytes associated with plants have the property to produce active biomolecules with their possible applications in agro-industrial sectors. This study provides a project work on analyzing various activities of fungal endophytes isolated from Swertia chirayita of Sikkim Himalayan region. Among several fungal endophytes screened, isolate UTCRF6 was found most active with the secretion of enzymes protease, cellulase, amylase and chitinase, as well as other metabolites Indoleacetic acid and siderophores. This endophyte was found active in restricting the growth of phyto-pathogens, including strains of Fusarium solani , Colletotrichum gloeosporioides , Alternaria alternata, Pestalotiopsis theae and Sclerotinia sclerotiorum . Morphological and molecular studies of this endophytic fungus showed similarity with Penicillium citrinum. Graphic abstract

Drug resistance mutations in protease gene of HIV-1 subtype C infected patient population - Mohammad Misbah; Poonam Gupta; Gaurav Roy; Suresh Kumar; Mohammad Husain (VirusDisease, 2021)

Taxonomic description and annotation of Catapodium rigidum (L.) C. E. Hubbard (Poaceae: Pooideae, Poeae, Parapholiinae) from Kashmir Himalayas, India - Mudassir Ahmad Bhat; Sheikh Abdul Shakoor; Poonam Chowdhary; Priya Badgal; Bilal Ahmad Mir; Amarjit Singh Soodan (Vegetos, 2021)

In silico molecular docking of SARS-CoV-2 surface proteins with microbial non-ribosomal peptides: identification of potential drugs - Poonam Bansal; Raman Kumar; Jasbir Singh; Suman Dhanda (Journal of Proteins and Proteomics, 2021)

A Comparative Study of Levocetirizine Loaded Vesicular and Matrix Type System for Topical Application: Appraisal of Therapeutic Potential against Atopic Dermatitis - Ravi Raj Pal; Anish Kumar Maurya; Poonam Parashar; Shubhini A. Saraf (Journal of Pharmaceutical Innovation, 2021)

Membrane Bound Aminopeptidase B of a Potential Probiotic Pediococcus acidilactici NCDC 252: Purification, Physicochemical and Kinetic Characterization - Pooja Attri; Drukshakshi Jodha; Poonam Bansal; Jasbir Singh; Suman Dhanda (International Journal of Peptide Research and Therapeutics, 2021)

SNPRBb: economically important trait specific SNP resources of buffalo (Bubalus bubalis) - D. C. Mishra; Sunita Yadav; Poonam Sikka; A. Jerome; S. S. Paul; A. R. Rao; Neeraj Budhlakoti; Jyotika Bhati; K. P. Singh; A. K. Balhara; I. Singh; Anil Rai; et al. (Conservation Genetics Resources, 2021)

Crop Response to Iron Deficiency is Guided by Cross-Talk Between Phytohormones and their Regulation of the Root System Architecture - Pandurang R. Divte; Poonam Yadav; Atul Bhagawan Pawar; Vasundhara Sharma; Anjali Anand; Raghunath Pandey; Bhupinder Singh (Agricultural Research, 2021)

Intercropping in Sugarcane Improves Functional Diversity, Soil Quality and Crop Productivity - S. R. Singh; Poonam Yadav; Dinesh Singh; S. K. Shukla; M. K. Tripathi; Lal Bahadur; Aradhana Mishra; Sanjeev Kumar (Sugar Tech, 2021)

Variability in alkaloid and phenolic content vis-a-vis antigout potential among the natural population of Gloriosa superba (L.) collected from Central India - Ankita Misra; Sharad Srivastava; Pushpendra Kumar Shukla; Manish Kumar; Md. Khalid; Poonam Kushwaha; Pawan Kumar Agrawal (Natural Product Research, 2021)

OsJAZ11 regulates phosphate starvation responses in rice - Bipin K. Pandey; Lokesh Verma; Ankita Prusty; Ajit Pal Singh; Malcolm J. Bennett; Akhilesh K. Tyagi; Jitender Giri; Poonam Mehra (Planta, 2021)
Main conclusion OsJAZ11 regulates phosphate homeostasis by suppressing jasmonic acid signaling and biosynthesis in rice roots. Abstract Jasmonic Acid (JA) is a key plant signaling molecule which negatively regulates growth processes including root elongation. JAZ (JASMONATE ZIM-DOMAIN) proteins function as transcriptional repressors of JA signaling. Therefore, targeting JA signaling by deploying JAZ repressors may enhance root length in crops. In this study, we overexpressed JAZ repressor OsJAZ11 in rice to alleviate the root growth inhibitory action of JA. OsJAZ11 is a low phosphate (Pi) responsive gene which is transcriptionally regulated by OsPHR2. We report that OsJAZ11 overexpression promoted primary and seminal root elongation which enhanced Pi foraging. Expression studies revealed that overexpression of OsJAZ11 also reduced Pi starvation response (PSR) under Pi limiting conditions. Moreover, OsJAZ11 overexpression also suppressed JA signaling and biosynthesis as compared to wild type (WT). We further demonstrated that the C-terminal region of OsJAZ11 was crucial for stimulating root elongation in overexpression lines. Rice transgenics overexpressing truncated OsJAZ11ΔC transgene (i.e., missing C-terminal region) exhibited reduced root length and Pi uptake. Interestingly, OsJAZ11 also regulates Pi homeostasis via physical interaction with a key Pi sensing protein, OsSPX1. Our study highlights the functional connections between JA and Pi signaling and reveals JAZ repressors as a promising candidate for improving low Pi tolerance of elite rice genotypes.

Tolerance of cotton to elevated levels of Pb and its potential for phytoremediation - Sivakoti Ramana; Awadhesh Kumar Tripathi; Kollah Bharati; Amar Bahadur Singh; Ajay Kumar; Asha Sahu; Poonam Singh Rajput; Pradip Dey; Jayanta Kumar Saha; Ashok K. Patra (Environmental Science and Pollution Research, 2021)

Four propositions on integrated sustainability: toward a theoretical framework to understand the environment, peace, and sustainability nexus - Joshua Fisher; Poonam Arora; Siqi Chen; Sophia Rhee; Tempest Blaine; Dahlia Simangan (Sustainability Science, 2021)
The sustainability agenda has evolved around a set of interconnected dilemmas regarding economic, social, and environmental goals. Progress has been made in establishing thresholds and targets that must be achieved to enable life to continue to thrive on the planet. However, much work remains to be done in articulating coherent theoretical frameworks that adequately describe the mechanisms through which sustainability outcomes are achieved. This paper reviews core concepts in the sustainability agenda to develop four propositions on integrated sustainability that collectively describe the underlying mechanisms of sustainable development. We then advance a framework for integrated sustainability and assess its viability through linear regression and principal components analysis of key selected indicators. The results provide preliminary evidence that countries with institutions that enable cooperation and regulate competition perform better in attaining integrated sustainability indicators. Our findings suggest that institutional design is important to sustainability outcomes and that further research into process-oriented mechanisms and institutional characteristics can yield substantial dividends in enabling effective sustainability policy.

COVID-19 infection in a HIV positive health care worker: first case report from a tertiary care hospital of North India - Ritin Mohindra; Poonam Kanta; Pradakshana Porchezhian; Kapil Goyal; Vikas Suri; Mini P. Singh; Lakshmi PVM; Ashish Bhalla (VirusDisease, 2021)

Integration of Texture and Spectral Response with AI Techniques for Buildings Footprint Identification Using High-Resolution Satellite Images - Gaurav Pandey; Vinod Kumar Sharma; Poonam Chaudhary; V. M. Chowdary; Udayraj (Journal of the Indian Society of Remote Sensing, 2021)

Synergistically-acting Enterocin LD3 and Plantaricin LD4 Against Gram-Positive and Gram-Negative Pathogenic Bacteria - Poonam Sheoran; Santosh Kumar Tiwari (Probiotics and Antimicrobial Proteins, 2021)

Potential of cotton for remediation of Cd-contaminated soils - Sivakoti Ramana; Awadhesh Kumar Tripathi; Ajay Kumar; Amar Bahadur Singh; Kollah Bharati; Asha Sahu; Poonam Singh Rajput; Jayanta Kumar Saha; Sanjay Srivastava; Pradip Dey; Ashok K. Patra (Environmental Monitoring and Assessment, 2021)

Doxorubicin-Loaded Mixed Micelles for the Effective Management of Skin Carcinoma: In Vivo Anti-Tumor Activity and Biodistribution Studies - Nagarani Thotakura; Anshul Panjeta; Poonam Negi; Simran Preet; Kaisar Raza (AAPS PharmSciTech, 2021)

FTA cards for COVID 2019 samples: easy and cost effective innovation! - Poonam Chauhan; Parakriti Gupta; Komal Chhikara; Kapil Goyal; Mini P. Singh (VirusDisease, 2021)

Manganese-induced oxidative stress, ultrastructural changes, and proteomics studies in rice plants - Ritika Rajpoot; Rajneesh Kumar Srivastava; Anjana Rani; Poonam Pandey; R. S. Dubey (Protoplasma, 2021)

Theoretical and experimental verification of molecular properties of novel benzamide derivatives using computational platforms and in vitro antibacterial activity - Poonam M. Wanjari; Santosh N. Mokale; Avinash V. Bharati; Vishwas N. Ingle (Medicinal Chemistry Research, 2021)

Advances and clinical challenges for translating nerve conduit technology from bench to bed side for peripheral nerve repair - Poonam Meena; Anupama Kakkar; Mukesh Kumar; Nitin Khatri; Rakesh Kumar Nagar; Aarti Singh; Poonam Malhotra; Manish Shukla; Sumit Kumar Saraswat; Supriya Srivastava; Rajan Datt; Siddharth Pandey (Cell and Tissue Research, 2021)

First-time comparative investigation on Araucaria columnaris (G. Forst.) Hook. leaves: extraction techniques, phytochemicals, medicinal activities, and DFT study - Poonam K. Patial; Damanjit S. Cannoo (Medicinal Chemistry Research, 2021)

A rapid green synthesis of Ag/AgCl-NC photocatalyst for environmental applications - Priyanka Panchal; Poonam Meena; Satya Pal Nehra (Environmental Science and Pollution Research, 2021)

Correction to: Symbiotic Parameters, Productivity and Profitability in Kabuli Chickpea (Cicer arietinum L.) as Influenced by Application of Phosphorus and Biofertilizers - Diljeet Kaur; Guriqbal Singh; Poonam Sharma (Journal of Soil Science and Plant Nutrition, 2020)

Symbiotic Parameters, Productivity and Profitability in Kabuli Chickpea (Cicer arietinum L.) as Influenced by Application of Phosphorus and Biofertilizers - Diljeet Kaur; Guriqbal Singh; Poonam Sharma (Journal of Soil Science and Plant Nutrition, 2020)

Exemplifying rhizobacteria for growth stimulation and disease suppression in finger millet - Poonam Kumari; R. S. Netam; Prafull Kumar (Journal of Plant Diseases and Protection, 2020)

Peptidoglycan Hydrolases of Probiotic Pediococcus acidilactici NCDC 252: Isolation, Physicochemical and In Silico Characterization - Dimpi Gandhi; Preeti Chanalia; Poonam Bansal; Suman Dhanda (International Journal of Peptide Research and Therapeutics, 2020)

New record of a monopartite begomovirus and papaya leaf curl betasatellite infecting Mirabilis jalapa in Himachal Pradesh, India - Aditya Kulshreshtha; Poonam Roshan; Amit Kumar Kesharwani; Vipin Hallan (Indian Phytopathology, 2020)

Metal toxicity and natural antidotes: prevention is better than cure - Chetan Rajak; Neelu Singh; Poonam Parashar (Environmental Science and Pollution Research, 2020)

Jasmonates induce growth and modulation in pigments and vitamins of Brassica oleracea var. capitata, italica and botrytis edible heads (foliage/inflorescence) - Geetika Sirhindi; Shruti Kaushik; Ruqia Mushtaq; Poonam Sharma; Neha Dogra (Brazilian Journal of Botany, 2020)

3D Bioprinting of Cardiovascular Tissues for In Vivo and In Vitro Applications Using Hybrid Hydrogels Containing Silk Fibroin: State of the Art and Challenges - Laura Vettori; Poonam Sharma; Jelena Rnjak-Kovacina; Carmine Gentile (Current Tissue Microenvironment Reports, 2020)
Purpose of Review 3D bioprinting of cardiovascular tissues for in vitro and in vivo applications is currently investigated as a potential solution to better mimic the microenvironment typical of the human heart. However, optimal cell viability and tissue vascularization remain two of the main challenges in this regard. Silk fibroin (SF) as a natural biomaterial with unique features supports cell survival and tissue vascularization. This review aims to evaluate the potential of hydrogels containing SF in 3D bioprinting of cardiac tissue that better recapitulate the native cardiac microenvironment. Recent Findings SF hydrogels spontaneously develop nanocrystals, which limit their use for 3D bioprinting applications. Nevertheless, the printability of SF is improved in hybrid hydrogels by mixing it with other natural polymers (such as alginate and gelatin). This is achieved by adding SF with other polymers or by crosslinking it by peroxidase catalysis (i.e., with alginate). Compared to only SF-based hydrogels, hybrid hydrogels provide a durable bioprinted construct with improved mechanical stability and biological properties. To date, studies using cardiac cells in bioprinted SF constructs are yet to be performed. Summary Mixing SF with other polymers in bioprinted hybrid hydrogels improves the printability and durability of 3D bioprinted tissues. Studies using these hydrogels with cardiac cells will be required to evaluate the biocompatibility of SF hybrid hydrogels and to establish their potential use for cardiovascular applications.

OsJAZ9 overexpression modulates jasmonic acid biosynthesis and potassium deficiency responses in rice - Ajit Pal Singh; Bipin K. Pandey; Poonam Mehra; Thierry Heitz; Jitender Giri (Plant Molecular Biology, 2020)

Utilizing Advance Texture Features for Rapid Damage Detection of Built Heritage Using High-Resolution Space Borne Data: A Case Study of UNESCO Heritage Site at Bagan, Myanmar - Navneet Kaur; Poonam S. Tiwari; Hina Pande; Shefali Agrawal (Journal of the Indian Society of Remote Sensing, 2020)

Statistical inferences from measured data on concentrations of naturally occurring radon, thoron, and decay products in Kumaun Himalayan belt - Ankur Kumar; Prakhar Singh; Tarun Agarwal; Manish Joshi; Poonam Semwal; Kuldeep Singh; Parmanad Prakash Pathak; Rakesh Chand Ramola (Environmental Science and Pollution Research, 2020)

Cartilage repair using stem cells & biomaterials: advancement from bench to bedside - Anupama Kakkar; Aarti Singh; Sumit Kumar Saraswat; Supriya Srivastava; Nitin Khatri; Rakesh Kumar Nagar; Mukesh Kumar; Poonam Meena; Rajan Datt; Siddharth Pandey (Molecular Biology Reports, 2020)

Correction to: a facile approach for fabricating CD44-targeted delivery of hyaluronic acid-functionalized PCL nanoparticles in urethane-induced lung cancer: Bcl-2, MMP-9, caspase-9, and BAX as potential markers - Poonam Parashar; Chandra Bhushan Tripathi; Malti Arya; Jovita Kanoujia; Mahendra Singh; Abhishek Yadav; Shubhini A. Saraf (Drug Delivery and Translational Research, 2020)

Palynofloral diversity and palaeoenvironments of early Eocene Akri lignite succession, Kutch Basin, western India - Poonam Verma; Rahul Garg; M. R. Rao; Sunil Bajpai (Palaeobiodiversity and Palaeoenvironments, 2020)

Coordination of Mesorhizobium sp. and endophytic bacteria as elicitor of biocontrol against Fusarium wilt in chickpea - Sharon Nagpal; Poonam Sharma; Asmita Sirari; R.K. Gupta (European Journal of Plant Pathology, 2020)

Gold nanoparticles modulate the steroidogenic and apoptotic pathway in a buffalo granulosa cell model - Erica Lawai Lyngdoh; Varij Nayan; Monika Vashisht; Suman Kumari; Anuradha Bhardwaj; Tanvi Bhatia; Jasmer Dalal; Shikha Pawaria; Suneel Kumar Onteru; Poonam Sikka; Dheer Singh (Biotechnology Letters, 2020)

Augmented Therapeutic Efficacy of Naringenin Through Microemulsion-Loaded Sericin Gel Against UVB-Induced Photoaging - Poonam Parashar; Surabhi Pal; Monika Dwivedi; Shubhini A. Saraf (AAPS PharmSciTech, 2020)

In Vitro Dissolution Profiles Similarity Assessment in Support of Drug Product Quality: What, How, When—Workshop Summary Report - Sandra Suarez-Sharp; Andreas Abend; Thomas Hoffelder; David Leblond; Poonam Delvadia; Elisabeth Kovacs; Dorys Argelia Diaz (The AAPS Journal, 2020)

Development and Validation of Sample Preparation and an HPLC Analytical Method for Dissolution Testing in Fed-State Simulated Gastric Fluid—Illustrating Its Application for Ibuprofen and Ketoconazole Immediate Release Tablets - Harsh S. Shah; Rusha Sardhara; Kajal Nahar; Ting Xu; Poonam Delvadia; Akhtar Siddiqui; Zongming Gao; Arzu Selen; Kenneth Morris (AAPS PharmSciTech, 2020)

Genetic variability: physiological characteristics, pathogenicity and molecular diversity of Fusarium oxysporum f. sp. cumini infecting Cumin cyminum L. in India - Poonam Kanani; Y. M. Shukla (Vegetos, 2020)

Photosynthetic Response of Plants Under Different Abiotic Stresses: A Review - Anket Sharma; Vinod Kumar; Babar Shahzad; M. Ramakrishnan; Gagan Preet Singh Sidhu; Aditi Shreeya Bali; Neha Handa; Dhriti Kapoor; Poonam Yadav; Kanika Khanna; Palak Bakshi; Abdul Rehman; et al. (Journal of Plant Growth Regulation, 2020)

Experimental and kinetic study of removal of lead (Pb+2) from battery effluent using sweet lemon (Citrus limetta) peel biochar adsorbent - Poonam; Narendra Kumar (Environment, Development and Sustainability, 2020)

Characterisation of recombinant thermostable manganese-superoxide dismutase (NeMnSOD) from Nerium oleander - Rashmi Gangwar; Poonam Kumari; Apurva Chatrath; Ramasare Prasad (Molecular Biology Reports, 2020)

Conservation and prioritization of threatened plants in Indian Himalayan Region - Poonam Mehta; K. Chandra Sekar; Deepika Bhatt; Ashutosh Tewari; Kapil Bisht; Shashi Upadhyay; Vikram S. Negi; Bhawana Soragi (Biodiversity and Conservation, 2020)

Glucose withdrawal induces Endothelin 1 release with significant angiogenic effect from first trimester (FTM), but not term human umbilical cord perivascular cells (HUCPVC) - Peter Szaraz; Poonam Mander; Nadav Gasner; Max Librach; Farwah Iqbal; Clifford Librach (Angiogenesis, 2020)

Understanding the Oral Absorption of Irbesartan Using Biorelevant Dissolution Testing and PBPK Modeling - Navpreet Kaur; Poonam Singh Thakur; Ganesh Shete; Rahul Gangwal; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2020)

Production of Agar-Derived Antioxidants and Single Cell Detritus from Gracilaria corticata Using Agarase from Microbulbifer sp. CMC-5 - RaviChand Jonnadula; Md. Imran; Poonam Vashist; Sanjeev C. Ghadi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Effect of full-length and truncated variants of LL-37 on dengue virus infection and immunomodulatory effects of LL-37 in dengue virus infected U937-DC-SIGN cells - Nandadeep J. Jadhav; Poonam S. Patil; Kalichamy Alagarasu (International Journal of Peptide Research and Therapeutics, 2020)

In Vitro Efficacy of Lipid Conjugated Peptidomimetics Against Mycobacterium smegmatis - Deepika Sharma; Poonam; Rahul Shrivastava; Gopal Singh Bisht (International Journal of Peptide Research and Therapeutics, 2020)

Aggregation, adhesion and efficacy studies of probiotic candidate Pediococcus acidilactici NCDC 252: a strain of dairy origin - Raman Kumar; Poonam Bansal; Jasbir Singh; Suman Dhanda; Jitender Kumar Bhardwaj (World Journal of Microbiology and Biotechnology, 2020)

In situ gel of lamotrigine for augmented brain delivery: development characterization and pharmacokinetic evaluation - Poonam Parashar; Naresh Diwaker; Jovita Kanoujia; Mahendra Singh; Abhishek Yadav; Indu Singh; Shubhini A. Saraf (Journal of Pharmaceutical Investigation, 2020)

Implication of Coformer Structural Diversity on Cocrystallization Outcomes of Telmisartan with Improved Biopharmaceutical Performance - Jamshed Haneef; Poonam Arora; Renu Chadha (AAPS PharmSciTech, 2020)

Total Phenolic Content and Antioxidant Activity of Meconopsis aculeata Royle: A High Value Medicinal Herb of Himalaya - Amit Bahukhandi; K. Chandra Sekar; Anjali Barola; Monika Bisht; Poonam Mehta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Next generation sequencing, biochemical characterization, metabolic pathway analysis of novel probiotic Pediococcus acidilactici NCDC 252 and it’s evolutionary relationship with other lactic acid bacteria - Poonam Bansal; Raman Kumar; Jasbir Singh; Suman Dhanda (Molecular Biology Reports, 2019)

Seed bacterization stimulated resistance in chickpea against Fusarium oxysporum f. sp. ciceris - Poonam Kumari; Veena Khanna (Indian Phytopathology, 2019)

Investigating the contribution of climate variables to estimates of net primary productivity in a tropical deciduous forest in India - Poonam Tripathi; Mukunda Dev Behera; Soumit K. Behera; Nayan Sahu (Environmental Monitoring and Assessment, 2019)

Establishing a correlation between RIN and A260/280 along with the multivariate evaluation of factors affecting the quality of RNA in cryopreserved cancer bio-specimen - Sanket G. Shah; Mudasir Rashid; Tripti Verma; Madan Ludbe; Bharat Khade; Poonam B. Gera; Sanjay Gupta (Cell and Tissue Banking, 2019)

Co-existence of Leclercia adecarboxylata (LSE-1) and Bradyrhizobium sp. (LSBR-3) in nodule niche for multifaceted effects and profitability in soybean production - K. C. Kumawat; Poonam Sharma; Inderjeet Singh; Asmita Sirari; B. S. Gill (World Journal of Microbiology and Biotechnology, 2019)

Molecular characterization and infectivity analysis of a bipartite begomovirus associated with cotton leaf curl Multan betasatellite naturally infecting Rumex nepalensis in northern India - Dolly Sharma; Aditya Kulshreshtha; Poonam Roshan; Vipin Hallan (Journal of Plant Pathology, 2019)

Characterisation of carrageenan extracted from fresh and defatted red algae along the Pamban coast, Tamilnadu, India - Poonam Chidambaram; Archanadevi Jeyprakash; Pothiraj Chinnathambi (Vegetos, 2019)

Correction to: Endoplasmic Reticulum Stress Plays a Key Role in Rotenone-Induced Apoptotic Death of Neurons - Poonam Goswami; Sonam Gupta; Joyshree Biswas; Neeraj Joshi; Supriya Swarnkar; Chandishwar Nath; Sarika Singh (Molecular Neurobiology, 2019)

Genome analysis provides insight about pathogenesis of Indian strains of Rhizoctonia solani in rice - Srayan Ghosh; Neelofar Mirza; Poonam Kanwar; Kriti Tyagi; Gopaljee Jha (Functional & Integrative Genomics, 2019)

Biodegradation of diuron by endophytic Bacillus licheniformis strain SDS12 and its application in reducing diuron toxicity for green algae - Anil Kumar Singh; Poonam Singla (Environmental Science and Pollution Research, 2019)

Tectona grandis (teak) – A review on its phytochemical and therapeutic potential - Pooja Vyas; Dinesh Kumar Yadav; Poonam Khandelwal (Natural Product Research, 2019)

Delivery of Docetaxel to Brain Employing Piperine-Tagged PLGA-Aspartic Acid Polymeric Micelles: Improved Cytotoxic and Pharmacokinetic Profiles - Anupama Singh; Nagarani Thotakura; Bhupinder Singh; Shikha Lohan; Poonam Negi; Deepak Chitkara; Kaisar Raza (AAPS PharmSciTech, 2019)

Modeling net primary productivity of tropical deciduous forests in North India using bio-geochemical model - Soumit Kumar Behera; Poonam Tripathi; Mukunda Dev Behera; Rakesh Tuli (Biodiversity and Conservation, 2019)

Plant invasion correlation with climate anomaly: an Indian retrospect - Poonam Tripathi; Mukunda Dev Behera; Partha Sarathi Roy (Biodiversity and Conservation, 2019)

Assessment of Biopharmaceutical Performance of Supersaturating Formulations of Carbamazepine in Rats Using Physiologically Based Pharmacokinetic Modeling - Samarth D. Thakore; Poonam Singh Thakur; Ganesh Shete; Rahul Gangwal; Ajit S. Narang; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2019)

Pressurized Metered Dose Inhaler Technology: Manufacturing - Ernest Vallorz; Poonam Sheth; Paul Myrdal (AAPS PharmSciTech, 2019)

First report of potato virus M, potato virus Y and cucumber mosaic virus infection in Solanum nigrum in India - Poonam Chaudhary; Reenu Kumari; Balwinder Singh; Vipin Hallan; Avinash Kaur Nagpal (Journal of Plant Pathology, 2019)

Synergism of Pseudomonas aeruginosa (LSE-2) nodule endophyte with Bradyrhizobium sp. (LSBR-3) for improving plant growth, nutrient acquisition and soil health in soybean - K. C. Kumawat; Poonam Sharma; Asmita Sirari; Inderjeet Singh; B. S. Gill; Ummed Singh; Krishna Saharan (World Journal of Microbiology and Biotechnology, 2019)

RETRACTED ARTICLE: A facile approach for fabricating CD44-targeted delivery of hyaluronic acid-functionalized PCL nanoparticles in urethane-induced lung cancer: Bcl-2, MMP-9, caspase-9, and BAX as potential markers - Poonam Parashar; Chandra Bhushan Tripathi; Malti Arya; Jovita Kanoujia; Mahendra Singh; Abhishek Yadav; Shubhini A. Saraf (Drug Delivery and Translational Research, 2019)

Alterations in plant sugar metabolism: signatory of pathogen attack - Poonam Kanwar; Gopaljee Jha (Planta, 2019)

Indoor inhalation dose assessment for thoron-rich regions of Indian Himalayan belt - Poonam Semwal; Tarun Kumar Agarwal; Kuldeep Singh; Manish Joshi; Gurupad Singh Gusain; Bijay Kumar Sahoo; Rakesh Chand Ramola (Environmental Science and Pollution Research, 2019)

Pectin-encrusted gold nanocomposites containing phytic acid and jacalin: 1,2-dimethylhydrazine-induced colon carcinogenesis in Wistar rats, PI3K/Akt, COX-2, and serum metabolomics as potential targets - Malti Arya; Pooja Singh; Chandra B. Tripathi; Poonam Parashar; Mahendra Singh; Jovita Kanoujia; Anupam Guleria; Gaurav Kaithwas; Krishna P. Gupta; Shubhini A. Saraf (Drug Delivery and Translational Research, 2019)

Response of DNA damage genes in acrolein-treated lung adenocarcinoma cells - Poonam Sarkar (Molecular and Cellular Biochemistry, 2019)

Current Status of Stem Cell Treatment for Type I Diabetes Mellitus - Anupama Kakkar; Ashima Sorout; Mahak Tiwari; Pallavi Shrivastava; Poonam Meena; Sumit Kumar Saraswat; Supriya Srivastava; Rajan Datt; Siddharth Pandey (Tissue Engineering and Regenerative Medicine, 2018)

Symbiotic Parameters, Growth, Nutrient Uptake as Influenced by Biofertilizers under Conservation Agriculture Practices - Harpreet Kaur Virk; Guriqbal Singh; Poonam Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

In vitro propagation, clonal fidelity and phytochemical analysis of Rhodiola imbricata Edgew: a rare trans-Himalayan medicinal plant - Ashwani Kumar Bhardwaj; Baldev Singh; Kulwinder Kaur; Poonam Roshan; Anu Sharma; Dechen Dolker; Avilekh Naryal; Shweta Saxena; Pratap Kumar Pati; Om Prakash Chaurasia (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Real Time Eye Blink Extraction Circuit Design from EEG Signal for ALS Patients - Rakesh Ranjan; Rajeev Arya; Poonam Kshirsagar; Vinay Jain; Deepak K. Jain; Arun Kumar Sangaiah (Journal of Medical and Biological Engineering, 2018)

Protective Role of Mentha arvensis Aqueous Extract against Manganese Induced Toxicity by Reducing Mn Translocation and Promoting Antioxidative Defense in growing Indica Rice Seedlings - Ritika Rajpoot; Anjana Rani; Rajneesh Kumar Srivastava; Poonam Pandey; R. S. Dubey (Journal of Crop Science and Biotechnology, 2018)

Applications of Clinically Relevant Dissolution Testing: Workshop Summary Report - Sandra Suarez-Sharp; Michael Cohen; Filippos Kesisoglou; Andreas Abend; Patrick Marroum; Poonam Delvadia; Evangelos Kotzagiorgis; Min Li; Anna Nordmark; Nagesh Bandi; Erik Sjögren; Andrew Babiskin; et al. (The AAPS Journal, 2018)

Novel screening protocol for precise phenotyping of salt-tolerance at reproductive stage in rice - Krishnendu Chattopadhyay; Amaresh Kumar Nayak; Bishnu Charan Marndi; Annie Poonam; Koushik Chakraborty; Ramani Kumar Sarkar (Physiology and Molecular Biology of Plants, 2018)

Genetic characterization of chikungunya viruses isolated during the 2015-2017 outbreaks in different states of India, based on their E1 and E2 genes - Jayashri Patil; Ashwini More; Poonam Patil; Santosh Jadhav; Priyanka Newase; Megha Agarwal; Sarika Amdekar; C. G. Raut; Deepti Parashar; Sarah S. Cherian (Archives of Virology, 2018)

N-Acetyl-tryptophan glucoside (NATG) protects J774A.1 murine macrophages against gamma radiation-induced cell death by modulating oxidative stress - Poonam Malhotra; Ashutosh K. Gupta; Darshana Singh; Saurabh Mishra; Shravan K. Singh; Raj Kumar (Molecular and Cellular Biochemistry, 2018)

Inosine improves cognitive function and decreases aging-induced oxidative stress and neuroinflammation in aged female rats - Poonam Ruhal; Dinesh Dhingra (Inflammopharmacology, 2018)

QbD-based development of α-linolenic acid potentiated nanoemulsion for targeted delivery of doxorubicin in DMBA-induced mammary gland carcinoma: in vitro and in vivo evaluation - Chandra Bhushan Tripathi; Poonam Parashar; Malti Arya; Mahendra Singh; Jovita Kanoujia; Gaurav Kaithwas; Shubhini A. Saraf (Drug Delivery and Translational Research, 2018)

Continuous measurement of equilibrium equivalent radon/thoron concentration using time-integrated flow-mode grab sampler - Preeti Pant; Tushar Kandari; Mukesh Prasad; Poonam Semwal; R. C. Ramola (Acta Geophysica, 2018)

Study of radon flux and natural radionuclides (226Ra, 232Th and 40K) in the Main Boundary Thrust region of Garhwal Himalaya - Tushar Kandari; Mukesh Prasad; Preeti Pant; Poonam Semwal; Abhay Anand Bourai; Rakesh Chand Ramola (Acta Geophysica, 2018)

Measurement of 222Rn and 220Rn exhalation rate from soil samples of Kumaun Hills, India - Poonam Semwal; Kuldeep Singh; T. K. Agarwal; Manish Joshi; Preeti Pant; Tushar Kandari; R. C. Ramola (Acta Geophysica, 2018)

Genetic analysis of persistency in HF crossbred cattle at an organized farm of northern India - Nisha Sharma; Raman Narang; Neeraj Kashyap; Soni Kumari; Simarjeet Kaur; Poonam Ratwan (Tropical Animal Health and Production, 2018)

Altered microRNA expression signature in Chikungunya-infected mammalian fibroblast cells - Deepti Parashar; Mandar S. Paingankar; Ashwini More; Poonam Patil; Sarika Amdekar (Virus Genes, 2018)

Design, synthesis and pharmacological evaluation of carboxamide and carbothioamide derivatives of 1,3,4-thiadiazole as the inhibitors of acetylcholinesterase and oxipiperazine)ative stress for the management of cognitive debility - Akanksha Kulshreshtha; Poonam Piplani (Medicinal Chemistry Research, 2018)

Infection of potato virus S and M in tomato in North-western India - Poonam Chaudhary; Surender Kumar; Balwinder Singh; Vipin Hallan; Avinash Kaur Nagpal (Journal of Plant Pathology, 2018)

Effects of Formulation Variables on Lung Dosimetry of Albuterol Sulfate Suspension and Beclomethasone Dipropionate Solution Metered Dose Inhalers - Jeffry D. Schroeter; Poonam Sheth; Anthony J. Hickey; Bahman Asgharian; Owen T. Price; Jay T. Holt; Denise S. Conti; Bhawana Saluja (AAPS PharmSciTech, 2018)

Ameliorative Role of Castasterone on Copper Metal Toxicity by Improving Redox Homeostasis in Brassica juncea L. - Poonam Yadav; Ravdeep Kaur; Mukesh Kumar Kanwar; Renu Bhardwaj; Geetika Sirhindi; Leonard Wijaya; M. N. Alyemeni; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2018)

Continuous Column Studies for Water Defluoridation Using Synthesized Magnesium-incorporated Hydroxyapatite Pellets: Experimental and Modeling Studies - Poonam Mondal; Dhiraj Mehta; Virendra Kumar Saharan; Suja George (Environmental Processes, 2018)

Assessment of improved buccal permeation and bioavailability of felodipine microemulsion-based cross-linked polycarbophil gel - Mahendra Singh; Jovita Kanoujia; Poonam Parashar; Malti Arya; Chandra B. Tripathi; V. R. Sinha; Shailendra K. Saraf; Shubhini A. Saraf (Drug Delivery and Translational Research, 2018)

Ecotoxicological effects of microplastics on biota: a review - Sadasivam Anbumani; Poonam Kakkar (Environmental Science and Pollution Research, 2018)

‘Lineaments’ the Potential Groundwater Zones in Hard Rock Area: A Case Study of Basaltic Terrain of WGKKC-2 Watershed from Kalmeswar Tehsil of Nagpur District, Central India - Abhay M. Varade; Y. D. Khare; Poonam Yadav; A. P. Doad; Sandipan Das; Madhura Kanetkar; R. B. Golekar (Journal of the Indian Society of Remote Sensing, 2018)

ω-3 Fatty Acid Synergized Novel Nanoemulsifying System for Rosuvastatin Delivery: In Vitro and In Vivo Evaluation - Chandra Bhushan Tripathi; Neha Gupta; Pranesh Kumar; Ashok Kumar Singh; Vinit Raj; Poonam Parashar; Mahendra Singh; Jovita Kanoujia; Malti Arya; Shubhini A Saraf; Sudipta Saha (AAPS PharmSciTech, 2018)

Persistence, dissipation and consumer risk assessment of a combination formulation of flubendiamide and deltamethrin on cucumber - K.K. Sharma; V. Shashi Bhushan; Cherukuri Sreenivasa Rao; K. Narsimha Reddy; Hemanta Banerjee; Swagata Mandal; Balwinder Singh; R.S. Battu; Gagan Jyot; S.K. Sahoo; Soudamini Mohapatra; S. Lekha; et al. (Food Additives & Contaminants: Part A, 2018)

Castasterone and Citric Acid Supplementation Alleviates Cadmium Toxicity by Modifying Antioxidants and Organic Acids in Brassica juncea - Ravdeep Kaur; Poonam Yadav; Ashwani Kumar Thukral; Anket Sharma; Renu Bhardwaj; Mohammed N. Alyemeni; Leonard Wijaya; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2018)

Cadmium Alters Mitochondrial Membrane Potential, Inhibits Electron Transport Chain Activity and Induces Callose Deposition in Rice Seedlings - Rajneesh Kumar Srivastava; Ritika Rajpoot; Poonam Pandey; Anjana Rani; R. S. Dubey (Journal of Plant Growth Regulation, 2018)

Impact of LULC change on the runoff, base flow and evapotranspiration dynamics in eastern Indian river basins during 1985–2005 using variable infiltration capacity approach - Pulakesh Das; Mukunda Dev Behera; Nitesh Patidar; Bhabagrahi Sahoo; Poonam Tripathi; Priti Ranjan Behera; S K Srivastava; Partha Sarathi Roy; Praveen Thakur; S P Agrawal; Y V N Krishnamurthy (Journal of Earth System Science, 2018)

Transfer Factors and Effective Dose Evaluation Due to Natural Radioactivity in Staple Food Grains from the Vicinity of Proposed Nuclear Power Plant - Poonam Yadav; V. K. Garg; Balvinder Singh; Vandana Pulhani; Suman Mor (Exposure and Health, 2018)

Paired blood cultures increase the sensitivity for detecting pathogens in both inpatients and outpatients - Bansidhar Tarai; Dinesh Jain; Poonam Das; Sandeeep Budhiraja (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Geothermal energy potential of Tulsishyam thermal springs of Gujarat, India - Hemant Kumar Singh; Aswathi Thankappan; Poonam Mohite; Satish Kumar Sinha; Dornadula Chandrasekharam; Trupti Chandrasekhar (Arabian Journal of Geosciences, 2018)

Augmented bioavailability of felodipine through an α-linolenic acid-based microemulsion - Mahendra Singh; Jovita Kanoujia; Poonam Parashar; Malti Arya; Chandra B. Tripathi; V. R. Sinha; Shailendra K. Saraf; Shubhini A. Saraf (Drug Delivery and Translational Research, 2018)

Correction to: Deformability of Human Mesenchymal Stem Cells Is Dependent on Vimentin Intermediate Filaments - Poonam Sharma; Zachary T. Bolten; Diane R. Wagner; Adam H. Hsieh (Annals of Biomedical Engineering, 2018)

Cellular and molecular targets for the immunotherapy of hepatocellular carcinoma - Vikrant Rai; Joe Abdo; Abdullah N. Alsuwaidan; Swati Agrawal; Poonam Sharma; Devendra K. Agrawal (Molecular and Cellular Biochemistry, 2018)

Untapped amaranth (Amaranthus spp.) genetic diversity with potential for nutritional enhancement - Alka Shukla; Nidhi Srivastava; Poonam Suneja; Shiv K. Yadav; Zakir Hussain; J. C. Rana; Sangita Yadav (Genetic Resources and Crop Evolution, 2018)

Identification of host cellular targets of AC4 and AV2 proteins of tomato leaf curl palampur virus and their sub-cellular localization studies - Poonam Roshan; Aditya Kulshreshtha; Vipin Hallan (VirusDisease, 2017)

Antioxidant and Antibacterial Activities of Sugarcane Bagasse Lignin and Chemically Modified Lignins - Ramandeep Kaur; S. K. Uppal; Poonam Sharma (Sugar Tech, 2017)

Assessment of Century Plant (Agave americana) for Remediation of Chromium Contaminated Soils - Sivakoti Ramana; Sanjay Srivastava; Ashis K. Biswas; Ajay Kumar; Amar B. Singh; Dashrath Singh; Poonam S. Rajput (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Multifaceted Rhizobacteria-Mediated Growth Augmentation in Chickpea - Poonam Kumari; Veena Khanna; Prafull Kumar (Agricultural Research, 2017)

Consequences of copper treatment on pigeon pea photosynthesis, osmolytes and antioxidants defense - Poonam Sharma; Geetika Sirhindi; Anil Kumar Singh; Harpreet Kaur; Ruqia Mushtaq (Physiology and Molecular Biology of Plants, 2017)

28-Homobrassinolide potential for oxidative interface in Brassica juncea under temperature stress - Geetika Sirhindi; Harpreet Kaur; Renu Bhardwaj; Poonam Sharma; Ruquia Mushtaq (Acta Physiologiae Plantarum, 2017)

Investigation of Need of Natural Bioenhancer for a Metabolism Susceptible Drug—Raloxifene, in a Designed Self-Emulsifying Drug Delivery System - Poonam Singh Thakur; Narinder Singh; Abhay T. Sangamwar; Arvind Kumar Bansal (AAPS PharmSciTech, 2017)

Influence of Formulation Factors on the Aerosol Performance of Suspension and Solution Metered Dose Inhalers: A Systematic Approach - Poonam Sheth; Dennis Sandell; Denise S. Conti; Jay T. Holt; Anthony J. Hickey; Bhawana Saluja (The AAPS Journal, 2017)

Morpho-physiological and transcriptome profiling reveal novel zinc deficiency-responsive genes in rice - Tirthankar Bandyopadhyay; Poonam Mehra; Suboot Hairat; Jitender Giri (Functional & Integrative Genomics, 2017)

Efficient synthesis and antimicrobial evaluation of 2-((1-substituted-1H-1,2,3-triazol-4-yl)-1-naphthaldehydes and their oxime derivatives - Pinki Yadav; Kashmiri Lal; Poonam Rani; Satbir Mor; Ashwani Kumar; Anil Kumar (Medicinal Chemistry Research, 2017)

Molecular characterization of a new begomovirus infecting Mirabilis jalapa in northern India - Aditya Kulshreshtha; Poonam Roshan; Dolly Sharma; Vipin Hallan (Archives of Virology, 2017)

Stabilization of tannery sludge amended soil using Ricinus communis, Brassica juncea and Nerium oleander - Poonam Rani; Adarsh Kumar; Ramesh Chandra Arya (Journal of Soils and Sediments, 2017)

Novel LC–MS/MS method for estimation of niacin with negligible matrix effect and its application to the BE study - Poonam Vats; S. Manaswita Verma; Tausif Monif (Journal of Pharmaceutical Investigation, 2017)

Deformability of Human Mesenchymal Stem Cells Is Dependent on Vimentin Intermediate Filaments - Poonam Sharma; Zachary T. Bolten; Diane R. Wagner; Adam H. Hsieh (Annals of Biomedical Engineering, 2017)

Estimation of Mineral and Trace Element Profile in Bubaline Milk Affected with Subclinical Mastitis - Mahavir Singh; Poonam Yadav; Anshu Sharma; V.K. Garg; Dinesh Mittal (Biological Trace Element Research, 2017)

Delivery of Thermoresponsive-Tailored Mixed Micellar Nanogel of Lidocaine and Prilocaine with Improved Dermatokinetic Profile and Therapeutic Efficacy in Topical Anaesthesia - Gajanand Sharma; Shelly Kamboj; Kanika Thakur; Poonam Negi; Kaisar Raza; O. P. Katare (AAPS PharmSciTech, 2017)

Biological Control of Fusarium sp. NBRI-PMSF12 Pathogenic to Cultivated Betelvine by Bacillus sp. NBRI-W9, a Potential Biological Control Agent - Poonam C. Singh; Deepali Shukla; Touseef Fatima; Chandra Shekhar Nautiyal; Jayandra Kumar Johri (Journal of Plant Growth Regulation, 2017)

Sensitive LC-MS/MS Method for the Determination of Ramipril in Human Plasma: Application to a Bioequivalence Study in Indian Volunteers - Arabinda Saha; Poonam Vats; Sanjay Jagannath Gurule; Arshad Khuroo (Journal of Pharmaceutical Innovation, 2017)

A Successive Application Approach for Effective Utilization of Three Aquatic Plants in Arsenic Removal - Poonam; Munish Kumar Upadhyay; Ambedkar Gautam; Shekhar Mallick; Sudhakar Srivastava (Water, Air, & Soil Pollution, 2017)

Genome Sequence of Microbulbifer mangrovi DD-13T Reveals Its Versatility to Degrade Multiple Polysaccharides - Md. Imran; Poonam Pant; Yogini P. Shanbhag; Samir V. Sawant; Sanjeev C. Ghadi (Marine Biotechnology, 2017)

Sibling Drosophila species (Drosophila leontia and Drosophila kikkawai) show divergence for thermotolerance along a latitudinal gradient - Poonam Ranga; Ravi Prakash; Nirotpal Mrinal (Evolutionary Ecology, 2017)

Wound healing applications of sericin/chitosan-capped silver nanoparticles incorporated hydrogel - Jyoti Verma; Jovita Kanoujia; Poonam Parashar; Chandra Bhusan Tripathi; Shubhini A. Saraf (Drug Delivery and Translational Research, 2017)

Relevance of mouse models of cardiac fibrosis and hypertrophy in cardiac research - Vikrant Rai; Poonam Sharma; Swati Agrawal; Devendra K. Agrawal (Molecular and Cellular Biochemistry, 2017)

Synthesis, Optical Investigation and Biological Properties of Europium(III) Complexes with 2-(4-Chlorophenyl)-1-(2-Hydroxy-4-Methoxyphenyl)Ethan-1-one and Ancillary Ligands - Poonam Nandal; S. P. Khatkar; Rajesh Kumar; Avni Khatkar; V. B. Taxak (Journal of Fluorescence, 2017)

Co-application of 6-ketone type brassinosteroid and metal chelator alleviates cadmium toxicity in B. juncea L. - Ravdeep Kaur; Poonam Yadav; Ashwani Kumar Thukral; Amandeep Walia; Renu Bhardwaj (Environmental Science and Pollution Research, 2017)

Breeding Potential of Potato Somatic Hybrids: Evaluations for Adaptability, Tuber Traits, Late Blight Resistance, Keeping Quality and Backcross (BC1) Progenies - Satish Kumar Luthra; Jagesh Kumar Tiwari; Mehi Lal; Poonam Chandel; Vinod Kumar (Potato Research, 2016)

Terminalia arjuna bark extract alleviates nickel toxicity by suppressing its uptake and modulating antioxidative defence in rice seedlings - Ritika Rajpoot; Anjana Rani; Rajneesh Kumar Srivastava; Poonam Pandey; R. S. Dubey (Protoplasma, 2016)

DADS Analogues Ameliorated the Cognitive Impairments of Alzheimer-Like Rat Model Induced by Scopolamine - Apra Manral; Poonam Meena; Vikas Saini; Fouzia Siraj; Shruti Shalini; Manisha Tiwari (Neurotoxicity Research, 2016)

Endoplasmic Reticulum Stress Instigates the Rotenone Induced Oxidative Apoptotic Neuronal Death: a Study in Rat Brain - Poonam Goswami; Sonam Gupta; Joyshree Biswas; Sharad Sharma; Sarika Singh (Molecular Neurobiology, 2016)

Strategic synthesis and in vitro antimicrobial evaluation of novel difluoromethylated 1-(1, 3-diphenyl-1H-pyrazol-4-yl)-3, 3-difluoro-1, 3-dihydro-indol-2-ones - Tejpal Singh Chundawat; Poonam Kumari; Nutan Sharma; Sunita Bhagat (Medicinal Chemistry Research, 2016)

Genetic diversity in groundnut (Arachis hypogaea L.) genotypes and detection of marker trait associations for plant habit and seed size using genomic and genic SSRs - Poonam G. Bhad; Suvendu Mondal; Anand M. Badigannavar (Journal of Crop Science and Biotechnology, 2016)

Streptozotocin Induced Neurotoxicity Involves Alzheimer’s Related Pathological Markers: a Study on N2A Cells - Joyshree Biswas; Poonam Goswami; Sonam Gupta; Neeraj Joshi; Chandishwar Nath; Sarika Singh (Molecular Neurobiology, 2016)

Genome-wide characterization and expression profiling of TIFY gene family in pigeonpea (Cajanus cajan (L.) Millsp.) under copper stress - Geetika Sirhindi; Poonam Sharma; Preeti Arya; Parul Goel; Gulshan Kumar; Vishal Acharya; Anil Kumar Singh (Journal of Plant Biochemistry and Biotechnology, 2016)

Prostaglandin analogues: current treatment option for glaucoma - Poonam Piplani; Deepali Aggarwal; Vasudha Abbhi; Lovneet Saini (Medicinal Chemistry Research, 2016)

Regulatory Perspectives on Strength-Dependent Dissolution Profiles and Biowaiver Approaches for Immediate Release (IR) Oral Tablets in New Drug Applications - Sandra Suarez-Sharp; Poonam R. Delvadia; Angelica Dorantes; John Duan; Anna Externbrink; Zongming Gao; Tapash Ghosh; Sarah Pope Miksinski; Paul Seo (The AAPS Journal, 2016)

Therapeutic Effect of Cereal Grains: A Review - Poonam Singhal; Geetanjali Kaushik (Critical Reviews in Food Science and Nutrition, 2016)

Organelle Genome Analysis in Somatic Hybrids Between Solanum tuberosum and S. pinnatisectum Revealed Diverse Cytoplasm Type in Potato - Jagesh Kumar Tiwari; Sapna Devi; Poonam Chandel; Nilofer Ali; Vinay Bhardwaj; Bir Pal Singh (Agricultural Research, 2016)

Endoplasmic Reticulum Stress Plays a Key Role in Rotenone-Induced Apoptotic Death of Neurons - Poonam Goswami; Sonam Gupta; Joyshree Biswas; Neeraj Joshi; Supriya Swarnkar; Chandishwar Nath; Sarika Singh (Molecular Neurobiology, 2016)

A single gene all3940 (Dps) overexpression in Anabaena sp. PCC 7120 confers multiple abiotic stress tolerance via proteomic alterations - Om Prakash Narayan; Nidhi Kumari; Poonam Bhargava; Hema Rajaram; Lal Chand Rai (Functional & Integrative Genomics, 2016)

Water deficit and aluminum interactive effects on generation of reactive oxygen species and responses of antioxidative enzymes in the seedlings of two rice cultivars differing in stress tolerance - Poonam Pandey; Rajneesh Kumar Srivastava; Ritika Rajpoot; Anjana Rani; Akhilesh Kumar Pandey; R. S. Dubey (Environmental Science and Pollution Research, 2016)

Hypoxia-Induced Inflammatory Chemokines in Subjects with a History of High-Altitude Pulmonary Edema - K. P. Mishra; Navita Sharma; Poonam Soree; R. K. Gupta; Lilly Ganju; S. B. Singh (Indian Journal of Clinical Biochemistry, 2016)

Contraceptive studies of isolated fractions of Cuminum cyminum in male albino rats - Poonam Saxena; Rajnish Gupta; R.S. Gupta (Natural Product Research, 2015)

Comparative Study of Chemical Pretreatments and Acid Saccharification of Bagasse of Sugar Crops for Ethanol Production - Pushpinder Kaur; S. K. Uppal; Chandni Dhir; Poonam Sharma; Ramandeep Kaur (Sugar Tech, 2015)

Bioprospecting and molecular characterization of laccase producing bacteria from paper mills of Himachal Pradesh - Karuna Dhiman; Poonam Shirkot (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Interspecific potato somatic hybrids between Solanum tuberosum and S. cardiophyllum, potential sources of late blight resistance breeding - Poonam Chandel; Jagesh Kumar Tiwari; Nilofer Ali; Sapna Devi; Shashi Sharma; Sanjeev Sharma; Satish Kumar Luthra; Bir Pal Singh (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Analysis of Genetic and Epigenetic Changes in Potato Somatic Hybrids Between Solanum tuberosum and S. etuberosum by AFLP and MSAP Markers - Jagesh Kumar Tiwari; Shaumaya Saurabh; Poonam Chandel; Sapna Devi; Nilofer Ali; Chandra Mohan Bist; Bir Pal Singh (Agricultural Research, 2015)

Allele Mining in Solanum Germplasm: Cloning and Characterization of RB-Homologous Gene Fragments from Late Blight Resistant Wild Potato Species - Jagesh Kumar Tiwari; Sapna Devi; Sanjeev Sharma; Poonam Chandel; Shashi Rawat; Bir Pal Singh (Plant Molecular Biology Reporter, 2015)

Modulatory role of jasmonic acid on photosynthetic pigments, antioxidants and stress markers of Glycine max L. under nickel stress - Geetika Sirhindi; Mudaser Ahmad Mir; Poonam Sharma; Sarvajeet Singh Gill; Harpreet Kaur; Ruquia Mushtaq (Physiology and Molecular Biology of Plants, 2015)

Morin mitigates acetaminophen-induced liver injury by potentiating Nrf2 regulated survival mechanism through molecular intervention in PHLPP2-Akt-Gsk3β axis - Fatima Rizvi; Alpana Mathur; Poonam Kakkar (Apoptosis, 2015)

Bioprospecting of Thermotolerant Bacteria from Hot Water Springs of Himachal Pradesh for the Production of Taq DNA Polymerase - Ambika Verma; Karuna Dhiman; Monika Gupta; Poonam Shirkot (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

In Vitro and In Vivo Efficacy of Self-Assembling RGD Peptide Amphiphiles for Targeted Delivery of Paclitaxel - Poonam Saraf; Xiaoling Li; Lisa Wrischnik; Bhaskara Jasti (Pharmaceutical Research, 2015)

A snapshot of microbial communities from the Kutch: one of the largest salt deserts in the World - Aanal S. Pandit; Madhvi N. Joshi; Poonam Bhargava; Inayatullah Shaikh; Garima N. Ayachit; Sandeep R. Raj; Akshay K. Saxena; Snehal B. Bagatharia (Extremophiles, 2015)

Removal of Fluoride from Drinking Water Using Novel Adsorbent Magnesia-Hydroxyapatite - Poonam Mondal; Suja George (Water, Air, & Soil Pollution, 2015)

Exogenous application of calcium and silica alleviates cadmium toxicity by suppressing oxidative damage in rice seedlings - Rajneesh Kumar Srivastava; Poonam Pandey; Ritika Rajpoot; Anjana Rani; Arti Gautam; R. S. Dubey (Protoplasma, 2015)

Bioaugmentation of Mesorhizobium cicer, Pseudomonas spp. and Piriformospora indica for Sustainable Chickpea Production - Pallavi Mansotra; Poonam Sharma; Sunita Sharma (Physiology and Molecular Biology of Plants, 2015)

Click chemistry inspired synthesis of piperazine-triazole derivatives and evaluation of their antimicrobial activities - Poonam Khedar; Kasiviswanadharaju Pericherla; Rajnish Prakash Singh; Prabhat Nath Jha; Anil Kumar (Medicinal Chemistry Research, 2015)

Estimation of Aboveground Phytomass of Plantations Using Digital Photogrammetry and High Resolution Remote Sensing Data - Sujata Upgupta; Sarnam Singh; Poonam S. Tiwari (Journal of the Indian Society of Remote Sensing, 2015)

A review on adsorbents used for defluoridation of drinking water - Poonam Mondal; Suja George (Reviews in Environmental Science and Bio/Technology, 2015)

Influence of β-cyclodextrin on the Properties of Norfloxacin Form A - Lucas Chierentin; Claudia Garnero; Ana Karina Chattah; Poonam Delvadia; Thomas Karnes; Marcela Raquel Longhi; Hérida Regina Nunes Salgado (AAPS PharmSciTech, 2015)

Protective Effects of a Piperazine Derivative [N-{4-[4-(2-methoxy-phenyl)-piperazin-1-yl]-phenyl} Carbamic Acid Ethyl Ester] Against Aluminium-Induced Neurotoxicity: Insights From In Silico and In Vivo Studies - Poonam Meena; Apra Manral; Vikas Saini; Manisha Tiwari (Neurotoxicity Research, 2015)

Inhibition of Neuroinflammation and Mitochondrial Dysfunctions by Carbenoxolone in the Rotenone Model of Parkinson’s Disease - Poonam Thakur; Bimla Nehru (Molecular Neurobiology, 2015)

Factors Influencing Aerodynamic Particle Size Distribution of Suspension Pressurized Metered Dose Inhalers - Poonam Sheth; Stephen W. Stein; Paul B. Myrdal (AAPS PharmSciTech, 2015)

Weighted morphology: a new approach towards phylogenetic assessment of Nostocales (Cyanobacteria) - Swati Mishra; Poonam Bhargava; Siba Prasad Adhikary; Anubhav Pradeep; Lal Chand Rai (Protoplasma, 2015)

Quantitative structure–activity relationship (QSAR) studies as strategic approach in drug discovery - Harun M. Patel; Malleshappa N. Noolvi; Poonam Sharma; Varun Jaiswal; Sumit Bansal; Sandeep Lohan; Suthar Sharad Kumar; Vikrant Abbot; Saurabh Dhiman; Varun Bhardwaj (Medicinal Chemistry Research, 2014)

Exploring Pellet Forming Filamentous Fungi as Tool for Harvesting Non-flocculating Unicellular Microalgae - Sanjeev Kumar Prajapati; Pushpendar Kumar; Anushree Malik; Poonam Choudhary (BioEnergy Research, 2014)

Upscaling of leaf area index in Terai forest plantations using fine- and moderate-resolution satellite data - Poonam Tripathi; N.R. Patel; S.P.S. Kushwaha; V.K. Dadhwal (International Journal of Remote Sensing, 2014)

Lactobacillus acidophilus Protected Organs in Experimental Arthritis by Regulating the Pro-inflammatory Cytokines - Sarika Amdekar; Vinod Singh; Avnish Kumar; Poonam Sharma; Rambir Singh (Indian Journal of Clinical Biochemistry, 2014)

Spectral delineation of albite zone using ASTER data in Khetri Copper Belt - Poonam S. Tiwari; R. D. Garg; A. K. Sen; V. K. Dadhwal (Arabian Journal of Geosciences, 2014)

Cadmium and lead interactive effects on oxidative stress and antioxidative responses in rice seedlings - Rajneesh Kumar Srivastava; Poonam Pandey; Ritika Rajpoot; Anjana Rani; R. S. Dubey (Protoplasma, 2014)

Analysis of Differentially Expressed Genes Involved in Stevioside Biosynthesis in Cultures of Stevia Rebaudiana Bertoni Treated with Steviol as an Immediate Precursor - Arpan R. Modi; Sandip Raj; Poonam Kanani; Armi Patel; Subhash Narayanan (Journal of Plant Growth Regulation, 2014)

Does malaria epidemiology project Cameroon as ‘Africa in miniature’? - Huguette Gaelle Ngassa Mbenda; Gauri Awasthi; Poonam K Singh; Inocent Gouado; Aparup Das (Journal of Biosciences, 2014)

Sequence heterogeneity in human immunodeficiency virus type 1 nef in patients presenting with rapid progression and delayed progression to AIDS - Poonam Gupta; Mohammad Husain; Charoo Hans; Hanu Ram; Supriya Singh Verma; Mohammad Misbah; L. S. Chauhan; Arvind Rai (Archives of Virology, 2014)

Metagenomics of petroleum muck: revealing microbial diversity and depicting microbial syntrophy - Madhvi N. Joshi; Shivangi V. Dhebar; Shivani V. Dhebar; Poonam Bhargava; Aanal Pandit; Riddhi P. Patel; Akshay Saxena; Snehal B. Bagatharia (Archives of Microbiology, 2014)

Isolation and HPLC method development of azafrin from Alectra parasitica var. chitrakutensis - Poonam Agrawal; Kirti Laddha; Ashok Tiwari (Natural Product Research, 2014)

Advances in Metered Dose Inhaler Technology: Formulation Development - Paul B. Myrdal; Poonam Sheth; Stephen W. Stein (AAPS PharmSciTech, 2014)

Advances in Metered Dose Inhaler Technology: Hardware Development - Stephen W. Stein; Poonam Sheth; P. David Hodson; Paul B. Myrdal (AAPS PharmSciTech, 2014)

Heavy Metals Bioconcentration from Soil to Vegetables and Assessment of Health Risk Caused by Their Ingestion - V. K. Garg; Poonam Yadav; Suman Mor; Balvinder Singh; Vandana Pulhani (Biological Trace Element Research, 2014)

Schizophillum commune Causing Sinusitis with Nasal Polyposis in the Sub-Himalayan Region: First Case Report and Review - Santwana Verma; Poonam Gupta; Digvijay Singh; Anil Kanga; N. K. Mohindroo; Anupam Jhobta (Mycopathologia, 2014)

Antidiabetic Potential of Commonly Consumed Legumes: A Review - Poonam Singhal; Geetanjali Kaushik; Pulkit Mathur (Critical Reviews in Food Science and Nutrition, 2014)

Water deficit and aluminum tolerance are associated with a high antioxidative enzyme capacity in Indica rice seedlings - Poonam Pandey; Rajneesh Kumar Srivastava; R. S. Dubey (Protoplasma, 2014)

Emergence of drug resistance-associated mutations in HIV-1 subtype C protease gene in north India - Mohd Azam; Abida Malik; Meher Rizvi; Supriya Singh; Poonam Gupta; Arvind Rai (Virus Genes, 2013)

Analysis of genetic stability of in vitro propagated potato microtubers using DNA markers - Jagesh K. Tiwari; Poonam Chandel; Shruti Gupta; Jai Gopal; B. P. Singh; Vinay Bhardwaj (Physiology and Molecular Biology of Plants, 2013)

Reduced cell wall degradation plays a role in cow dung-mediated management of wilt complex disease of chickpea - Chandra Shekhar Nautiyal; Suchi Srivastava; Sandhya Mishra; Mehar Hasan Asif; Puneet Singh Chauhan; Poonam C. Singh; Pravendra Nath (Biology and Fertility of Soils, 2013)

Cloning and Sequence Analysis of Three Variants of the Gene Encoding Alkaline Xylanase C from the Alkaliphilic Bacillus sp. (NCL 87-6-10) - Poonam Sharma; Meenakshi V. Rele; Lalitha Sunil Kumar (Biochemical Genetics, 2013)

Chemical Composition of Sweet Sorghum Juice and its Comparative Potential of Different Fermentation Processes for Enhanced Ethanol Production - Yuvraj; Ramandeep Kaur; S. K. Uppal; Poonam Sharma; Harinder Singh Oberoi (Sugar Tech, 2013)

In vitro cytotoxicity, antimicrobial, and metal-chelating activity of triterpene saponins from tea seed grown in Kangra valley, India - Robin Joshi; Swati Sood; Poonam Dogra; Madhvi Mahendru; Dharmesh Kumar; Shalika Bhangalia; Harish Chandra Pal; Neeraj Kumar; Shashi Bhushan; Arvind Gulati; Ajit Kumar Saxena; Ashu Gulati (Medicinal Chemistry Research, 2013)

Synthesis and comparative bioefficacy of N-(1-phenethyl-4-piperidinyl)propionanilide (fentanyl) and its 1-substituted analogs in Swiss albino mice - Pradeep Kumar Gupta; Shiv Kumar Yadav; Yangchen Doma Bhutia; Poonam Singh; Pooja Rao; Niranjan Laxman Gujar; Kumaran Ganesan; Rahul Bhattacharya (Medicinal Chemistry Research, 2013)

Trichoderma: a potential bioremediator for environmental clean up - Pratibha Tripathi; Poonam C. Singh; Aradhana Mishra; Puneet S. Chauhan; Sanjay Dwivedi; Ritu Thakur Bais; Rudra Deo Tripathi (Clean Technologies and Environmental Policy, 2013)

MYB transcription factor genes as regulators for plant responses: an overview - Supriya Ambawat; Poonam Sharma; Neelam R. Yadav; Ram C. Yadav (Physiology and Molecular Biology of Plants, 2013)

Water quality analysis of surface water: a Web approach - Poonam Prasad; Meenal Chaurasia; R. A. Sohony; Indrani Gupta; R. Kumar (Environmental Monitoring and Assessment, 2013)

On rising temperature trends at Dehradun in Doon valley of Uttarakhand, India - OMVIR SINGH; POONAM ARYA; BHAGWAN SINGH CHAUDHARY (Journal of Earth System Science, 2013)

Salicylic acid alleviates aluminum toxicity in rice seedlings better than magnesium and calcium by reducing aluminum uptake, suppressing oxidative damage and increasing antioxidative defense - Poonam Pandey; Rajneesh Kumar Srivastava; R. S. Dubey (Ecotoxicology, 2013)

Palynostratigraphy and depositional environment of Vastan Lignite Mine (Early Eocene), Gujarat, western India - M R RAO; ASHOK SAHNI; R S RANA; POONAM VERMA (Journal of Earth System Science, 2013)

Divergence of water balance mechanisms in two sibling species (Drosophila simulans and D. melanogaster): effects of growth temperatures - Ravi Parkash; Dau Dayal Aggarwal; Divya Singh; Chanderkala Lambhod; Poonam Ranga (Journal of Comparative Physiology B, 2013)

Mapping of fluoride endemic area and assessment of F−1 accumulation in soil and vegetation - Poonam Saini; Suphiya Khan; Mamta Baunthiyal; Vinay Sharma (Environmental Monitoring and Assessment, 2013)

Bamboo Shoots: A Novel Source of Nutrition and Medicine - Poonam Singhal; Lalit Mohan Bal; Santosh Satya; P. Sudhakar; S. N. Naik (Critical Reviews in Food Science and Nutrition, 2013)

Naringenin prevents high glucose-induced mitochondria-mediated apoptosis involving AIF, Endo-G and caspases - Radhika Kapoor; Fatima Rizvi; Poonam Kakkar (Apoptosis, 2013)

Photocatalytic Degradation of Cuprous Oxide Nanostructures Under UV/Visible Irradiation - Poonam Sharma; Shatendra K. Sharma (Water Resources Management, 2012)

Fatty Acid–RGD Peptide Amphiphile Micelles as Potential Paclitaxel Delivery Carriers to αvβ3Integrin Overexpressing Tumors - Narashima Murthy Javali; April Raj; Poonam Saraf; Xiaoling Li; Bhaskara Jasti (Pharmaceutical Research, 2012)

Antifertility activity of methanolic bark extract of Aegle marmelos (l.) in male wistar rats - Shyam S Agrawal; Ashok Kumar; Sumeet Gullaiya; Vishal Dubey; Ashish Nagar; Poonam Tiwari; Parul Dhar; Varun Singh (DARU Journal of Pharmaceutical Sciences, 2012)

Effect of nonlinear soil-structure interaction on seismic response of low-rise SMRF buildings - Prishati Raychowdhury; Poonam Singh (Earthquake Engineering and Engineering Vibration, 2012)

Multifaceted attributes of dairy propionibacteria: a review - Poonam; Sarang Dilip Pophaly; Sudhir Kumar Tomar; Sachinandan De; Rameshwar Singh (World Journal of Microbiology and Biotechnology, 2012)

Molecular docking and receptor-specific 3D-QSAR studies of acetylcholinesterase inhibitors - Pran Kishore Deb; Anuradha Sharma; Poonam Piplani; Raghuram Rao Akkinepally (Molecular Diversity, 2012)

Synthesis and antimicrobial activity of 5-((3-aryl-1-phenyl-1H-pyrazol-4-yl)methylene)thiazolidine-2,4-diones - Om Prakash; Deepak K. Aneja; Poonam Lohan; Khalid Hussain; Sanjiv Arora; Chetan Sharma; Kamal R. Aneja (Medicinal Chemistry Research, 2012)

Assessment of the interactive effects of ambient O3 and NPK levels on two tropical mustard varieties (Brassica campestris L.) using open-top chambers - Poonam Singh; Shalini Singh; S. B. Agrawal; Madhoolika Agrawal (Environmental Monitoring and Assessment, 2012)

Bamboo Shoot Preservation for Enhancing its Business Potential and Local Economy: A Review - Lalit M. Bal; Poonam Singhal; Santosh Satya; S. N. Naik; Abhijit Kar (Critical Reviews in Food Science and Nutrition, 2012)

Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Neha Gupta; Poonam Sharma; R. J. Santosh Kumar; Rishi K. Vishwakarma; B. M. Khan (Molecular Biology Reports, 2012)

Lactobacillus protected bone damage and maintained the antioxidant status of liver and kidney homogenates in female wistar rats - Sarika Amdekar; Avnish Kumar; Poonam Sharma; Rambir Singh; Vinod Singh (Molecular and Cellular Biochemistry, 2012)

Molecular analysis of gut microbiota in obesity among Indian individuals - Deepak P Patil; Dhiraj P Dhotre; Sachin G Chavan; Armiya Sultan; Dhawal S Jain; Vikram B Lanjekar; Jayshree Gangawani; Poonam S Shah; Jayshree S Todkar; Shashank Shah; Dilip R Ranade; Milind S Patole; et al. (Journal of Biosciences, 2012)

Rotenone-induced apoptosis and role of calcium: a study on Neuro-2a cells - Supriya Swarnkar; Poonam Goswami; Pradeep Kumar Kamat; Sonam Gupta; Ishan K. Patro; Sarika Singh; Chandishwar Nath (Archives of Toxicology, 2012)

Synthesis and pharmacological evaluation of some new naphthol derived aryloxy derivatives as cognition enhancers - Poonam Piplani; Ruchi Malik; Bhavneet Kaur; Anuradha Kaplish (Medicinal Chemistry Research, 2012)

Divergent strategies for adaptation to desiccation stress in two Drosophila species of immigrans group - Ravi Parkash; Dau Dayal Aggarwal; Poonam Ranga; Divya Singh (Journal of Comparative Physiology B, 2012)

Divergence of larval resource acquisition for water conservation and starvation resistance in Drosophila melanogaster - Ravi Parkash; Dau Dayal Aggarwal; Poonam Ranga; Divya Singh (Journal of Comparative Physiology B, 2012)

Provenance of the Late Neogene Siwalik sandstone, Kumaun Himalayan Foreland Basin: Constraints from the metamorphic rank and index of detrital rock fragments - POONAM JALAL; SUMIT K GHOSH (Journal of Earth System Science, 2012)

Increase in growth, productivity and nutritional status of rice (Oryza sativa L. cv. Basmati) and enrichment in soil fertility applied with an organic matrix entrapped urea - Manoj Kumar; Kuldeep Bauddh; Manish Sainger; Poonam Ahlawat Sainger; Jay Shankar Singh; Rana Pratap Singh (Journal of Crop Science and Biotechnology, 2012)

Effect of Dietary Supplementation of Organic Chromium on Performance, Carcass Traits, Oxidative Parameters, and Immune Responses in Commercial Broiler Chickens - S. V. Rama Rao; M. V. L. N. Raju; A. K. Panda; N. S. Poonam; O. Krishna Murthy; G. Shyam Sunder (Biological Trace Element Research, 2012)

Semi-quantitative RT-PCR analysis of fat metabolism genes in mammary tissue of lactating and non-lactating water buffalo (Bubalus bubalis) - Poonam Yadav; Manishi Mukesh; Ranjit Singh Kataria; Anita Yadav; Ashok Kumar Mohanty; Bishnu Prasad Mishra (Tropical Animal Health and Production, 2012)

Genetics of flowering time in bread wheat Triticum aestivum: complementary interaction between vernalization-insensitive and photoperiod-insensitive mutations imparts very early flowering habit to spring wheat - SUSHIL KUMAR; VISHAKHA SHARMA; SWATI CHAUDHARY; ANSHIKA TYAGI; POONAM MISHRA; ANUPAMA PRIYADARSHINI; ANUPAM SINGH (Journal of Genetics, 2012)

Identification of Fibrinogen-Binding Proteins of Aspergillus fumigatus Using Proteomic Approach - Santosh Kumar Upadhyay; Poonam Gautam; Hrishikesh Pandit; Yogendra Singh; Seemi Farhat Basir; Taruna Madan (Mycopathologia, 2012)

Spherulites and thundereggs from pitchstones of the Deccan Traps: geology, petrochemistry, and emplacement environments - Pooja V. Kshirsagar; Hetu C. Sheth; Sheila J. Seaman; Badrealam Shaikh; Poonam Mohite; Trupti Gurav; D. Chandrasekharam (Bulletin of Volcanology, 2012)

Seasonal Trends of PM2.5 and PM10 in Ambient Air and Their Correlation in Ambient Air of Lucknow City, India - Poonam Pandey; Altaf Husain Khan; Ambrish Kumar Verma; Kunwar Anand Singh; Neeraj Mathur; Ganesh Chandra Kisku; Shyamal Chandra Barman (Bulletin of Environmental Contamination and Toxicology, 2012)

Study of C-Reactive Protein and Myocardial Infarction in the Indian Population - Kavita Shalia; Sudha Savant; Vijaya A. Haldankar; Tulip Nandu; Poonam Pawar; Siddhi Divekar; V. K. Shah; Purvi Bhatt (Indian Journal of Clinical Biochemistry, 2012)

Production and characterization of somatic hybrids between Solanum tuberosum L. and S. pinnatisectum Dun. - D. Sarkar; Jagesh K. Tiwari; Sushruti Sharma; Poonam; Sanjeev Sharma; J. Gopal; B. P. Singh; S. K. Luthra; S. K. Pandey; D. Pattanayak (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Modeling of novel HIV-1 protease inhibitors incorporating N-Aryl-oxazolidinone-5-carboxamides as P2 ligands using quantum chemical and topological finger print descriptors - Shalini Singh; Sarika Singh; Poonam Shukla (Medicinal Chemistry Research, 2011)

Transcriptomic and Proteomic Profile of Aspergillus fumigatus on Exposure to Artemisinin - Poonam Gautam; Santosh Kumar Upadhyay; Wazid Hassan; Taruna Madan; Ravi Sirdeshmukh; Curam Sreenivasacharlu Sundaram; Wasudev Namdeo Gade; Seemi Farhat Basir; Yogendra Singh; Puranam Usha Sarma (Mycopathologia, 2011)

Alteration in mitochondrial thiol enhances calcium ion dependent membrane permeability transition and dysfunction in vitro: a cross-talk between mtThiol, Ca2+, and ROS - Brijesh Kumar Singh; Madhulika Tripathi; Pramod Kumar Pandey; Poonam Kakkar (Molecular and Cellular Biochemistry, 2011)

Optimization of Chemical Pretreatment and Acid Saccharification for Conversion of Sugarcane Bagasse to Ethanol - S. K. Uppal; Ramandeep Kaur; Poonam Sharma (Sugar Tech, 2011)

Interaction between COCHLEATA and UNIFOLIATA genes enables normal flower morphogenesis in the garden pea, Pisum sativum - SUSHIL KUMAR; VISHAKHA SHARMA; SWATI CHAUDHARY; RENU KUMARI; NISHA KUMARI; POONAM MISHRA (Journal of Genetics, 2011)

Onset of Darcy–Brinkman Ferroconvection in a Rotating Porous Layer Using a Thermal Non-Equilibrium Model: A Nonlinear Stability Analysis - Sunil; Poonam Sharma; Amit Mahajan (Transport in Porous Media, 2011)

In Vitro Sensitivity of Rhizobium and Phosphate Solubilising Bacteria to Herbicides - Jeenie; Poonam Sharma; Veena Khanna (Indian Journal of Microbiology, 2011)

Differences in Ozone Sensitivity at Different NPK Levels of Three Tropical Varieties of Mustard (Brassica campestris L.): Photosynthetic Pigments, Metabolites, and Antioxidants - Poonam Singh; Madhoolika Agrawal; Shashi Bhushan Agrawal (Water, Air, & Soil Pollution, 2011)

Molecular and morphological characterization of somatic hybrids between Solanum tuberosum L. and S. etuberosum Lindl. - Jagesh K. Tiwari; Poonam; D. Sarkar; SK. Pandey; Jai Gopal; S. Raj Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Interaction studies of a novel Co(II)-based potential chemotherapeutic agent with human serum albumin (HSA) employing biophysical techniques - Farukh Arjmand; Poonam Tewatia; Mubashira Aziz; Rizwan H. Khan (Medicinal Chemistry Research, 2010)

Immunological detection of bean common mosaic virus in French bean (Phaseolus vulgaris L.) leaves - Poonam Verma; U. P. Gupta (Indian Journal of Microbiology, 2010)

Solvated Crystalline Forms of Nevirapine: Thermoanalytical and Spectroscopic Studies - Renu Chadha; Poonam Arora; Anupam Saini; Dharamvir Singh Jain (AAPS PharmSciTech, 2010)

Protective Role of Curcumin on Lindane Induced Reproductive Toxicity in Male Wistar Rats - Poonam Sharma; Rambir Singh (Bulletin of Environmental Contamination and Toxicology, 2010)

Appraisal of salinity and fluoride in a semi-arid region of India using statistical and multivariate techniques - Suman Mor; Surender Singh; Poonam Yadav; Versha Rani; Pushpa Rani; Monika Sheoran; Gurmeet Singh; Khaiwal Ravindra (Environmental Geochemistry and Health, 2009)

Analyzing hyper-spectral and multi-spectral data fusion in spectral domain - H. Pande; Poonam S. Tiwari; Shashi Dobhal (Journal of the Indian Society of Remote Sensing, 2009)

Lymphocyte recruitment into the tumor site is altered in patients with MSI-H colon cancer - Kristen M. Drescher; Poonam Sharma; Patrice Watson; Zoran Gatalica; Stephen N. Thibodeau; Henry T. Lynch (Familial Cancer, 2009)

Automatic urban road extraction using airborne laser scanning/altimetry and high resolution satellite data - Poonam S. Tiwari; H. Pande; Ashwini Kumar Pandey (Journal of the Indian Society of Remote Sensing, 2009)

Resynthesized Brassica juncea lines with novel organellar genome constitution obtained through protoplast fusion - Poonam Yadav; S. R. Bhat; S. Prakash; L. C. Mishra; V. L. Chopra (Journal of Genetics, 2009)

Identification of SSR Markers for Salt-tolerance in Rice Variety CSR10 by Selective Genotyping - Poonam Rana; Sunita Jain; Sheetal Yadav; Navinder Saini; R. K. Jain (Journal of Plant Biochemistry and Biotechnology, 2009)

A comparative study of antioxidative defense system in the copper and temperature acclimated strains of Anabaena doliolum - Yogesh Mishra; Poonam Bhargava; Riti Thapar; Ashish Kumar Srivastava; Lal Chand Rai (World Journal of Microbiology and Biotechnology, 2008)

Effects of adolescent fluoxetine treatment on fear-, anxiety-or stress-related behaviors in C57BL/6J or BALB/cJ mice - Maxine Norcross; Poonam Mathur; Abigail J. Enoch; Rose-Marie Karlsson; Jonathan L. Brigman; Heather A. Cameron; Judith Harvey-White; Andrew Holmes (Psychopharmacology, 2008)

Effects of adolescent fluoxetine treatment on fear-, anxiety- or stress-related behaviors in C57BL/6J or BALB/cJ mice - Maxine Norcross; Mathur Poonam; Abigail J. Enoch; Rose-Marie Karlsson; Jonathan L. Brigman; Heather A. Cameron; Judith Harvey-White; Andrew Holmes (Psychopharmacology, 2008)

Microbiological Quality and Organochlorine Pesticide Residue in Commercially Available Ready-To-Eat Raisins - Sapna Sharma; Prachi Chandra; Chetna Mishra; Poonam Kakkar (Bulletin of Environmental Contamination and Toxicology, 2008)

An overview of the genus Xylocarpus - Vijai Lakshmi; Poonam Gupta (Natural Product Research, 2008)

Use of laser range and height texture cues for building identification - Poonam S. Tiwari; Hina Pande (Journal of the Indian Society of Remote Sensing, 2008)

Toxic metals and organochlorine pesticides residue in single herbal drugs used in important ayurvedic formulation – ‘Dashmoola’ - Vartika Rai; Poonam Kakkar; Jyotsna Singh; Chetna Misra; Santosh Kumar; Shanta Mehrotra (Environmental Monitoring and Assessment, 2008)

Mineralization of 2-aminobenzenesulfonate by a bacterial consortium - Surjeet Singh; Poonam Singh; S. K. Awasthi; Anjali Pandey; Leela Iyengar (World Journal of Microbiology and Biotechnology, 2008)

Excess copper induces anoxygenic photosynthesis in Anabaena doliolum: a homology based proteomic assessment of its survival strategy - Poonam Bhargava; Yogesh Mishra; Ashish Kumar Srivastava; Om Prakash Narayan; Lal Chand Rai (Photosynthesis Research, 2008)

Assessment of Genetic Diversity Among Rice Genotypes with Differential Adaptations to Salinity Using Physio-morphological and Molecular Markers - Sheetal Yadav; Poonam Rana; Navinder Saini; Sunita Jain; Rajinder K. Jain (Journal of Plant Biochemistry and Biotechnology, 2008)

Formation and characterization of three dimensional human hepatocyte cell line spheroids on chitosan matrix for in vitro tissue engineering applications - Poonam Verma; Vipin Verma; Pratima Ray; Alok R. Ray (In Vitro Cellular & Developmental Biology - Animal, 2007)

Studies on the Genotoxicity of Endosulfan in Different Tissues of Fresh Water Fish Mystus vittatus Using the Comet Assay - Shilpi Sharma; N. S. Nagpure; Ravindra Kumar; Sanjay Pandey; Satish K. Srivastava; Poonam J. Singh; P. K. Mathur (Archives of Environmental Contamination and Toxicology, 2007)

Mitochondria: a hub of redox activities and cellular distress control - Poonam Kakkar; B. K. Singh (Molecular and Cellular Biochemistry, 2007)

A Study to Evaluate Heavy Metals and Organochlorine Pesticide Residue in Zingiber officinale Rosc. Collected from Different Ecological Zones of India - Chetna Mishra; Sapna Sharma; Poonam Kakkar (Bulletin of Environmental Contamination and Toxicology, 2007)

Induction of COX-2 by acrolein in rat lung epithelial cells - Poonam Sarkar; Barbara E. Hayes (Molecular and Cellular Biochemistry, 2007)

Mineralization of 4-aminobenzenesulfonate (4-ABS) by Agrobacterium sp. strain PNS-1 - Poonam Singh; Nils-Kåre Birkeland; Leela Iyengar; Ramanathan Gurunath (Biodegradation, 2006)

Immunoproteomic analysis of secretory proteins ofAspergillus fumigatus with specific IGE immunoreactivity - Poonam Gautam; Taruna Madan; W. N. Gade; P. Usha Sarma (Indian Journal of Clinical Biochemistry, 2006)

Salinity and Copper-Induced Oxidative Damage and Changes in the Antioxidative Defence Systems of Anabaena doliolum - Ashish Kumar Srivastava; Poonam Bhargava; Lal Chand Rai (World Journal of Microbiology and Biotechnology, 2005)

Rayleigh modes in anisotropic, heterogeneous poroelastic layers - Anil K. Vashishth; Poonam Khurana (Journal of Seismology, 2005)

Gauri Shankar Singhal (1933–2004): A Photochemist, a Photobiologist, a Great Mentor and a Generous Friend - Usha P. Andley; Poonam Nanda R. Velagaleti; Arindam Sen; Baishnab C. Tripathy (Photosynthesis Research, 2005)

Effects of genotype, explant orientation, and wounding on shoot regeneration in tomato - Poonam Bhatia; Nanjappa Ashwath; David J. Midmore (In Vitro Cellular & Developmental Biology - Plant, 2005)

Synthesis and Neuromuscular Blocking Activity of 16β-Piperidino Epiandrosterone Derivatives - Sonal Dubey; D.P. Jindal; Poonam Piplani; Louse C. Young; Behrooz Fathi; Alan L. Harvey (Medicinal Chemistry Research, 2005)

Altered melanoma cell surface glycosylation mediates organ specific adhesion and metastasis via lectin receptors on the lung vascular endothelium - Vaidehi Krishnan; Sanjay M. Bane; Poonam D. Kawle; Kikkeri N. Naresh; Rajiv D. Kalraiya (Clinical & Experimental Metastasis, 2005)

Biodegradation of 4-aminobenzenesulphonate by a newly isolated bacterial strain PNS-1 - Poonam Singh; L.C. Mishra; Leela Iyengar (World Journal of Microbiology and Biotechnology, 2004)

Tissue Culture Studies of Tomato (Lycopersicon esculentum) - Poonam Bhatia; Nanjappa Ashwath; Tissa Senaratna; David Midmore (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Genetic analysis of a CSR10 (indica) × Taraori Basmati F3 population segregating for salt tolerance using ISSR markers - Amit Kaushik; Navinder Saini; Sunita Jain; Poonam Rana; R.K. Singh; Rajinder K. Jain (Euphytica, 2003)

Effect of diazepam treatment and its withdrawal on pro/antioxidative processes in rat brain - Sarah Musavi; Poonam Kakkar (Molecular and Cellular Biochemistry, 2003)

Correlation studies on oil content and fatty acid profile of some Cruciferous species - S. Mandal; Sangita Yadav; Ranbir Singh; Gulnaz Begum; Poonam Suneja; M. Singh (Genetic Resources and Crop Evolution, 2002)

In vitro propagation of Stackhousia tryonii Bailey (Stackhousiaceae): a rare and serpentine-endemic species of central Queensland, Australia - Poonam Bhatia; Naveen P. Bhatia; Nanjappa Ashwath (Biodiversity and Conservation, 2002)

In vitro multiplication of Quercus leucotrichophora and Q. glauca: Important Himalayan oaks - Vijay K. Purohit; Sushma Tamta; Suman Chandra; Poonam Vyas; Lok Man S. Palni; Shyamal K. Nandi (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Cytoplasmic effects on photosynthesis and ribulose-1,5-bisphosphate carboxylase activity in Brassica species - Sivakoti Ramana; Poonam Sharma-Natu; Mohan C. Ghildiyal (Euphytica, 2002)

Improving the quality of industrially important enzymes by directed evolution - Rajendra Rani Chirumamilla; Reddivari Muralidhar; Roger Marchant; Poonam Nigam (Molecular and Cellular Biochemistry, 2001)

A test strip for the estimation of urea in serum - Hemant Kumar; Ashok Kumar; Poonam Kumari; N. B. Tulsani (Indian Journal of Clinical Biochemistry, 2000)

Pro and antioxidant responses to repeated administration of diazepam in rat brain - Sarah Musavi; Poonam Kakkar (Molecular and Cellular Biochemistry, 2000)

Arthropod–Frog Connection: Decahydroquinoline and Pyrrolizidine Alkaloids Common to Microsympatric Myrmicine Ants and Dendrobatid Frogs - John W. Daly; H. Martin Garraffo; Poonam Jain; Thomas F. Spande; Roy R. Snelling; César Jaramillo; A. Stanley Rand (Journal of Chemical Ecology, 2000)

Groundwater Quality Assessment of Tehsil Kheragarh, Agra (India) with Special Reference to Fluoride - M. K. Gupta; Vibha Singh; Poonam Rajwanshi; Meetu Agarwal; Kavita Rai; Shalini Srivastava; Rohit Shrivastav; Sahab Dass (Environmental Monitoring and Assessment, 1999)

Further Alkaloids Common to Ants and Frogs: Decahydroquinolines and a Quinolizidine - Tappey H. Jones; Jeffrey S. T. Gorman; Roy R. Snelling; Jacques H. C. Delabie; Murray S. Blum; H. Martin Garraffo; Poonam Jain; John W. Daly; Thomas F. Spande (Journal of Chemical Ecology, 1999)

Diazepam induced early oxidative changes at the subcellular level in rat brain - Sarah Musavi; Poonam Kakkar (Molecular and Cellular Biochemistry, 1998)

Leaching of aluminium from cookwares -- a review - Poonam Rajwanshi; Vibha Singh; M.K. Gupta; Sahab Dass (Environmental Geochemistry and Health, 1997)

GABA agonists and neurotransmitters metabolizing enzymes in steroid-primed OVX rats - Gurcharan Kaur; Poonam Sharma; Sanjeev Bhardwaj; Gurjinder Kaur (Molecular and Cellular Biochemistry, 1997)

Oxidative changes in brain of aniline-exposed rats - Poonam Kakkar; Sita Awasthi; P.N. Viswanathan (Archives of Environmental Contamination and Toxicology, 1992)

Association among geomagnetic activity, atmospheric electric field and selected meteorological parameters - Poonam Mehra (Advances in Atmospheric Sciences, 1990)

Lunar phases and atmospheric electric field - Poonam Mehra (Advances in Atmospheric Sciences, 1989)

Possible solar influence on atmospheric electric field - Poonam Sikka; A. Mary Selvam; A. S. Ramaehandra Murty (Advances in Atmospheric Sciences, 1988)